Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

A machine learning-based dual system coupling model of catalytic-gasification: a calcium-based case study with mechanistic interpretability - Yadong Ge; HongRu Li; Zaixin Li; Zhi Wang; Xiaoqiang Cui; Beibei Yan; Junyu Tao; Zhanjun Cheng; Ningbo Gao (Bioresource Technology, 2027)

Genetic architecture and genomic prediction of tail rotted disease tolerance in Cynoglossus semilaevis using INDEL markers identified by whole-genome resequencing - Mengyang Chang; Jibin Shen; Kunpeng Shi; Yishuai Li; Cen Ma; Jiayu Cheng; Yingming Yang; Zhongkai Cui; Songlin Chen; Zhenxia Sha (Aquaculture, 2027)

Physics-informed prediction of tunnel excavation-induced ground response in layered soils considering geostatic equilibrium - Zilong Cheng; Jun Shen; Xiaohua Bao; Xiangsheng Chen; Hongzhi Cui (Tunnelling and Underground Space Technology, 2026)

Geostationary observations of air pollutants from biomass burning: A synergy of GIIRS and GEMS over Southeast Asia - Shan Han; Shangyi Liu; Mengya Sheng; Jhoon Kim; Ximin Cui; Minqiang Zhou; Wei Wang; Isamu Morino; Voltaire A. Velazco; Zhao-Cheng Zeng (Remote Sensing of Environment, 2026)

Co-modified rice starch by extrusion and GML: multi-level structure - Jiaqi Song; Chong Cui; Zhuang Yang; Shiwen Cheng; Fan Yu; Jiangkai Zeng; Xiaoqi Ma; Xiaoshuai Yu; Zhigang Xiao; Lishuang Wang (Journal of Food Engineering, 2026)

Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Characteristics and constitutive model of segmented damage and fracture in granite under thermo-hydro-mechanical (THM) condition - Luping Cheng; Chun Wang; Yi Tan; Hao Li; Zonghong Zhou; Yumeng Ren; Juanjuan Li; Taihao Cui (Geothermics, 2026)

Preparation of MXene/MnO2/wood photothermal evaporator for efficient solar-driven water purification - Nan Zheng; Atian Xie; Guojun Cheng; Quan Li; Zhaozhao Li; Jiuyun Cui (Desalination, 2026)

The progress of mitochondrial function and transfer in stem cell regulation and therapy - Yubing Zhang; Zhuojian Qu; Zhiliang Guo; Lijuan Zhang; Hong Li; Xiaoyun Zhang; Xiumei Guan; Xiaodong Cui; Wenxu Wang; Min Cheng (Journal of Physiology and Biochemistry, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Restoration of membrane potential rescues organelle function via NS309-mediated KCa activation in aged porcine oocytes - Ying-Yan Jin; Cheng-Lin Zhan; Song-Hee Lee; Ji-Yeon Lee; Xiang-Shun Cui (Theriogenology, 2026)

Steam explosion-assisted method is a green and efficient extraction method for prebiotic pectins - Xu Zheng; Chengying Zhao; Yuyi Du; Yongkai Yuan; Hao Feng; Cheng Zhao; Jiefen Cui; Jinkai Zheng (Food Hydrocolloids, 2026)

Achieving adsorption re-centering via chemically locked Ni3S2@NiSe heterointerfaces for high-performance battery-type supercapacitors - Xiuzhang Zheng; Xi Wang; Peipei Yang; Lejiao Duan; Jianlong Huang; Liang Cui; Wenrong Yang; Xueying Cao; Degang Jiang; Zhenxiang Cheng; Jingquan Liu (Chemical Engineering Journal, 2026)

Stable acid-responsive two-component lipid vesicles for redox regulation-enabled ferroptosis-driven immunotherapy of hepatocellular carcinoma - Chengyuan Cai; Jing Wen; Xiao Wang; Zike Liao; Jinmei Cheng; Jiaxin Li; Jisheng Xiao; Zhong-Kai Cui; Xiaopin Duan (Chemical Engineering Journal, 2026)

Dual-tailoring of microenvironment and electronic structure in tandem catalysts for highly selective CO2-to-ethanol electroreduction - Shuo Cui; Cheng Yang; Tingting Tang; Xinjie Liu; Xinlong Huang; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Molten salt assisted thermochemical conversion of waste for production of sustainable fuels and chemicals: A review - Rehman Farooq; Cui Quan; Xizhi Cheng; Ye Shui Zhang; Aneta Magdziarz; Ningbo Gao (Biomass and Bioenergy, 2026)

Experimental study on flow field distribution and material separation characteristics in a pneumatic potato impurity removal device based on CFD-DEM coupling - Zhihao Tian; Zhongcai Wei; Yubo Liu; Guoliang Su; Zhen Cui; Faming Wang; Xiangcai Zhang; Xianliang Wang; Xiupei Cheng; Xiuhong Wang; Chengqian Jin (Computers and Electronics in Agriculture, 2026)

Dual-site magnetic microporous organic networks enabling high-performance capture and quantification of per- and polyfluoroalkyl substances - Chun-Ying Xu; Qing-Zhi Hou; Xiang-Sheng Xue; Zhan-Hui Qiu; Yuan-Yuan Cui; Cheng-Xiong Yang (Water Research, 2026)

Allelochemicals stimulation (ACS) strategy: Potential for studying allelopathy and discovery of phytotoxins - Dan He; Zhibo Hu; Haishan Cui; Cheng Li; Qiang Wang; Heng Guo; Lan Liu; Jing Li (Phytochemistry, 2026)

Selective flotation separation of spodumene from silicate gangue enhanced by ultrasound-induced interfacial dissolution - Dongfang Lu; Man Cui; Lanlan Chen; Jinrui Cheng; Mingzhu Zhang; Yuhua Wang; Xiayu Zheng (Minerals Engineering, 2026)

Hydrothermal synthesis of carbon-zeolite composites from coal gasification coarse slag and fine slag: Insight into residual carbon - Jungang Tang; Kaizhi Yang; Mingmin Bao; Li Cui; Jianming Gao; Fangqin Cheng; Kezhou Yan (Journal of Environmental Chemical Engineering, 2026)

Ag@BiPO4/MXene derived from F-containing nitrobenzene wastewater for efficient photocatalytic production of H2O2 - Die Zhou; Yu Liu; Guoqiang Shi; Diao Zhao; Xiyuan Cheng; Ren Cui; Daomei Chen; Jiaqiang Wang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal dynamics of global vegetation growth synchrony: Analysis from complex network - Fang Wu; Junwen Jia; Cheng Li; Xuefeng Cui (Global and Planetary Change, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Refrigerated cooked rice can retain its slow starch digestion property only with rice varieties having long amylose chains after microwave reheating - Jingru Zhuang; Yiyang Li; Lanbin Cui; Enpeng Li; Changquan Zhang; Cheng Li (Food Chemistry, 2026)

Acylation-based post-modification synthesis of an efficient fluorophilic magnetic microporous organic network for improved extraction of fluorine-containing drugs - Jia-Mei Kang; Can Liu; Yuan-Yuan Cui; Cheng-Xiong Yang (Food Chemistry, 2026)

Numerical analysis of seepage through earth dam considering deterministic modeling of heterogeneous cutoff wall parameter - Zhi-wei Cai; Ri-cheng Miao; Wei Cui (Engineering Geology, 2026)

Phosphonium-mediated engineering of polyamide membranes for efficient dye desalination - Dalong Zhang; Qianqi Cheng; Shengchao Chen; Kecheng Guan; Yuheng Guo; Boxiang Cui; Zhe Zhang; Dong Zou (Desalination, 2026)

Techno-economic and environmental assessment of biomass-to-gasoline production via dual fluidized bed gasification coupled with a syngas-to-gasoline process - Hongyu Cui; Yuwen Shao; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Weiming Yi; Baofeng Zhao; Lingyu Tai; Sunu Herwi Pranolo; Obie Farobie; Paolo De Filippis; Benedetta De Caprariis; et al. (Chemical Engineering Journal, 2026)

A novel composite reagent combined with a two-step calcination process for comprehensive detoxification of secondary aluminum dross - Lang Tao; Dehua Liang; Panhuan Wen; Cheng Chen; Fei Wang; Haibin Cui; Guojun Lv (Chemical Engineering Journal, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Iodine vapor adsorption induced liquid conductive metal-organic frameworks for self-powered humidity sensing - Weifang Zhang; Yuan Cheng; Lingling Zhuang; Ruijin Jiang; Cui-Cui Ji; Rong-Rong Xie; Yupeng Chen (Chemical Engineering Journal, 2026)

Future reshaping of soil freeze–thaw seasonality on the Tibetan plateau - Lanbo Cui; Fuqiang Wang; Wenjing Huang; Heng Zhao; Jiageng Hu; Jiahao Shi; Heng Wang; Yimei Cheng; Mengcheng Guo; Shreedhar Maskey (CATENA, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Size-dependent regulation of soil microbial functional-network structure by polystyrene microplastics - Guanlin Li; Junliang Chen; Yi Tang; Xiaoxun Zhao; Sushu Cui; Babar Iqbal; Pengfei Cheng; Tingting Zhao; Daolin Du; Peng Wang (Applied Soil Ecology, 2026)

A synergy strategy of deep eutectic solvents and boric acid modified β-CD polymer for enhancing enantioseparation in HPLC - Xiaoqian Yuan; Ziyi Cheng; Jiajia Fu; Wanting Duan; Yuchen Cui; Ruijun Tang; Xinru Wang; Youxin Li (Analytica Chimica Acta, 2026)

Association Between Circulating Essential Metals and Pregnancy Loss: A Systematic Review and Meta-Analysis - Liqin Wen; Meiqi Ren; Liantong Wang; Jinhua Cheng; Haoqing Liang; Haochen Ai; Yuxin Yao; Shuying Lin; Zhekai Cui; Xiao Shi (Journal of Trace Elements in Medicine and Biology, 2026)

Semi-Analytical Solution to 3D Tunneling Face Stability Considering Excess Pore Pressure - Yang Cheng; Zi-Xuan Cui; Ze-Hang Qian; Zhen-Yu Yin; Wan-Huan Zhou (Transportation Geotechnics, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Mechanisms of midgut injury induced by chronic trace concentrations of chlorantraniliprole in silkworm (Bombyx mori) - Sheng Zhang; Jialu Cheng; Xueling Qin; Guimin Nong; Xiaoqing Cui; Zhaoshen Lu; Bing Li (Pesticide Biochemistry and Physiology, 2026)

Mitigate dynamic response analysis of submerged floating tunnel (SFT) under wave and impact loads - Xiaolu Cui; Lihua Wang; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Stress characteristics of hydrogen polyethylene pipelines reinforced with multi-layer steel wire under combined winding angles - Peng Jin; Hongqiang Ma; Wei Cui; Yangchen Zhao; Mingkun Yang; Huilun Kang; Xiaosong Cheng; Yue Zeng; Jing Wu (Ocean Engineering, 2026)

A spatio-temporal route planning algorithm with stopovers for ship navigation in Arctic ice-covered regions - Bin He; Cheng Lv; Meng Cui; Zhongnan Yan; Yueyun Wang; Xiaoping Pang; Xiaohong Zhang; Yinan Zhou (Ocean Engineering, 2026)

Structural property and bioactivity evaluation of reactive oxygen species hydrogels loaded with different polyphenols - Ya Fan; Shengrong Duan; Haiyan Zhang; Chushou Li; Guiguang Cheng; Tianqi Cui (Food Chemistry, 2026)

Combined application of 1-methylcyclopropene and silicon-window modified atmosphere packaging delays cell wall degradation and softening in cold-stored ‘Saiwaihong’ apples - Cheng Zhao; Jiefen Cui; Hao Wu; Xuanming Tang; Xueping Wang; Mengyu Ma; Ting Liu; Yanfang Pan; Jinkai Zheng (Food Chemistry, 2026)

Preparation and performance evaluation of a novel Tween 80-based microemulsion system for the remediation of petroleum hydrocarbon-contaminated soil using soil washing test - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng (Environmental Research, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Multiscale optimization of solar interfacial evaporation systems: toward a new design paradigm for next-generation, high-efficiency solar-driven energy harvesting - Cheng Chi; Shiyu Liu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Huchuan Yan; Cui Lai (Desalination, 2026)

Inner Helmholtz plane reconstruction-driven dynamic capture and conversion of crystalline water enables ultra-long cycle life of FeHCF cathodes - Rui Sun; Danyu Cui; Zijun Deng; Zhengyang Zhao; Zhe Cheng; Longqing Zhang; Yuhong Liang; Quanqiang Yuan; Chengcheng He; Yan Zhang; Qian Ning; Yang Ren; et al. (Chemical Engineering Journal, 2026)

Bio-instructive polyetheretherketone implants combat implant-associated bone infections through inducing bacterial cuproptosis-like death and promoting peri-implant immune remodeling - Weinan Yang; Tao Zhang; Yongwei Zhou; Zizhan Su; Zihao An; Congsun Li; Jiaxuan Zou; Wushi Cui; Wentao Chen; Jian Xiao; Tao Sun; Shicheng Wang; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal footprints and health risk assessments of odor emissions from large-scale food waste anaerobic digestion plants - Lin Cui; Ziyang Lou; Long Kong; Farooq Muhammad Amjad; Zhijie Wang; Changfu Yang; Jun Si; Meilan Zhang; Luochun Wang; Zhaowen Cheng (Atmospheric Environment, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Vertical geochemical characteristics and coupling effects on organic carbon stability in coastal sediments of the Yellow Sea, China - Limin Cui; Mingxiang Pan; Yanru Shao; Manqing Cheng; Zizhen Qi; Xin Fang; Yang Yang; Lei Gao (Acta Oceanologica Sinica, 2026)

Integrated methylome and transcriptome analysis reveals molecular bases for growth variation in dmrt1-homozygous male Chinese tongue sole (Cynoglossus semilaevis) - Xu Yan; Chaoyang Su; Fangzhou Cheng; Lanqing Ding; Fei Fang; Zhongkai Cui; Songlin Chen (Aquaculture, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Structure evolution and dynamics of covalent kaolinite ionization under alkaline activation for strategic metal dissociation - Muyang Chen; Xi Chao; Li Cui; Yuchao Zhang; Bo Yang; Kezhou Yan; Yanxia Guo; Fangqin Cheng (Resources, Conservation and Recycling, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Coupled vibration characteristics and vibration mitigation of submerged floating tunnel-track-train under wave load - Xiaolu Cui; Lihua Wang; Ke Li; Wenlong Luo; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Ecological stability of the Late Miocene Tatsumi-toge biota revealed by plant–insect interactions - Cui Wang; Atsushi Yabe; Bingshan Niu; Wei Wang; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A “dual thiol-yne click” post-synthesis strategy for bifunctional magnetic microporous organic networks enabling synergistic extraction of trace benzoylurea insecticides - Chun-Xiao Liu; Chun-Ying Xu; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2026)

Hydrodynamics in microbubble column reactors: Effect of operating conditions and liquid properties - Linxiao Zhai; Yuhui Li; Yizhou Cui; Chengxiang Li; Yitong Cheng; Yunpeng Zhao; Xingying Lan; Jinsen Gao; Xiaogang Shi (Journal of Environmental Chemical Engineering, 2026)

Enhanced performance of a heat-exchange vacuum membrane distillation (HE-VMD) module integrating polymer hollow-fiber tubes - Cheng Wu; Fangli Zhang; Chenyang Gu; Zhaohui Wang; Zhaoliang Cui (Desalination, 2026)

Chloride-repelling and interfacial hydroxyl enrichment synergy in Co-Pi@Cr2O3-CoP for high current density alkaline seawater electrolysis - Tingting Tang; Cheng Yang; Xinlong Huang; Shuo Cui; Xinjie Liu; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Hydrogen-enriched nano-enhanced waste plastic pyrolysis oil blends: Combustion, emission, and machine learning-based optimization in a dual-fuel diesel engine - Zhenzhen Cui; Xiaoliang Cheng; Jie Wei; Xiaowei Yang (Biomass and Bioenergy, 2026)

Lifetime burden of congenital heart disease from 1990 to 2021: a systematic analysis from the Global Burden of Disease Study 2021 - Meng-Yi Liu; Yue Cui; Lu-Hong Qiu; Jia-Xing Zhang; Su-Xin Zhang; Jie-Ling Ma; Hong Pan; Jie-Xin Zhang; Wei-Guo Ma; Ji-Mei Chen; Zhi-Cheng Jing (Science China Life Sciences, 2026)

Priority control of potentially toxic elements in urban park soils through integrated source apportionment and health risk assessment - Xiangtian Man; Jian Sun; Xingnian Ren; Mengli Chen; Cheng Yang; Ruxin Yang; Ailian Li; Junfang Cui; Han Zhang (Environmental Geochemistry and Health, 2026)

Closing Knowledge Gaps on Global Budget of Nitrogen Oxides ( NO x ) by Quantifying Indirect Emissions From Anthropogenic Nitrogen - Yan Wang; Yulong Yin; Cheng Gong; Niveta Jain; Marta Alfaro; Martial Bernoux; Julia Drewer; Changke Wang; Alberto Sanz‐Cobena; Sylvia S. Nyawira; Zhenling Cui; Scott X. Chang; et al. (Global Change Biology, 2026)
Human activities emit nitrogen oxides (NO x ≡ NO + NO 2 ; with source emissions approximated as nitric oxide (NO)), potent air pollutants and short‐lived climate forcers, through direct and indirect pathways. Unlike direct releases, however, indirect NO x emissions remain poorly understood and inadequately quantified. Here, by synthesizing available observations across global terrestrial ecosystems, we show that soil moisture and pH strongly affect the ratio of annual background NO to nitrous oxide (N 2 O) emissions (), with a critical threshold at 46% water‐filled soil pore space. Combining soil moisture‐stratified modeled by machine learning with known indirect N 2 O emission factors, global indirect NO x emission factors () are derived, yielding an aggregated median of 1.59% (95% confidence interval (CI): 0.45%–2.41%) and significantly higher ( p x emissions resulting from atmospheric deposition of nitrogen released by all anthropogenic sources amounted to approximately 886 (95% CI: 314–1639) Gg N year −1 (1 Gg = 10 9 g) in 2015, with fertilization, animal husbandry, and other human activities contributing about 25%, 26%, and 49%, respectively. Crucially, without soil moisture stratification, the global indirect NO x emissions would be underestimated by approximately 16% ( p x emissions in regional, national and global inventories, thereby supporting targeted strategies to mitigate air pollution and climate change.

A Study on Twisted Rudders on Medium-Sized Transport Ships Based on Experiments and CFD - Jing Zeng; Hujia Cui; Xuankai Cheng; Yuzhe Chen (Journal of Marine Science and Engineering, 2026)
To enhance the energy efficiency of medium-sized transport vessels, one set of conventional flat rudders and three sets of twisted rudders with different twist angles were designed for a single-propeller single-rudder medium-sized transport ship. By combining model tests and computational fluid dynamics (CFD) numerical simulations, this paper systematically investigates the influence of twist angle on ship propulsion performance and energy-saving effects and reveals the corresponding energy-saving mechanism. The results show that compared with the conventional flat rudder, all three sets of twisted rudders achieve energy savings, with the main engine power reduced by approximately 1.0%. Within the research scope of this paper, the energy-saving effect improves with the increase in twist angle. Compared with the flat rudder, the installation of a twisted rudder leads to reductions in propeller thrust, torque, and rudder resistance, while the propeller’s rotational speed remains essentially unchanged. The CFD calculation results are in good agreement with the experimental data, which accurately reflect the flow field differences and explain the energy-saving mechanism. Thus, CFD can be used as an effective method for the design and optimization of twisted rudders.

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

CFSS strut system: A prefabricated method with low-carbon, economic and safety performance in deep excavation - Xuesong Cheng; Chenkai Li; Fan Yi; Qinghan Li; Jiqing Zhang; Peng Zhang; Tao Cui; Bo Li (Transportation Geotechnics, 2026)

Development and verification of a frequency-domain integrated analysis framework for floating wind turbines under operational and parked conditions - Wenbin Zhou; Zhengshun Cheng; Shi Deng; Wenxi Shao; Minghao Cui (Ocean Engineering, 2026)

A multi-directional aerodynamic load reproduction method for hybrid model testing of floating vertical-axis wind turbines - Shixiang Deng; Minghao Cui; Qun Cao; Lei Liu; Lijun Yang; Zhengshun Cheng (Ocean Engineering, 2026)

Interannual variability and evolution of pan-arctic melt pond fraction associated with atmospheric circulation during 2000–2023 - Jiajun Feng; Bin Cheng; Qiuming Cheng; Xiangbin Cui; Gang Li; Yuanzhi Zhang (Global and Planetary Change, 2026)

Synthesis of octenyl succinic anhydride-modified corn starch: Focusing on the C2, C3 and C6 substitution positions of anhydroglucose units - Wei Gao; Yifan Chen; Yue Cheng; Xuemin Kang; Xingtao Yu; Wenguo Wang; Bo Cui; A.M. Abd El-Aty (Food Chemistry, 2026)

Enhancing geo-localization for crowdsourced flood imagery via LLM-guided attention - Fengyi Xu; Jun Ma; Waishan Qiu; Cui Guo; Jack C.P. Cheng (Computers, Environment and Urban Systems, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Genetic characteristics and agronomic traits in leafy head Chinese cabbage breeding - Yancan Li; Bing Cui; Yihui Zhang; Qian Ding; Faujiah Nurhasanah Ritonga; Fengde Wang; Han Zheng; Cheng Li; Yiran Xu; Xingfu Liu; Lixia Wang; Jianwei Gao; et al. (Theoretical and Applied Genetics, 2026)

Paeoniflorin's role in inhibiting malignant metastasis of gastrointestinal stromal tumors via CYP3A4 modulation - Dapeng Cui; Zeyin Cui; Yansen Li; Shuang Fan; Lei Li; Cheng Yang; Ruixia Yu; Jiaxin Cui; Runjia Fu; Jiandong Fei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Study on seepage characteristics of coal fracture networks based on fractal theory and micro-CT - Wenting Cui; Yanbin Yu; Weimin Cheng; Jie Zang; Zihao Yuan (Bulletin of Engineering Geology and the Environment, 2026)

n ‐Alkane Gradients Reshape Soil Microbial Networks and Functions at Petroleum Refinery Sites - Youru Zhang; Shixuan Cui; Yu Zhang; Jizhuang Chu; Kaiyue Liu; Xinjie Shan; Na Wang; Shudi Yao; Qiang Kong; Cheng Dong; Huanxin Zhang (Environmental Microbiology, 2026)
Petroleum refining activities exert substantial contamination pressure on soil ecosystems, yet the corresponding microbial response mechanisms remain insufficiently understood. This study integrates source apportionment, high‐throughput sequencing and co‐occurrence network analysis to elucidate microbial adaptations along a petroleum exposure gradient. Source analysis confirmed that all soils were predominantly influenced by petroleum‐derived inputs, with hydrocarbon concentrations increasing significantly across gradients. Under contamination levels of 422.35–621.21 mg/kg, petroleum pollution not only reduced soil total organic carbon (TOC) but also induced coupled C–N interactions and altered soil physicochemical properties, resulting in complex environmental effects. The soil quality index (SQI) exhibited a nonlinear trend, first decreasing and then increasing, with moderate overall levels (0.40–0.45). Functional diversity analyses indicated functional convergence rather than loss under contamination stress. At the metabolic level, low exposure primarily stimulated naphthalene degradation and detoxification pathways, whereas high exposure shifted microbial functions towards oxidative stress resistance and membrane structural remodelling. Meanwhile, microbial networks transitioned from densely connected but disturbance‐sensitive structures at low exposure to simplified yet more stable and robust configurations at high exposure. These findings provide mechanistic insights into microbial adaptation in petroleum‐contaminated soils and offer theoretical support for bioremediation strategies.

A comprehensive review of lactic acid bacteria-fermented plant-based beverages: substrate types, nutritional quality, probiotic characteristics, metabolic pathways and future development trends - Yiwen Chen; Yue Hu; Yun Xie; Miao Cui; Jianqiao Jiang; Yongkang Li; Jingyi Guo; Mengjie Xiang; Zheng Tian; Jianming Niu; Weidong Cheng; Feifei Gao (Critical Reviews in Food Science and Nutrition, 2026)

Establishment of CRISPR/Cas9-mediated gene editing and larval rearing techniques in Epinephelus fuscoguttatus - Fangzhou Cheng; Jiaqing Xu; Xinkai Cheng; Guanglue Li; Zhongkai Cui; Chaowei Li; Xu Yan; Qiaomu Hu; Songlin Chen (Aquaculture, 2026)

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Performance study of nickel-potassium/calcium oxide catalyst for carbon dioxide capture and conversion - Cui Quan; Haojie Suo; Xiaobin Liu; Xizhi Cheng; Ningbo Gao (Sustainable Chemistry and Pharmacy, 2026)

Coupled dynamics and resonance mitigation of submerged floating tunnel roadways under transient impact loads in marine environments - Xiaolu Cui; Jing Chen; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong; Pupeng Ai; Shixiao Fan (Ocean Engineering, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Decoding the effect of intermittent feeding strategy on the performances of modular moving bed constructed wetland: Nitrogen removal and antimicrobial resistance dissemination - Lei Zhou; Jiawei Xie; Liming Zhang; Xueqing Sui; Weicong Wang; Jianshi Huang; Shuangqi Wu; Naxin Cui; Shengbing He; Shuiping Cheng (Journal of Hazardous Materials, 2026)

Metabolic engineering of Yarrowia lipolytica for liquiritin production - Cun-Cui Kong; Xiao-Jing Wang; Hong-Xia Zhang; Song Qin; Cheng-Gang Ren (Chemical Engineering Journal, 2026)

Recycling spent lithium-ion batteries as high-performance catalysts for peracetic acid activation toward rapid degradation of organic pollutants - Ge Li; Yujie Cheng; Yufei Wu; Yuhao Tian; Bowen Yang; Haoran Chen; Guosen Zhang; Zhengqian Liu; Yuhong Cui; Jun Ma; Pengchao Xie (Chemical Engineering Journal, 2026)

Optimizing hydrogenation activation pathway in Cu-based hierarchical microspheres for sustainable nitrophenols hydrogenation with ultralow-reductant-consumption - Fengting Geng; Jiajia Cheng; Xuexin Niu; Xiaoli Wang; Hongxing Wang; Chaoyue Zhao; Ling Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Lifeng Cui; Longlong Geng (Chemical Engineering Journal, 2026)

Design of millimeter-sized porous carbon spheres guided by hydrodynamic principles - Xiao-Dong Shi; Cheng-Tong Wang; Wen-Cui Li; Hong-Lei Wang; An-Hui Lu (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Sedimentological and microstructural characteristics of weakly cemented strata formations in Chinese Coal Mines - Peichao Feng; Wei Qiao; Xianggang Cheng; Mengnan Liu; Xiangsheng Meng; Mengke Cui (Bulletin of Engineering Geology and the Environment, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

From biological to structural controls: explainable machine learning reveals depth-dependent shifts in predictors of soil organic carbon and microbial biomass across depth in subtropical plantations - Jingjing Zhuang; Cuina Yang; Yixuan Wang; Linbo Ma; Cui Cheng (Biology and Fertility of Soils, 2026)

An interpretable and adaptive tunnel water inflow prediction method using data augmentation and AHP-Enhanced OP-LightGBM - Jingqi Cui; Shunchuan Wu; Haiyong Cheng; Xiaowei Hou; Jiaxin Wang; Weihua Liu; Chaoqun Chu (Tunnelling and Underground Space Technology, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Flow behavior and entropy production in microcapillary-based joule–thomson refrigeration under various inlet-to-outlet pressure ratios - Xin Zhang; Longyu Yang; Han Gong; Wendi Bao; Biao Wang; Chen Zheng; Cheng Shao; Zheng Cui (International Journal of Refrigeration, 2026)

Exploring the mechanism of variation in 3D printing shape stability and mechanical performance of starch/gelatin printed products during dehydration process - Yue Cheng; Wei Gao; Xuemin Kang; Bo Cui (Food Research International, 2026)

Regulating chemistry and wettability of chitosan-based colloidal particles for dextran-in-PEG highly dispersed phase emulsions - Shukai Cheng; Liuyan Zhu; Wanying Cui; Ran Hong; Maodong Xu; Zhenxia Song; Jian Zhao; Cuige Zhang; Chunmiao Xia; Rongli Zhang (Food Hydrocolloids, 2026)

Assessment on attenuation, accumulation, and ecological risk of venlafaxine in aquatic ecosystems Co-exposed to polypropylene microplastics - Qi Lv; Jindong Xu; Cheng Ruan; Luosheng Cui; Na Ran; Zhenglu Wang (Environmental Research, 2026)

In situ formed biphasic high-entropy silicate ceramic aerogels reinforced by Al2O3 nanorods for high-temperature thermal insulation - Sisi Shang; Wenzhuo Hao; Zhen Zhang; Cheng Zhou; Jian Yang; Sam Sukgoo Yoon; Sheng Cui (Chemical Engineering Journal, 2026)

Sweat-responsive natural small-molecule-based co-assembled hydrogels: multifunctional properties, transdermal delivery, and potential for hyperhidrosis therapy - Mingping La; Jiamei Le; Chunxia Yin; Pan Cheng; Fen Ju; Xiaohong Zhu; Cui Li (Chemical Engineering Journal, 2026)

Starch as a designable platform for oral drug delivery: From structural modulation to application in inflammatory bowel disease - Mengyuan Qin; Feng Jiang; Yan Hong; Lingjin Li; Yongmin Cui; Canran Jin; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2026)

Co-hydrothermal carbonization as a sustainable treatment for pharmaceutical sludge-wheat straw blends: synergistic effect analysis and mechanistic investigation - Wang Liang; Yihao Cui; Saiyu Cheng; Yonghui Han; Yali Huang (Bioresource Technology, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Quantitative research and implications on policy texts of China’s maritime strategic scientific and technological strength: an analysis based on the three-dimensional framework of “instrument–objective–actor” - Xiaoyu Cui; Wanglai Cui; Yiqian Ding; Cheng Lang; Yunjie Zhang; Xiaoxiao Lin (Frontiers in Marine Science, 2026)
This paper constructs a diamond model for expanding national strategic marine scientific and technological capabilities, establishes a three-dimensional analytical framework of “policy instruments—policy objectives—policy actors,” and conducts a quantitative analysis of 229 policy documents using Nvivo 12. The results indicate that existing policy instruments are inadequately aligned with major strategic needs, production factors, and policy objectives; there is an imbalance in the application of instruments and the distribution of actors; and the system exhibits significant institutional endogeneity. The root causes lie in the allocation of powers and responsibilities between the central and local governments and fragmented inter-departmental governance. Based on these findings, the following optimization directions are proposed: enhance the alignment between policy instruments and objectives, and strengthen demand-side incentives to boost supply; use objectives to guide improvements in the quality of factor supply, focusing on talent development and breakthroughs in core technologies; improve the coordination system among laws, regulations, and policies; and restructure the mechanisms for central-local authority allocation and inter-departmental coordination to address the problem of entrenched preferences in instrument selection at the institutional level.

An efficient synthesis of halogenated 1,4,5,8-tetramethoxynaphthalenes - Gaoyang Yuan; Chenwu Liu; Jiqing Chen; Taohong Shi; Shouyan Xiang; Xiao Yu; Qilai Cheng; Jiahua Cui (Natural Product Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Early Cretaceous radiolarian assemblages in mélange of Yarlung-Tsangpo suture zone in the Saga area, southern Xizang - Zhi-Hao He; Xin Li; Ya-Lin Li; Atsushi Matsuoka; Hui Luo; Xiao-Hui Cui; Jian-Bo Cheng (Palaeoworld, 2026)

Uncovering the dynamic role of bedrock-stored water in ecosystem evapotranspiration - Yang Qiu; Fawang Zhang; Lin Gao; Zekang He; Hanxiang Xiong; Ling Peng; Zhiye Wang; Hao Cui; Cheng Su; Defang Zhang; Shizheng Zhou; Chuanming Ma; et al. (Journal of Hydrology, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

Synergistic utilization of circulating fluidized bed fly ash and pulverized fly ash in low-carbon solid waste cementitious materials: Performance and hydration mechanism - Jianmin Li; Liwen Guo; Ye Li; Jiayong Zhang; Cheng Zhang; Hui Pan; Xiao Cui; Xiaofan Zhao (Journal of Environmental Chemical Engineering, 2026)

Insights into gasification conversion mechanism of lignin in CO2/H2O environment: ReaxFF molecular dynamics simulation - Wang Liang; Saiyu Cheng; Yihao Cui; Yonghui Han; Yali Huang; Chunhe Jiang; Xiaojun Ning; Lihua Gao; Zhijun He; Chuan Wang; Guangwei Wang (Journal of Environmental Management, 2026)

Microemulsion flushing of petroleum hydrocarbons in porous media: Microfluidic insights into residual oil morphologies and removal mechanisms - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng; Quanbin Jin (Journal of Environmental Management, 2026)

Combined process of magnesium oxide precipitation-extraction for efficient recovery of cobalt and nickel from extraction slag of spent Li-ion batteries - Zhou Jiang; Jinsong Shi; Nanfu Yan; Yaqing Weng; Runhan Yan; Ting Cheng; Huiqin Guo; Hongmin Cui (Journal of Environmental Management, 2026)

Combining staged combustion and oxygen enrichment for stable and low-NOx porous media combustion of ammonia - Heng Zhang; Bang Cui; Jianguo Du; Zhou Yu; Xiong Liang; Yi-Bing Cheng; Yu Wang (Fuel, 2026)

Experimental investigation of plasma activation on RP-3 cracking and atomization within a circumferential flameholder - Hao Wang; Xinyao Cheng; Di Jin; Huimin Song; Min Jia; Zhibo Zhang; Wei Cui; Jiulun Sun (Chemical Engineering Journal, 2026)

Top-down constraint on CO emissions by incorporating emission heights: insights from COVID-19 activity changes in Nanchang city, China - Cheng Hu; Xuejing Shi; Lingjun Xia; Qitao Xiao; Guoqiang Bai; Fan Sun; Yifan Zhang; Yu Cui (Atmospheric Pollution Research, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Metagenomic sequencing reveals high reproducibility of human donor microbiota transplanted into germ-free mice via lower gut route - Yapeng Yang; Xiang Tan; Zeyue Zhang; Lifeng Liang; Zhifeng Wu; Jinhui He; Yuqing Wang; Miaomiao Dong; Jixia Zheng; Hang Zhang; Shuaifei Feng; Wei Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Copper-loaded halloysite nanotube-coated chitosan sutures: Enhanced antibacterial activity, mechanical strength, and reduced burst-release toxicity - Renzheng Guan; Xinyan Hao; Chuyang Chen; Guangqi Cheng; Qianchen Huang; Shuang Wang; Fang Wang; Jiwei Li; Aihua Cui; Shaohua Zhang (Applied Clay Science, 2026)

First Acoustic Evidence of Omura's Whale ( Balaenoptera omurai ) in the South China Sea - Chao Li; Huayong Yang; Haocai Huang; Jinping Cheng; Hongxing Cui (Marine Mammal Science, 2026)

Asymmetric Shifts in Precipitation Alter Nitrogen Use Strategies in Global Croplands - Jinglan Cui; Yujing Gao; Luxi Cheng; Xi Zhang; Ouping Deng; Miao Zheng; Zhongrui Xie; Hans J. M. van Grinsven; Lorenzo Rosa; Baojing Gu (Global Change Biology, 2026)
Global warming intensifies regional precipitation imbalances that disrupt cropland nitrogen cycling and threaten food security. Here, we show that global croplands respond asymmetrically to future precipitation change. Under a middle of the road scenario for 2050, 78% of croplands are projected to become wetter, increasing yields by 15% but raising nitrogen losses by 45%. The remaining 22% that become drier would experience a 29% decline in yields and a 25% rise in nitrogen losses. Nitrogen use efficiency declines by 3%–14% worldwide because both wetter and drier conditions reduce plant uptake or accelerate losses. Although altered precipitation increases global crop production by 8%, the accompanying 43% rise in nitrogen losses may compromise long term sustainability. Subtropical and tropical regions between 30° N and 30° S emerge as disruption hotspots. Adaptation measures such as optimized fertilizer management and adjusted planting dates could mitigate up to 462 billion USD per year in damages linked to nitrogen losses. These results highlight the need for adaptive strategies to secure food production and environmental sustainability under asymmetric precipitation change.

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

The sialyltransferase ST3GAL1 mediates MUCL1 sialylation to exacerbate breast cancer progression - Can Cui; Jing Feng; Boyu Shang; Qingxin Guo; Shuren Wang; Qi Wang; Fumin Cheng; Yi Zhou (Human Cell, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Analysis of thermal–mechanical responses of resonant rubblized concrete pavement system with asphalt overlay under diverse climatic conditions - Liyuan Liu; Jie Deng; Huailei Cheng; Kaili Hao; Lijun Sun; Miomir Miljković; Chen Cui (Transportation Geotechnics, 2026)

High-resolution spatiotemporal dynamic simulation and driving force analysis of carbon emissions in coastal cities: The case of Ningbo City - Guangxin Cui; Xusheng Cheng; Yanwei Sun; Chao Gao; Zheng Duan; Tian Ruan (Sustainable Cities and Society, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Comparing the effects of single and coupled sloshing excitation on the self-cleaning hydrodynamic performance of the aquaculture tank on an offshore vessel - Fuzhi Zu; Can Cui; Haoran Cheng; Yanfei Wu; Jiajun Hu; Lianhui Wu; Dezhen Li; Fukun Gui; Dejun Feng; Fei Wang (Ocean Engineering, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Carbon flux dynamics and carbon use efficiency and their key environmental drivers in a climate-sensitive Picea crassifolia forest - Boliang Cui; Chuanyan Zhao; Fei Zang; Linsong Wang; Fangshu Cheng; Tiansheng Gao; Zhongren Nan (Journal of Environmental Management, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Genomic selection accelerates genetic improvement of tolerance to visceral nodular disease in the half-smooth tongue sole (Cynoglossus semilaevis) - Mengyang Chang; Kunpeng Shi; Jibin Shen; Yu Yang; Yishuai Li; Jiayu Cheng; Xiangming Cheng; Yingming Yang; Zhongkai Cui; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Electrohydrodynamic direct-writing metal-ammonia complexed porous polymer fiber for highly sensitive and stable humidity sensor - Yifang Liu; Qintong He; Xianruo Du; Chenqi Zheng; Yisheng Zhong; Ruixin Chen; Yinuo Wang; Yuxiang Wu; Shufan Li; Xiang Cheng; Gaofeng Zheng; Huatan Chen; et al. (Chemical Engineering Journal, 2026)

Simultaneous remediation and fertilization of saline-alkaline soil via the application of various phosphorus-rich hydrochars - Ran Duan; Yuxin Yang; Xuchen Zhang; Junxia Wang; Jipeng Luo; Xiaoqiang Cui; Zhanjun Cheng; Guanyi Chen (Chemical Engineering Journal, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Environmental filtering of microbial specialists drives divergent C, N, and S cycling in grasslands: Vegetation buffering maintains microbial diversity amidst soil moisture contrasts - Yiming Dai; Haining Wang; Qixiu Cheng; Yiming Zhang; Ye Cui; Huan Ma; Xiaoyu Li; Daolong Xu; Jin Chen (CATENA, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

Integrating CO2-EOR and Sequestration via Assisting Steam Huff and Puff in Offshore Heavy Oil Reservoirs with Bottom Water - Guodong Cui; Kaijun Yuan; Haiqing Cheng; Quanqi Dai; Xi Chen; Rui Wang; Zhe Hu; Zheng Niu (Journal of Marine Science and Engineering, 2026)
CO2-assisted steam huff and puff is an effective method to improve oil recovery and store CO2 in heavy oil reservoirs. However, few studies focused on complex geological formations, such as bottom water. The bottom water condition not only complicates the process of oil production and CO2 sequestration, but also makes migration and distribution of oil, water and CO2 unclear. In this paper, a numerical geological model of an offshore heavy oil reservoir with bottom water is established to analyze the influence of bottom water on injection and production parameters, oil recovery and CO2 storage capability under vertical and horizontal well layouts. The results show that the bottom water could maintain the formation pressure, but reduce the steam chamber radius and heavy oil utilization area, increase water production and decrease the oil–water ratio. CO2 could enhance oil recovery in the bottom water reservoir. Oil development indicators of the horizontal well are higher than the vertical well. Meanwhile, CO2-assisted steam huff and puff use in the bottom water reservoir can create a high-pressure and -temperature environment to make CO2 supercritical, as it has better CO2 storage capability and efficiency. The CO2 storage efficiency of the horizontal well is 63% larger than the vertical well. Thus, the horizontal well layout should be used as a priority if bottom water presents. Conducted analysis of bottom water formation sensitivity parameters shows that the advantageous formation conditions are high oil saturation, porosity of 0.2–0.4 and permeability of 2000–3000 mD. The influence degrees of each formation parameter were evaluated as well.

Ascertaining and optimizing bearing performance for deformed shield tunnels reinforced with epoxy-bonded steel plates - Zhiwei Zhang; Xuesong Cheng; Tianqi Zhang; Hao Fu; Liyang Qi; Tao Cui; Peng Zhang; Gang Zheng (Tunnelling and Underground Space Technology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Dermal exposure to heavy metals contaminated soil from e-waste sites: Linking bioaccessibility to cellular uptake, cytotoxicity, and transport mechanisms in skin cells - Daolei Cui; Hua Zhong; Ziya Ma; Yiping Cheng; Chengxin Liu; Jingya Li; Jiaoyang Ma; Ping Xiang (Journal of Hazardous Materials, 2026)

Self-heating characteristics of rice straw in a 120-L insulated container: Experiments & CFD studies - Mingshuo Cui; Xinke Chen; Yuan Li; Tingting Luo; Qianhua Huang; Qingyan Fang; Peng Tan; Cheng Zhang; Gang Chen; Chungen Yin (Fuel, 2026)

NMR-based quantitative characterization and predictive modeling of adsorbed and free methane in deep coal reservoirs - Xinyu Fu; Shida Chen; Fan Yang; Shu Tao; Litao Ma; Cheng Liu; Jianghao Yang; Yi Cui; Qinghe Jing; Wei Gao (Fuel, 2026)

Unraveling novel pancreatic lipase and cholesterol esterase inhibitory peptides in Oryza Sativa L. and their mechanism by peptidomics, molecular dynamics simulations, and cell study - Liuyi Wei; Taoying Wu; Hao Wu; Li Wen; Bo Cui; Yunhui Cheng (Food Bioscience, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Research on surface hydrophobic modification and flotation decarbonization of coal gasification fine slag - Gan Cheng; Ruiwen Guo; Penghao Gao; Cui Xu; Peigao Duan; Zhiguo Zhang; Xiaowei Deng; Kezhou Yan; Fangqin Cheng (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dynamic Mechanisms of Land Use Conflict Under Main Function Oriented Zone Planning: A Case Study of Beijing-Tianjin-Hebei Region - Yang Zheng; Linlin Cheng; Junqi Wang; Yifang Wang; Huizhen Cui (Chinese Geographical Science, 2026)

Credibility-driven identification of cropland runoff source in surface waters using ANN-XGBoost model ensemble powered by microbial fingerprints - Pengcheng Li; Lu Dong; Liping Li; Mengzhu Xue; Guohui Xia; Kening Wang; Xin Zhang; Peng Liu; Cheng Zhang; Baoshan Cui; Junhong Bai; Xinhui Liu (Water Research, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Intensified NAO-South Asian Monsoon teleconnection during the Little Ice Age: Insights from speleothem records - Jingyao Zhao; Wen Liu; Liangkang Pan; Qiuqiu Luo; Jiahui Cui; Jian Wang; Kexin Wang; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Efficient lithium recovery from aluminum electrolytic slag via HCl solution: Leaching behavior and mechanism - Xi Chao; Guannan Li; Hefeng Yuan; Li Cui; Lijuan Wang; Fangqin Cheng (Minerals Engineering, 2026)

Nanocellulose fibers as stabilizers for Pickering emulsion coatings - Yong Cui; Yanyi Xue; Xinyi Zheng; Chen Cheng; Xiaolu Xu; Wenliang Wang (Journal of Food Engineering, 2026)

Microscopic insights into the fading mechanism of the hydrate memory effect - Liwei Cheng; Runze He; Jinlong Cui; Qun Yi; Bei Liu; Guangjin Chen (Fuel, 2026)

Influence of insufficient concrete consolidation at stud roots on the static and fatigue behavior of headed studs - Jiawei Liu; Qinghua Zhang; Zhenyu Cheng; Yuhao Zhang; Chuang Cui; Guoxi Liang (Engineering Structures, 2026)

Static and fatigue behaviors of ultrashort stud connectors embedded in ultra-thin, ultrahigh-performance concrete - Jiawei Liu; Qinghua Zhang; Zhenyu Cheng; Chuang Cui; Guoxi Liang (Engineering Structures, 2026)

Ion-mediated interfacial water reconstruction in cellulose-biochar aerogels enables seawater evaporation faster than pure water - Man Yuan; Lei Yang; Wei Liu; Meng Hu; Cheng Zhou; Xiaobei Guo; Sheng Cui (Chemical Engineering Journal, 2026)

Insight into the adsorption mechanism of gallium, vanadium on amidoxime resin and cascade desorption for synergistic recovery - Li Cui; Muyang Chen; Yu Zhang; Lijuan Wang; Bo Yang; Fangqin Cheng (Chemical Engineering Journal, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Transcriptome Analysis of 17α-Methyltestosterone-Induced Sex Reversal in Pseudopleuronectes yokohamae - Luyao Cheng; Xiaoxuan Sun; Zhen Meng; Wenteng Xu; Aijun Cui; Yongjiang Xu (Fishes, 2025)
Marbled flounder (Pseudopleuronectes yokohamae) exhibits a distinct female growth advantage and an XX/XY sex determination system. To exploit these traits, we investigated 17α-methyltestosterone (MT)-induced transcriptomic changes in gonadal tissue with the goal of generating pseudomale XX broodstock for all-female fry production. Full-sibling diploid juveniles (60 days post-hatching, dph) were fed diets containing 0 (control), 0.5, or 2 mg/kg MT for 120 days, followed by a 60-day recovery period on a commercial diet prior to sampling. Testicular transcriptomes were profiled via high-throughput sequencing, and key differentially expressed genes were validated using qPCR. Both MT treatments resulted in 100% masculinization. Testicular transcriptome analysis revealed 972 differentially expressed genes (DEGs) (180 up, 792 down) in the 0.5 mg/kg MT-treated males (MT05M) compared to the control males, and 1245 DEGs (842 up, 403 down) in the 2 mg/kg MT group (MT20M). Gene Ontology terms were enriched for extracellular space and signaling receptor regulator activity. KEGG pathway analysis indicated significant enrichment in neuroactive ligand–receptor interaction, ovarian steroidogenesis, and TGF-β signaling. qPCR confirmed significant downregulation (p

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The potential impact of glacier volume changes on biome dynamics in the southeastern margin of the Tibetan Plateau since the last deglaciation - Pengyu Li; Ziru Hao; Yang Yang; Xiao Zhang; Mengna Liao; Lina Liu; Kai Cui; Yongbo Wang; Haiyan Li; Jun Cheng; Kai Li; Jian Ni (Quaternary Science Reviews, 2025)

Detailed Asian summer monsoon changes during the Mid Holocene and their teleconnections with the northern high latitudes - Bin Zhao; Yingfang Cui; Kan Zhao; Yongjin Wang; Hai Cheng; R. Lawrence Edwards; Yijia Liang (Quaternary Science Reviews, 2025)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

The role of Cu precursors and reaction mechanism for Cu/IM-5 hierarchical molecular sieve in NH3-SCR - Xinwei You; Zhifang Li; Wenyao Tan; Zhengzhong Cheng; Yuanyuan Ma; Qianhua Song; Jinxing Cui (Journal of Environmental Chemical Engineering, 2025)

Molecular mechanisms underlying microplastics-induced inhibition of lateral root development in tomato (Solanum lycopersicum L.) - Rongchao Yang; Mengjiao Chen; Long Cheng; Yilan Cui; Chengyong Li; Yueqin Zhang (Journal of Environmental Management, 2025)

Multiphase stable coexistence of heterojunction 1T/2H-MoS2@NH2-MIL-125(Ti) for efficient photocatalytic degradation of tetracycline - Cheng Bu; Xuewen Guo; Jing Yang; Heyong Huang; Dapeng Zhang; Shihai Cui (Journal of Environmental Chemical Engineering, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Impact of soluble soybean polysaccharides with different molecular weights on the pasting, gel, and structural properties of potato starch - Huishan Shen; Shangzhen Cheng; Zan Cui; Weimin Kang; Yanyan Zhang; Xingli Liu; Hongwei Wang; Hua Zhang (Food Chemistry, 2025)

Design, preparation, characterization, and application of smart antibacterial films coated by ε-polylysine/2-pyridinecarboxaldehyde/Iron(Ⅱ) - Fangxuan Yi; Xiangyou Wang; Jie Huang; Kangqing Yuan; Yingjun Cui; Meng Cheng (Food Packaging and Shelf Life, 2025)

Bacterioferritin-driven oxidative stress resistance in anammox bacteria: Mechanistic insights into reactive oxygen species scavenging - Jin Wang; Yi-Cheng Wang; Cui-Zhong Chen; Jing Wang; Peng Yan; You-Peng Chen (Environmental Research, 2025)

Synergistic valorization of red mud and spent coffee grounds via one-step hydrothermal carbonization for high-efficiency Pb(II) and Cd(II) removal from wastewater - Yuting Cui; Yue Zhou; Mingqian Cheng; Wei Fang; Yaoling Wang; Chao Chen; Tingting Liu; Bin Li; Zewei Liu (Desalination, 2025)

High-performance porous liquid composite hollow fiber membranes for enhanced CO₂ removal in artificial lungs - Xiaoyun Wang; Liping Luo; Dejian Chen; Rizhi Chen; Huiqin Zhang; Yangming Cheng; Xufeng Chen; Zhaoliang Cui (Chemical Engineering Journal, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Ultrasound-coupled acid/alkali treatment of sewage sludge: Impacts on phosphorus release and speciation transformation - Chunying Dong; Junjie Feng; Micong Jin; Meiqiang Cai; Zhuohui Qian; Ruiyang Xiao; Yang Cheng; Xiaojie Cui; Lingyi Chen (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Retraction notice to “Multifunctional chondroitin sulfate based hydrogels for promoting infected diabetic wounds healing by chemo-photothermal antibacterial and cytokine modulation” [Carbohydrate Polymers 314 (2023) 120937] - Yuan Zhang; Wenjuan Chen; Wenjing Feng; Wenhong Fang; Xiao Han; Cui Cheng (Carbohydrate Polymers, 2025)

Experimental investigation on local scour evolution around a circular monopile in the silty bed under wave-current combinations - Chunguang Yuan; Mingxiao Xie; Jinquan Wang; Xiaoliang Xia; Long Xiao; Na Zhang; Cheng Cui (Coastal Engineering, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The lactylation of glucose-6-phosphate dehydrogenase promotes malignant phenotypes in cancer cell lines - Yan Zhang; Ying Wu; Aoxing Cheng; Fengjuan Cui; Zhenye Yang; Jing Guo (Molecular Biology Reports, 2025)

Constructing a PANoptosis-based prognostic signature to evaluate the immune landscape and therapeutic response in clear cell renal cell carcinoma - Yu Dong; Zitong Yang; Zhinan Xia; Jiahao Liao; Zhiming Cui; Shenhao Xu; Bing Liu; Liangliang Ren; Tengda Wang; Wei Guo; Shuwen Wang; Yuyong Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Serum amyloid A: multifaceted roles in inflammation and cellular interactions - Shouzheng Cheng; Dingyu Duan; Hao Cui; Yingying Lian; Fan Jiang; Qianming Chen; Taiwen Li; Lei Zhao (Immunologic Research, 2025)

Genome-wide identification and expression analysis of PP2C gene families in two Chimonanthus species - Xin-Chen He; Jie-Xin Shao; Wei Zou; Shu-Xiao Zhang; Li Zhu; Meng-Cheng Ji; Cui-Hua Gu; Li-Yuan Yang (Genetica, 2025)

A combination strategy of HPLC and boric acid modified β-CD polymer for super-efficiently separating chiral substances with O/N atoms in chiral and/or adjacent carbons - Xiaoqian Yuan; Yuchen Cui; Yaqin Nan; Ruijun Tang; Xinru Wang; Yanmei Xu; Xinghua Jin; Yiwen Wang; Ding Cheng; Youxin Li (Analytica Chimica Acta, 2025)

Interactions of dietary sodium citrate and soybean meal on growth performance, immune response, and intestinal microbiota of shrimp Penaeus vannamei - Keke Lei; Xidie Zhao; Hailing Zheng; Pei Cui; Jinhui Sun; Zhenyan Cheng (Aquaculture International, 2025)

Population Genomics and Climate Change Vulnerability in Two Sympatric Desert Rodents - Tian Tian; Jilong Cheng; Yu Zhang; Lin Xia; Yilin Chen; Fangyuan Yang; Zhixin Wen; Yaqian Cui; Weibo Wang; Xueying Zhang; Yanhua Qu; Qisen Yang (Global Change Biology, 2025)
Climate change poses a severe threat to desert ecosystems; however, understanding how specialized desert species respond to changing climate remains limited. These species are confronting extreme changes, including intensified droughts, altered precipitation, and temperature patterns. Here, we integrate population and ecogenomic approaches to examine population genetic structure, demographic history, and climate adaptation in two distantly related, sympatric rodent species in arid and semi‐arid regions in East Asia. We further combine genomic offset analysis, ecological niche modeling, and landscape connectivity assessments to evaluate their climate change risks. Our results reveal that the two species have diverged into five geographically distinct lineages, each associated with a different arid region. Lineage divergence times are estimated between 20 and 400 thousand years ago, with population size declines occurring around the Last Glacial Maximum. While the two species exhibited distinct climate adaptation, evidenced by different key climatic variables and associated genes identified for each species, they exhibited congruent vulnerability to future climate change. This was indicated by parallel patterns of genomic offset and niche suitability loss. Under future climate change scenarios, eastern lineages in high precipitation seasonality areas (e.g., DB lineages in Horqin Sandy Land) face a higher risk due to substantial genomic offset, habitat loss, and reduced connectivity. In contrast, lineages on the west ranges with low precipitation seasonality (e.g., QH lineages in the Qaidam Basin and HL lineage in the Changtang Plateau) appear less vulnerable, characterized by lower genomic offset and the expansion of desert habitats. Overall, this study provides a comprehensive framework for identifying vulnerable populations and predicting responses to climate changes in desert species, offering critical insights for the conservation of desert ecosystems.

Hydrophilicity-dependent photodegradation of antibiotics in ice: Freeze-concentration effects and dissolved organic matter interactions drive divergent kinetics, pathways and toxicity - Jingshuang Cui; Yue Chen; Fangyuan Cheng; Hao Yang; Jiao Qu; Ya-nan Zhang; Willie J.G.M. Peijnenburg (Water Research, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Environmental and biological controls on ecosystem water use efficiency over paddy fields with different management practices in Southern China - Bo Liu; Yuanzhi Shi; Jun Wei; Rangjian Qiu; Bin Liao; Cheng Li; Xiaoping Chen; Yuanlai Cui (Journal of Hydrology, 2025)

Slightly acidic electrolyzed water induces Staphylococcus aureus to enter the VBNC state: differences between planktonic and biofilm states bacteria - Ziyi Zhang; Jingqi Feng; Haoran Cui; Yu Wu; Yihong Wang; Weipeng Xu; Yiming Lu; Menghua Duan; Hui Yang; Shuai Cheng; Xiaolin Cai; Chunling Zhang; et al. (Food Research International, 2025)

Ionic liquid functionalized magnetic microporous organic network for efficient extraction of phenoxyacetic acid herbicides from vegetables - Xu-Hui Li; Yan-Hong Li; Yuan-Yuan Cui; Cheng-Xiong Yang (Food Chemistry, 2025)

Insight into the transformation of phosphorus in soil affected by microplastics: A review - Xuchen Zhang; Shicheng Dong; Junxia Wang; Kiran Yasmin Khan; Zhanjun Cheng; Xiaoqiang Cui; Jipeng Luo; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Synthesis of LaAlO3 based high near-infrared reflective red pigment by substituting A-site and B-site elements in perovskite structure with Ca2+/Cr3+ - Qiuli Fang; Jingsheng Liu; Yi Wu; Kangzhen Sun; Pengzhai Li; Cheng Cai; Sheng Cui; Yin Zhang (Chemical Engineering Journal, 2025)

Evolution of phosphorus during co-pyrolysis of wheat straw and mulch film components - Chao Fan; Junxia Wang; Yuxin Yang; Jian Li; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Chemical Engineering Journal, 2025)

Experimental study of localized hydro-thermal-mechanical coupling characteristics of unsaturated silt under step-freezing conditions - Yu-zhi Zhang; Cheng-yan Li; Meng Wang; Yi-han Cui; You-cheng Sun (Cold Regions Science and Technology, 2025)

OsSPL10 negatively regulates seedling salt tolerance through OsJAZ-mediated jasmonate pathway in rice (Oryza sativa L.) - Jilin Chen; Tong Lan; Tongtong Dong; Qiaoling Liao; Xiaoxiao An; Chao Fang; Xiaoxia Yang; Xinle Cheng; Kai Fan; Xiaofang Xie; Haitao Cui; Weiren Wu; et al. (Theoretical and Applied Genetics, 2025)

Pinocembrin Alleviates Postoperative Cognitive Dysfunction in Aged Mice by Modulating miR-384-5p/FZD1 Axis to Activate the Wnt/β-Catenin Pathway - Jie Li; Xue-li Peng; Xin-yu Cheng; Jun-jun Yang; Cui Cui; Jian-hui Liu (Molecular Neurobiology, 2025)

Risk assessment of tunnel construction in complex geological environments based on improved game theory and multi-dimensional cloud model - Shijiang Pu; Xiaolong Yang; Shunchuan Wu; Haiyong Cheng; Tianbin Xiang; Jingqi Cui; Meili Hu (Bulletin of Engineering Geology and the Environment, 2025)

Au/UiO-67 nanocomposites as an electrochemical sensor for methylmercury: Ligand substituent effects on electrocatalytic properties - Yao Liu; Yue-Cheng Kang; Ting-Ting Hu; Kang-Ping Cui; Xing Chen (Analytica Chimica Acta, 2025)

Spermidine-mediated enhancement of salt tolerance in cucumber and the role of H2O2 in regulating this enhancement - Ting-Ting Xu; Cui-Yun Dong; Cai-Hong Chai; Qiao Zhu; Cheng Ma; Zi-Qi Pei; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

The internal and external reverse-reduction pathway involved in the degradation of free DNA bases during advanced oxidation processes - Shuangshuang Cheng; Rui Cui; Yuehong Sun; Yuxin Li; Yangjian Zhou; Zilong Song; Xin Yang (Water Research, 2025)

Removal and toxic intervention of polystyrene microplastics and nanoplastics by magnetic nano-Fe3O4 in spermatogonial GC-1 cells - Cheng Cheng; Yanfan Cui; Yujie Wang; Jingfeng Huang; Jiale Ma; Tao Luo; Wen Chen (Reproductive Toxicology, 2025)

Integrating experimental insights with machine learning for inverse design of sustainable lignin-derived Cr (VI) adsorbents - Huirong Zhang; Yi Shen; Jinglei Cui; Baofeng Wang; Yanxia Guo; Dongke Zhang; Fangqin Cheng (Process Safety and Environmental Protection, 2025)

Insights into Mn-N synergism in activated carbon-based catalysts for low-temperature NH3-SCR of NOx - Yuhang Li; Huirong Zhang; Xiaojun Xue; Qiang Ren; Jinglei Cui; Baofeng Wang; Yanxia Guo; Dongke Zhang; Fangqin Cheng (Journal of Environmental Chemical Engineering, 2025)

The investigation of phosphonate-decorated covalent organic frameworks with photo responsive effect for the effective adsorption and separation towards rare earth elements - Runhan Yan; Hongmin Cui; Jingsong Shi; Wei Jiang; Fei Gao; Nanfu Yan; Yaqing Weng; Minghui Li; Yuewei Liu; Ting Cheng (Journal of Environmental Chemical Engineering, 2025)

Manipulating internal catalytic microenvironment of dynamic Cu/SSZ-13 catalysts by in situ Ce incorporation for efficient NH3-SCR - Yan Wang; Tiantian Zhang; Xinya Wu; Yuanjiang Wang; Hao Qu; Cheng Zhang; Jianguo Cui; Cailing Xu; Zhaoqiang Li; Yongquan Qu; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2025)

Lipid profiles and microstructure of alpine Holstein milk: Comparison with common Holstein milk - Xinying Hu; Qingyun Wang; Shuai Wang; Xinyi Cheng; Ping Qin; Jingwei Cui; Li Wang; Wei Wei; Xingguo Wang (International Dairy Journal, 2025)

Exploring the effect of inoculation strategies with Saccharomyces cerevisiae and Lactobacillus paracasei SMN-LBK on chemical, flavor and metabolic profiles of prune wine - Jianqiao Jiang; Yun Xie; Miao Cui; Yiwen Chen; Yongkang Li; Yue Hu; Jianming Niu; Weidong Cheng; Feifei Gao (Food Research International, 2025)

Extraction of pigments from chestnut (Castanea mollissima) shells using green deep eutectic solvents: Optimization, HPLC-MS identification, stability, and antioxidant activities - Zhongxu Li; Caihong Cheng; Li Zhang; Jialin Xue; Qingyang Sun; Haoran Wang; Ruiguo Cui; Ruijie Liu; Lijun Song (Food Chemistry, 2025)

A customized immunomodulator reinforces the T cell-mediated immunological cascade for cancer therapy - Guowang Cheng; Jiaxin Wu; Wei Liu; Yumiao Yang; Hao Cui; Xiuxiu Dai; Bowen Li; Zhen Tian; Xiaojia Chen; Xiaohui Li; Zhenfeng Wu; Guochao Liao; et al. (Chemical Engineering Journal, 2025)

Synthesis of novel estradiol bisselenocyanate with unique 2-selenocyano-17-selenocyanoesteryl structure and evaluation of antitumor activity - Tao Gan; Yang Cheng; Wenhao Tian; Zhiping Liu; Chunfang Gan; Yanmin Huang; Chunrui Cai; Jianguo Cui (Molecular Diversity, 2025)

Study on the change of multi-season urban heat island effect from the perspective of urban functional zones - T. Su; X. S. Dou; X. Y. Cui; D. Liu; B. Lei; M. N. Yuan; R. J. Chen; X. Cheng (International Journal of Environmental Science and Technology, 2025)

Inhibition by dissolved organic matter of the degradation of purine compounds by the sulfate radical - Shuangshuang Cheng; Rui Cui; Jinpeng Yu; Yujie Zhao; Xin Yang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Arbuscular mycorrhizal fungi mediate rare taxa and network complexity in rhizospheric and endophytic bacterial communities of Allium schoenoprasum L - Yiming Zhang; Ye Cui; Qixiu Cheng; Zishan Li; Yiming Dai; Keqing Lin; Xiaoyu Li; Jin Chen (Rhizosphere, 2025)

Genome-wide identification of aldehyde dhydrogenase (ALDH) family genes in pepper (Capsicum annuum) reveals involvement of CaALDH7B1 in heat and drought stress tolerance - Bo Yang; Yifen Shang; Lang Wen; Yijia Cui; Zixing Li; Yuan Cheng; Chaochao Liu (Plant Gene, 2025)

Different Arbuscular mycorrhizal fungi species alter rhizospheric and endophytic bacterial diversity, network stability and function of Allium schoenoprasum L - Jin Chen; Qixiu Cheng; Yiming Zhang; Ye Cui; Yiming Dai; Keqing Lin; Zishan Li; Boyan Wang; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Real-time tracking and early diagnosis of mercury(II) exposure via a novel NIR-based fluorescent probe based on thiahemicyanine dye - Fuyang Liu; Jianwei Cui; Haoyue Hu; Senmiao Ren; Hulan Chen; Yun Deng; Zhen Huang; Cheng Peng; Wim Dehaen; Jun Lu; Yuyu Fang (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

A novel molecularly imprinted sensors using chitosan on nitrogen-doped hollow carbon nanospheres for bisphenol A detection - Lirong Ma; Yincang Cui; Zhigang Wang; Qian Cheng; Yanqiang Zhou; Guoliang Zhang; Luyao Wang; Yiwu Zhu; Feng Xu; Tursun Abdiryim (Journal of Hazardous Materials, 2025)

Dopamine-modified hydrated silica immobilized Flavourzyme for efficient bioactive peptide release from β-lactoglobulin - Xu Zhao; Yuqin Cheng; Jucai Xu; Chun Cui (Food Chemistry, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Training of mesenchymal stem cells by using hydrogel microspheres for the repair of intervertebral disc degeneration - Mingzheng Chang; Xiaohui Zhang; Xiaoxiong Wang; Qingliang Ma; Shangye Li; Cheng Qiu; Shuo Wang; Suomao Yuan; Yonghao Tian; Yunhao You; Dapeng Zhang; Jiwei Cui; et al. (Chemical Engineering Journal, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

G-protein coupled receptor 183 (GPR183) inhibits visceral metastasis of non-small cell lung cancer - Lei Cheng; Shifang Li; Zhenwen Cui; Xuezhi Sun; Mengqi Gong; Yun Chen; Li Meng; Yiwei Liao (Clinical & Experimental Metastasis, 2025)

Cooperative nuclear import of duck plague virus DNA polymerase subunits: pUL42 NLS Enhances pUL30 nuclear import and viral replication, with VP22 as a compensatory factor - Yuxi Cui; Mingshu Wang; Anchun Cheng; Qiao Yang; Xumin Ou; Di Sun; Yu He; Xinxin Zhao; Ying Wu; Shaqiu Zhang; Bin Tian; Juan Huang; et al. (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Research on crystallization and separation of electrolytic aluminum slag leaching solution based on the phase diagram of AlCl3-CaCl2-H2O(-HCl) system - Wenxuan Guo; Huaigang Cheng; Liping Sun; Jing Zhao; Li Cui (Desalination, 2025)

Advancements in the investigation of the mechanisms underlying cognitive aging - Honglu Zou; Shuo Zhang; Xinxin Cui; Hongyan Xu; Zhangying Zhou; Danmeng Cheng; Yanan Han; Youcai Tang; Anqin Dong; Xianwen Dong (Biogerontology, 2025)

Electric vehicle range prediction considering real-time driving factors and battery capacity index - Xinwei Ma; Jiaao Li; Hongjun Cui; Long Cheng; Yanjie Ji; Jianbiao Wang (Transportation Research Part D: Transport and Environment, 2025)

A potent fluorescent probe for HOCl with dual NIR emissions: Achieving the early diagnosis of polystyrene microplastics-induced liver injury involved in ferroptosis - Jianwei Cui; Jiaji Teng; Peini Xiang; Fuyang Liu; Zhixing Cao; Jun Lu; Yun Deng; Yuzhi Li; Cheng Peng; Wim Dehaen; Yuyu Fang (Journal of Hazardous Materials, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

Characterization of differences in physicochemical properties, volatile organic compounds, and vitro digestion properties of turnips by inoculation of lactic acid bacteria - Miao Cui; Yun Xie; Junbo Zhang; Jie Feng; Yiwen Chen; Yongkang Li; Yue Hu; Jianming Niu; Weidong Cheng; Feifei Gao (Food Bioscience, 2025)

Gelatin bloom values affects the starch molecular structure changes and digestibility of resulting wheat starch/gelatin complexes - Yue Cheng; Yifan Chen; Wei Gao; Xuemin Kang; Bo Cui (Food Hydrocolloids, 2025)

Biomimetic photosynthesis nanoreactors based thylakoid synergy with metformin for reversing tumor immunosuppressive microenvironment therapy - Peiliang Zhong; Yuyue Zhao; Hao Cui; Guowang Cheng; Linze Xia; Zhen Tian; Wei Liu; Jiaxin Wu; Jiaxian Yu; Xinyi Peng; Guangtao Yu; Dandan Ma (Chemical Engineering Journal, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

A Pipeline Leakage Detection Technique Using Ground Penetrating Radar Polarization Method - Ran Wang; Fan Cui; Guoqi Dong; Xiaoxue Zhao; Qi Cheng; Guixin Zhang; Mengli Zhang (Water Resources Management, 2025)

Pilot Exploration of RGMa-BMP4 Signaling in Neutrophil Activation in NMOSD: Integrating Clinical and Molecular Insights - Weihe Zhang; Lei Cui; Yeqiong Zhang; Yang He; Xiaoxuan Li; Yu Wang; Jinsong Jiao; Dantao Peng; Ming Jin; Cheng Xiao (Molecular Neurobiology, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Structural response analysis of different submerged floating tunnel route selection conditions in the complex strait under the action of typhoon Sepat - Cheng Cui; Bo Huang; Minglin Chen; Wenlong Luo; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Boosted chlorate hydrogenation reduction via continuous atomic hydrogen - Yilin Lu; Xiangdong Zhu; Aodi Li; Cheng Cheng; Beibei Xiao; Peixin Cui; Yujun Wang; Dongmei Zhou (Journal of Hazardous Materials, 2025)

Enhanced metal – support interaction through activated carbon structure optimization: New insights into enhanced NH3-SCR performance of Fe-Mn/AC catalysts - Huirong Zhang; Yuhang Li; Jian Niu; Xiaojun Xue; Qiang Ren; Jinglei Cui; Baofeng Wang; Yanxia Guo; Dongke Zhang; Fangqin Cheng (Journal of Environmental Chemical Engineering, 2025)

Numerical study on the effects of the mechanical degradation of UHPC layer and stud connectors on the fatigue performance of steel-UHPC composite bridge decks - Lingcong Miao; Zhenyu Cheng; Jialing Song; Qinghua Zhang; Chuang Cui; Jun Li (Engineering Structures, 2025)

Electronic structure regulation of Fe3C neighbored Fe-N4 ensembles enables optimized redox-cascade electrocatalysis for high-performance lithium-sulfur batteries - Zhiqiang Zhou; Lekang Cui; Lubin Yang; Cheng Ma; Yongzheng Zhang; Wenming Qiao; Jitong Wang; Yayun Zhang; Licheng Ling (Chemical Engineering Journal, 2025)

Triphenylphosphine directly knitted porous coordinating hyper crosslinked poly(ionic liquid)s for efficient CO2 fixation into cyclic carbonates - Mengqian Fu; Tianyu Guo; Shuaifei Liu; Wen Liu; Yong Li; Cui Qiao; Yunong Li; Zifeng Yang; Wei Hua; Qian Su; Weiguo Cheng; Suojiang Zhang (Chemical Engineering Journal, 2025)

Development of Brassica rapa-nigra monosomic alien addition lines: cytology, genetics, and morphology - Pengfei Li; Haiyan Wu; Shizhen Guo; Shunlin Wang; Mimi Zhang; Mengyang Liu; Wei Ma; Jianjun Zhao; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

3D rockfall trajectories analysis considering earthquake-induced initial velocities: a case study in Nujiang Bridge area, China - Tao Jiang; Yufeng Wei; Shenghua Cui; Jianjun Zhao; Mengjie Yang; Wenqi Cheng; Decai Kong; Jianxin Song (Landslides, 2025)

An often-overlooked health issue: The potential adverse effects of microplastics on the human ocular health - Yabo Bao; Xianlei Fang; Yiping Cheng; Daolei Cui; Hai Liu; Ping Xiang (Critical Reviews in Environmental Science and Technology, 2025)

A sudden drop in temperature causes an imbalance in skin mucus barrier homeostasis in grass carp (Ctenopharyngodon idella) - Yali Wang; Xiaoning Gao; Zihao Cheng; Rong Chen; Yangyang Zhang; Subin Cui; Siyu Zhang; Kun Hu; Congdi Wu (Aquaculture, 2025)

Nonlinear wind wave model under effects of wind and dissipation: Establishment and validation - Wenhao Cheng; Zeng Liu; Jifeng Cui; Jianglong Sun (Wave Motion, 2025)

Multi-scale study of the synergy between human activities and climate change on urban heat islands in China - Kui Yang; Jinting Zhang; Dongge Cui; Yanni Ma; Yaochu Ye; Xiaoman He; Zenan Yang; Miaomiao Cheng; Yaoxuan Zhang (Sustainable Cities and Society, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Optimizing vessel trajectories: Advanced denoising and interpolation techniques for AIS data - Yiheng Chen; Yanming Chen; Yue Cui; Xinyu Cai; Changgui Yin; Yongxin Cheng (Ocean Engineering, 2025)

Advancing insights into structural response phenomena in semi-submersible floating wind turbine hulls through model testing - Yueyuan Ma; Zhengshun Cheng; Shuaishuai Wang; Wenhua Zhao; Minghao Cui; Peng Chen (Ocean Engineering, 2025)

E se tea aqueous-ethanol extract ameliorates D-galactose induced oxidative stress and inflammation via the Nrf2 signal pathway - Guiguang Cheng; Meng Zhang; Jinke Zhang; Sifan Teng; Zhengxuan Wang; Tianqi Cui; Shanshan Xiao (Food Research International, 2025)

Tyrosinase inhibition and enzyme kinetics of red rice bran protein peptides: Mechanism, identification, in silico exploration, and experimental validation - Zhenhao Zhao; Junbo Hu; Huimin Cui; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Bioscience, 2025)

Unveiling the mechanism of Gelatin's influence on starch digestibility: A focus on amylopectin chain distribution - Yifan Chen; Yue Cheng; Wei Gao; Xuemin Kang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2025)

Metal coordination-based double-network microsphere scaffolds facilitate bone regeneration via oxygen-driven mitochondrial oxidative phosphorylation - Chao Lin; Jialei He; Jiachen Li; Qingsong Zou; Lina Huang; Nuo Chen; Xiaojian Ye; Xiaoxiao Li; Wenguo Cui; Qian Cheng (Chemical Engineering Journal, 2025)

High near-infrared reflection characteristics and energy-saving applications of Bi-doped LaAlO3 perovskite yellow pigment - Cheng Cai; Yi Wu; Kangzhen Sun; Qiuli Fang; Pengzhai Li; Sheng Cui; Yin Zhang (Chemical Engineering Journal, 2025)

Ultrafast self-gelling, superabsorbent, and adhesive chitosan-based hemostatic powders for rapid hemostasis and wound healing - Ashuang Liu; Shengyong Cui; Lei Song; Xiangshu Guo; Zhimao Huang; Shancan Wang; Kai Cheng; Ying Xiao; Youfen Fan; Rong Wang (Carbohydrate Polymers, 2025)

Integrated learning framework for enhanced specific surface area, pore size, and pore volume prediction of biochar - Chao Chen; Yongjie Hu; Yadong Ge; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Xiaoqiang Cui; Guanyi Chen (Bioresource Technology, 2025)

Efficient generation of all ESC-derived mice carrying a homozygous lethal mutation through eight-cell embryo injection - Xidi Yin; Meng Yan; Yanbo Cheng; Zhoujie Li; Chong Cui; Yingyi Wang; Nan Liu; Yilai Shu; Jinsong Li; Qing Li (Science China Life Sciences, 2025)

Research Progress of Fuel Cell Technology in Marine Applications: A Review - Zheng Zhang; Xiangxiang Zheng; Daan Cui; Min Yang; Mojie Cheng; Yulong Ji (Journal of Marine Science and Engineering, 2025)
With the increasing severity of global environmental issues and the pressure from the strict pollutant emission regulations proposed by the International Maritime Organization (IMO), the shipping industry is seeking new types of marine power systems that can replace traditional propulsion systems. Marine fuel cells, as an emerging energy technology, only emit water vapor or a small amount of carbon dioxide during operation, and have received widespread attention in recent years. However, research on their application in the shipping industry is relatively limited. Therefore, this paper collects relevant reports and literature on the use of fuel cells on ships over the past few decades, and conducts a thorough study of typical fuel cell-powered vessels. It summarizes and proposes current design schemes and optimization measures for marine fuel cell power systems, providing directions for further improving battery performance, reducing carbon emissions, and minimizing environmental pollution. Additionally, this paper compares and analyzes marine fuel cells with those used in automotive, aviation, and locomotive applications, offering insights and guidance for the development of marine fuel cells. Although hydrogen fuel cell technology has made significant progress in recent years, issues still exist regarding hydrogen production, storage, and related safety and standardization concerns. In terms of comprehensive performance and economics, it still cannot effectively compete with traditional internal combustion engines. However, with the continued rapid development of fuel cell technology, marine fuel cells are expected to become a key driver for promoting green shipping and achieving carbon neutrality goals.

Observed CO2 concentration reveals steep decrease of anthropogenic emissions in winters of 2021 and 2022 in Hangzhou and Yangtze River Delta region, China - Cheng Hu; Huili Liu; Yifan Zhang; Yu Cui; Fan Sun; Xuejing Shi; Junqing Zhang; Yanrong Yang; Leying Zhang; Bing Qi; Qitao Xiao; Ning Hu; et al. (Science of The Total Environment, 2025)

An improved frequency-domain approach for integrated analysis of three-column semi-submersible floating wind turbines - Changen Li; Peng Chen; Shi Deng; Zhengshun Cheng; Shuaishuai Wang; Minghao Cui; Gareth Erfort (Ocean Engineering, 2025)

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Nonlinear feedback of Asian summer monsoon to abrupt events in North Atlantic: Evidence from a precisely dated speleothem record during late MIS3 - Xi Chen; Jingyao Zhao; Kexin Wang; Xiyu Dong; Jiahui Cui; Liangkang Pan; Carlos Pérez-Mejías; Hai Cheng (Global and Planetary Change, 2025)

Exploring the mechanisms of enhanced activated carbon’s toluene adsorption and regeneration by utilizing inherent pyrite in coal - Huirong Zhang; Lijun Zhu; Zihe Pan; Jinglei Cui; Baofeng Wang; Dongke Zhang; Yanxia Guo; Fangqin Cheng (Fuel, 2025)

Eco-friendly synthesis of Arabinoxylan-Catechin conjugates: Enhanced functional and antioxidant properties via cold plasma and ultrasonic methods - Dima Atehli; Zhiyuan Xu; Xiaoyu Guo; Meng Xiao; Boyu Cheng; Xing Jia; Bo Wu; Ji Kang; Qingbin Guo; Steve W. Cui (Food Chemistry, 2025)

Electrochemical extraction technologies of lithium: Development and challenges - Hefeng Yuan; Muzi Li; Li Cui; Lijuan Wang; Fangqin Cheng (Desalination, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

Open-shell polymers reaching high photocatalysis and photothermal effect - Li Tian; Jiameng Zhang; Mengya Shang; Shukui Guo; Gongshu Wang; Zhenzhen Guo; Cheng-Xing Cui; Jun Jiang (Chemical Engineering Journal, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Implications for Unveiling Caledonian Tin Mineralization in the Jiumao Sn Polymetallic Deposit, Northern Guangxi Province - Youyue Lu; Jingya Cao; Shunbo Cheng; Bang An; Jianming Fu; Xiaoyong Yang; Zhicai Li; Liyan Ma; Sen Cui (Journal of Earth Science, 2025)

Fabrication of microporous organic network incorporated monolithic column for improved high performance liquid chromatographic separation of small molecules - Ting Wang; Yuan-Yuan Cui; Cheng-Xiong Yang (Analytica Chimica Acta, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Food-driven transformation of nitrogen fluxes with urbanization in China - Ouping Deng; Jiale Wei; Jinglan Cui; Shuai Huang; Luxi Cheng; Rong Huang; Baojing Gu (Resources, Conservation and Recycling, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

A new method for quantitative characterization of dynamic migration behavior of NaCl in beef during marinating - Yingjie Feng; Fujia Dong; Cheng Wu; Jiarui Cui; Guangxian Wang; Zhongxiong Zhang; Songmin Cao; Sijia Liu; Hui Li; Yingkun Shi; Jianguo Yu; Songlei Wang (Food Research International, 2025)

Nonlinear flutter critical state prediction for a bridge girder based on instantaneous power balance principle - Yue Cheng; Genshen Fang; Wei Cui; Yongle Li; Lin Zhao (Engineering Structures, 2025)

Travel intensity of private electric vehicles and implications for GHG emission reduction in China - Wenbo Li; Mengzhe Wang; Xiu Cheng; Ke Cui; Qianwen Li; Shengwu Chen (Environmental Impact Assessment Review, 2025)

Unity of terrestrial and extraterrestrial soils in granular configuration - Jun Zhang; Yong Li; Yifei Cui; Zi Wu; Yuan Xue; Jianyi Cheng; Hu Jiang; Yao Li; Jian Guo; Jiayan Nie; Guodong Wang; Ao Luo (Earth and Planetary Science Letters, 2025)

Study on rock-breaking mechanism of impact trenching in underground diaphragm wall with consideration of slurry effects - Ri-cheng Miao; Zi-han Gu; Cao Wang; Wei Cui (Computers and Geotechnics, 2025)

Corrigendum to “A spatiotemporal probiotic spore-loaded oxygen generator resumes gut microbiome balance and improves hypoxia for treating viral pneumonia” [Chem. Eng. J. 505 (2025) 159706] - Qikun Cheng; Mingzhi Xie; Hangjie Ying; Cuiyuan Jin; Lijun Yang; Dong Ma; Shumao Cui; Liyun Shi (Chemical Engineering Journal, 2025)

Optimized dense fibril network by ternary strategy to improve charge transport and realize efficient organic solar cells - Chuanlong Cui; Cheng Sun; Yuyi Bi; Shuyu Yao; Yuchang Zhao; Jianxiao Wang; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2025)

Simultaneous nitrogen removal and phosphorus recovery in granular sludge-based partial denitrification/anammox-hydroxyapatite precipitation (PD/A-HAP) process under low C/N ratio and dissolved oxygen limitation - Lijie Chen; Zhenjun Wu; Jiayu Niu; Yihan Wang; Ming Cai; Jiale Xi; Yanlei Cui; Lang Cheng; Xinyi Fan (Bioresource Technology, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Prediction of Coal Burst Location and Risk Level in Roadway Using XGBoost with Multi-element Microseismic Information and Its Application in Steeply Inclined Ultra-Thick Coal Seam - Feng Cui; Cheng Zong; Xinglai Lai; Chong Jia; Zhong Luo (Rock Mechanics and Rock Engineering, 2025)

Saccharomyces cerevisiae fermentation of high molecular weight hyaluronic acid enhanced the antioxidant capacity in skin fibroblasts - Meng Zhang; Doudou Shi; Mimi Cui; Jinyong Li; Wenjing Cheng; Chunhong Pu; Jiachan Zhang; Changtao Wang (Archives of Microbiology, 2025)

Neuregulin 1 improved gastric motility and reduced gastric inflammation by activating the α7nAChR through the cholinergic anti-inflammatory pathway in diabetic rats - Weigang Cui; Yuqi Ma; Libin Zhang; Lei Zhang; Qianyin Yao; Jie Zhang; Yatao Cheng; Wenqin Zeng; Qin Liu; Fengyun Liu; Chunyan Liang (Toxicology and Applied Pharmacology, 2025)

Benzene-induced hematotoxicity enhances the self-renewal ability of HSPCs in Mll-Af9 mice - Jin Zhou; Pinpin Sui; Jianxin Zhao; Xiurong Cheng; Tao Yu; Shiwei Cui; Xiangrong Song; Caihong Xing (Toxicology, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial-temporal quantification of Yangtze River traffic flow using AIS data - Yue Cui; Yanming Chen; Yiheng Chen; Xinyu Cai; Changgui Yin; Yongxin Cheng (Ocean Engineering, 2025)

Early-Middle Holocene climate change and its impact on the succession of Neolithic cultures in southern Hangzhou Bay - Jing Lu; Haiwei Zhang; Rui Zhang; Jiahui Cui; Yanyan Bao; Xiaowen Niu; Yanjun Cai; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

Cascading effect modelling of integrating geographic factors in interdependent systems - Yong Ge; Mo Zhang; Rongtian Zhao; Die Zhang; Zhiyi Zhang; Daoping Wang; Qiuming Cheng; Yuxue Cui; Jian Liu (Environmental Modelling & Software, 2025)

Study on the rational construction methods and mechanical properties of composite beams in transverse negative bending moment zones - Jiawei Liu; Qinghua Zhang; Zhenyu Cheng; Chuang Cui; Kun Tang (Engineering Structures, 2025)

A spatiotemporal probiotic spore-loaded oxygen generator Resumes gut microbiome balance and Improves hypoxia for treating viral pneumonia - Qikun Cheng; Mingzhi Xie; Hangjie Ying; Cuiyuan Jin; Lijun Yang; Dong Ma; Shumao Cui; Liyun Shi (Chemical Engineering Journal, 2025)

Highly efficient CO2 capture from open air and dilute gas streams by tunable azolate ionic liquids based deep eutectic solvents - Guokai Cui; Yepin Cheng; Wei Zhang; Xiangyu Shen; Lai Li; Ruina Zhang; Yaoji Chen; Quanli Ke; Chunliang Ge; Huayan Liu; Wenyang Fan; Hanfeng Lu (Chemical Engineering Journal, 2025)

Detection and molecular epidemiology of canine parvovirus and identification of highly pathogenic CPV-2c isolates from Shandong, China - Jiahui Li; Baoyu Cheng; Zihe Li; Yanlei Cui; Haiyan Yang; Weiquan Liu; Chuanmei Zhang; Yongle Yu (Virus Genes, 2025)

Application Prospects and Challenges of VHF Data Exchange System (VDES) in Smart Fisheries - Zuli Wu; Minsi Xiong; Tianfei Cheng; Yang Dai; Shengmao Zhang; Wei Fan; Xuesen Cui (Journal of Marine Science and Engineering, 2025)
Smart fisheries are an important way to promote the sustainable development of fisheries, and efficient and reliable marine communication systems are the key to realizing smart fisheries. As an emerging marine communication technology, the VHF Data Exchange System (VDES) has the advantages of a high data transmission rate, large communication capacity, and wide coverage, providing new opportunities for the transformation and upgrading of smart fisheries. This paper introduces the technical architecture and functions of the VDES, compares it with existing marine communication technologies, analyzes the key requirements of a smart fishery, and assesses how the VDES meets these requirements. The potential application scenarios of the VDES in smart fishery fields such as fishing vessel monitoring, fishery resource management, and maritime security are discussed. The challenges faced by the VDES in the application of smart fisheries, such as technology, policies and regulations, and construction cost layout, are analyzed, and its future development trend is prospected. Suggestions such as its integration with emerging technologies, the realization of global seamless coverage, and the strengthening of international cooperation and data sharing are proposed. This paper aims to provide theoretical guidance and scientific reference for the promotion and application of the VDES in smart fisheries.

Integrated transcriptomic and epigenomic analyses to disclose the transcriptional regulatory mechanisms of lipid and energy metabolism under cold stress in grass carp - Songqian Huang; Chenyu Yan; Yuan Xu; He Jiao; Minghao Zhang; Jiangbo Cheng; Wenting Wang; Zongbin Cui; Liangbiao Chen; Peng Hu; Qianghua Xu (Aquaculture, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

A novel framework for fatigue hotspot localization and damage assessment of multi-defect marine structures under random vibration - Dengkai Cui; Ruili Xie; Ming Li; Wei Cheng (Ocean Engineering, 2025)

Binding mechanisms and phosphorus adsorption performance of soil mineral-BDOM complexes - Jinlong Yan; Xiangqian Zhou; Wei Zhang; Fengli Cheng; Hui Wang; Liqiang Cui; Guixiang Quan (Journal of Water Process Engineering, 2025)

Effects of ecological restoration on microbial-mediated ammonia removal in polluted rivers: Microcosm experiment and physical modelling - Zhen Cui; Cheng Chen; Qiuwen Chen; Mengnan He; Wenting Fan (Journal of Cleaner Production, 2025)

Simulation study on the effect of temperature on hydrogen production performance of alkaline electrolytic water - Xiaobing Bi; Gan Wang; Daan Cui; Xinyi Qu; Shuaishuai Shi; Dong Yu; Mojie Cheng; Yulong Ji (Fuel, 2025)

Effect of active site size in dispersed MoS2 nanocatalysts on slurry-phase hydrocracking of residue - Hui Luo; Cheng Ding; Siqi Yin; Wenan Deng; Chuan Li; Wenlong Cui; Feng Du (Fuel, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Generation of unpaired electrons to promote electron transfer at the cathode of room-temperature sodium sulfur batteries - Chen Huang; Jing Yu; Yao-Jie Lei; Oleg Usoltsev; Li Gong; Zhibiao Cui; Junshan Li; Canhuang Li; Bingfei Nan; Xuan Lu; Ren He; Xuede Qi; et al. (Chemical Engineering Journal, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Superior broadband sound absorption in hydrophobicity and mechanical enhancing Poly(urethane-imide)/Melamine aerogels via ambient drying - Enyuan Hu; Yingwen Zhu; Haiyun Li; Cheng Deng; Bo Cui; Lei Zhao; Jinhui Wu; Xinmiao Wang; Mengfu Zhu (Chemical Engineering Journal, 2025)

A logistic-Lasso-regression-based seismic fragility analysis method for electrical equipment considering structural and seismic parameter uncertainty - Jiawei Cui; Ailan Che; Sheng Li; Yongfeng Cheng (Earthquake Engineering and Engineering Vibration, 2025)

A simply synthesized, silver ions-doped porous gold microparticles-based SERS aptamer sensor for ultrasensitive and broad-range quantitative detection of IL-6 - Bixia Liang; Zhixi Huang; Lingyan Cheng; Jin Quan; Zongxia Mou; Nan Li; Xin Cui (Analytica Chimica Acta, 2025)

Epigenetic Resources: Gaps in Aquatic Animal Germplasm Research - Fangcheng Li; Junfang Zhang; Xiangbing Cheng; Xinyao Cui; Jiamin Sun; Qigen Liu (Reviews in Aquaculture, 2025)
Aquatic animal germplasm research plays a vital role in biodiversity conservation and sustainable aquaculture. The traditional view is that diversity of germplasm resources is commonly attributed to genetic variation. However, recent studies in transgenerational epigenetics have shown that epigenetic information can also be passed down to offspring, which is consistent with the definition of germplasm. Therefore, it is necessary to define epigenetic information, such as DNA methylation, histone modifications, and ncRNAs, which can be passed down through generations, as epigenetic resources and incorporate them into the concept of germplasm. Germplasm resources should include not only genetic resources but also epigenetic resources. Epigenetic variation can arise from genetic, environmental, or stochastic factors. Genetic and epigenetic variation co‐determine phenotypic traits. It has been demonstrated that epigenetic information can be inherited across generations in aquatic animals. DNA methylation, histone modification, and ncRNAs are involved in addressing environmental challenges, maintaining genetic diversity, improving breeding strategies, combating inbreeding decline, and age determination. Therefore, future research on epigenetic resources is important for germplasm conservation, development, and utilization. This review proposes a new theoretical framework to elucidate the place of epigenetic resources in germplasm research and collects articles from the past 8 years that explore the inheritance of epigenetic information in aquatic animals. Integrating epigenetic research into germplasm studies enhances our understanding of population dynamics, adaptation, and evolutionary processes, thereby informing conservation strategies and enhancing aquaculture practices. By considering both genetic and epigenetic resources, we can address the challenges facing germplasm diversity and sustainable aquaculture more comprehensively.

Determining the geographical origins of goji berries using the Twin-Tower model for Multi-Feature - Jiarui Cui; Cheng Wu; Shibo Pan; Kenken Li; Sijia Liu; Yu Lv; Songlei Wang; Ruiming Luo (Computers and Electronics in Agriculture, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Unraveling the promotive mechanism of nitrogen-doped porous carbon from wasted lignin for Cr (VI) removal - Huirong Zhang; Yi Shen; Xiaokai Shi; Jinlei Cui; Baofeng Wang; Yanxia Guo; Dongke Zhang; Fangqin Cheng (Science of The Total Environment, 2024)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

Middle to late Miocene cooling and drying in the northern Tibetan Plateau based on evidence from plant-insect interactions - Cui Wang; Yusheng (Chris) Liu; Natalia Maslova; Hui Jia; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Spatio-temporal evolution of the Paleo-Tethys in western Yunnan: Insights from mafic rocks in the Lancang tectonic belt - Ya Cui; Yuejun Wang; Renjie Zhou; Yang Wang; Teresa Ubide; Xin Qian; Cheng Wang; Xin Wang (Lithos, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Fluxapyroxad induced toxicity of earthworms: Insights from multi-level experiments and molecular simulation studies - Lanlan Zhang; Yao Liu; Ying Xu; Mengyuan Pei; Mengyao Yao; Xiaoni Chen; Yifei Cui; Fengyang Han; Yubo Lu; Cheng Zhang; Yanhua Wang; Peng Gao; et al. (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Comprehensive review of plant-derived anti-hyperlipidemia peptides: Production, anti-hyperlipidemia mechanism, and structure-activity relationship study - Liuyi Wei; Hao Wu; Xufeng Wang; Li Wen; Bo Cui; Yunhui Cheng (Food Chemistry, 2024)

Fabrication of fluorinated magnetic microporous organic network for selective and efficient extraction of benzoylurea insecticides in tea beverages - Hui-Ping Yu; Qian-Qian Xu; Xin Wang; Yuan-Yuan Cui; He-Fang Wang; Cheng-Xiong Yang (Food Chemistry, 2024)

Comparative evaluating laser ionization and iKnife coupled with rapid evaporative ionization mass spectrometry and machine learning for geographical authentication of Larimichthys crocea - Weibo Lu; Honghai Wang; Lijun Ge; Siwei Wang; Xixi Zeng; Zhujun Mao; Pingya Wang; Jingjing Liang; Jing Xue; Yiwei Cui; Qiaoling Zhao; Keyun Cheng; et al. (Food Chemistry, 2024)

Preparation and characterization of Chitosan based edible coating containing vanillin/HPβCD inclusion complex and its application in chicken preservation - Chen Peiyao; Hua Shuhao; Liu Yinxin; Li Cheng; Zhang Xinyi; Lu Xingmeng; Sun Cui; Sun Chongde; Lingxia Huang (Food Control, 2024)

Protective immune-response of Aeromonas hydrophila phage lysate in crucian carp against direct virulent challenge with A. hydrophila-TPS - Ruiqi Liang; Ziyin Cui; Sayed Haidar Abbas Raza; Tingxuan Li; Zhe Zhang; Qixing Huang; Huifang Bai; Yan Cheng; Bingmei Du; Jinhong Li; Wenbin Zhu; Xiaochen Ren; et al. (Fish & Shellfish Immunology, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Engineering of calcium overload for state-of-the-art tumor therapy - Xinping Liu; Hui Hu; Jinjin Chen; Yi Li; Yaming Cheng; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2024)

Application of an α-galactosidase from Bacteroides fragilis on structural analysis of raffinose family oligosaccharides - Heyang Zu; Xuecui Yan; Jing Wu; Jingying Zhao; Kevin H. Mayo; Yifa Zhou; Liangnan Cui; Hairong Cheng; Lin Sun (Carbohydrate Polymers, 2024)

Light-driven biodegradation of chloramphenicol by photosensitized Shewanella oneidensis MR-1 - Yongqi Wang; Haibing Dai; Meitong Jin; Jueyu Wang; Ziheng Song; Yingjie Liu; Wenqi Chai; Lu Cheng; Na Zhao; Daizong Cui; Min Zhao (Bioresource Technology, 2024)

Cytological mapping of a powdery mildew resistance locus PmRc1 based on wheat-Roegneria ciliaris structural rearrangement library - Menghao Cheng; Huajian Zhang; Yao Zhang; Xiong Tang; Zongkuan Wang; Xu Zhang; Xinying Song; Xingyue Li; Huimin Cui; Tong Wang; Rongrong Song; Jin Xiao; et al. (Theoretical and Applied Genetics, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

“Click” post-synthesis of chiral microporous organic network for chiral high-performance liquid chromatographic separation - Han Li; Ke Li; Yuan-Yuan Cui; Cheng-Xiong Yang (Analytica Chimica Acta, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

What influences intermodal Choices: Metro-Centric, Bus-Centric, Hybrid? insights from Machine learning Approaches - Xinwei Ma; Xiaolin Tian; Hongjun Cui; Mingjia He; Jianbiao Wang; Long Cheng (Transportation Research Part D: Transport and Environment, 2024)

Effects of microwave treatment on vegetable oil quality & biological activities - Fuchun Chen; Ben Xu; Wenyu Cui; Yunfu Wang; Fachun Wan; Anwei Cheng (Trends in Food Science & Technology, 2024)

Exploring the association between multi-mode transport and the built environment: A comparative study of metro, bus, taxi, and shared bike use - Zhitao Li; Jinjun Tang; Wenkang Zhang; Yifeng Ji; Lida Cui; Cheng Hu; Chuyun Zhao (Sustainable Cities and Society, 2024)

Deteriorating wintertime habitat conditions for waterfowls in Caizi Lake, China: Drivers and adaptive measures - Xiudi Zhu; Bo Cheng; Hongqing Li; Lizhi Zhou; Fengling Yan; Xiaoyuan Wang; Qiang Zhang; Vijay P. Singh; Lijuan Cui; Bo Jiang (Science of The Total Environment, 2024)

Long-term trend forecast of chlorophyll-a concentration over eutrophic lakes based on time series decomposition and deep learning algorithm - Cheng Chen; Mingtao Hu; Qiuwen Chen; Jianyun Zhang; Tao Feng; Zhen Cui (Science of The Total Environment, 2024)

Effective adsorption performance and mechanism of methylene blue from dye wastewater by humic acid sucrose-modified red mud - Wei Fang; Yue Zhou; Mingqian Cheng; Jinzhong Yang; Qifei Huang; Zechun Huang; Yuting Cui; Liping Zhang; Yushu Wang; Qihong Cen; Zewei Liu; Bin Li (Process Safety and Environmental Protection, 2024)

Dynamic mechanical properties and microstructure of ultrafine slag powder cement paste utilizing solid waste industrial tailings powder and fly ash - Hang Zou; Shitang Cui; Kai Zhao; Jingsong Cheng; Zhijun Zheng; Shengjun Li; Yongliang Zhang (Process Safety and Environmental Protection, 2024)

Research on ultimate strength of hull girder considering initial imperfections under monotonic/cyclic bending moments - A bulk carrier case - Huwei Cui; Runwen Hu; Zemin Chen; Cheng Zheng (Ocean Engineering, 2024)

Multicentennial-scale coupling of the East Asian monsoon to North Atlantic climates during the Last Glacial Maximum - Yingfang Cui; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Quan Wang; Zhenjun Wang; Jianshun Chen; Hai Cheng; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Efficient separating dipropyl ether/isopropanol/water azeotrope by extractive distillation with mixed entrainer based on ionic liquid - Peizhe Cui; Yangyang Wang; Haiyang Cheng; Zhen Wang; Leilei Xin; Wenwu Xu; Yinglong Wang; Guoxuan Li; Zhaoyou Zhu (Journal of Cleaner Production, 2024)

Redistribution of phosphorus fraction driven by organic carbon and microbial community during composting - Lei Cheng; Hu Cui; Yang Ou; Lixia Wang; Meiwen Bao (Journal of Environmental Management, 2024)

Structural characteristics and gelling properties of citrus pectins after chemical and enzymatic modifications: Conformation plays a vital role in Ca2+-induced gelation - Jiefen Cui; Dan Liu; Yuyang Zhang; Mengyu Ma; Mengshan Shang; Cheng Zhao; Xingmiao Lu; Chengying Zhao; Jinkai Zheng (Food Chemistry, 2024)

Integrated virtual screening coupled with sensory evaluation identifies N-succinyl-L-tryptophan as a novel compound with multiple taste enhancement properties - Pimiao Huang; Zhirong Wang; Yuqing Cheng; Wenxiang Gao; Chun Cui (Food Chemistry, 2024)

Compatibility of vivianite-crystallization pathway of phosphorus recovery with anaerobic digestion systems of thermally hydrolyzed sludge - Haoran Cui; Xiaofan Yang; Xiaozhong Gao; Dezhi Sun; Xiang Cheng (Environmental Research, 2024)

A frequency-domain hydroelastic approach for modeling and stochastic dynamic analysis of pontoon-type floating bridges - Minghao Cui; Zhengshun Cheng; Peng Chen; Torgeir Moan (Engineering Structures, 2024)

Regional detrital zircon record of the drainage sediments surrounding the South China Sea: Provenance signature and tectonic implications - Ce Wang; Heqi Cui; Cheng-Shing Chiang; Ming Su; Letian Zeng; Junmin Jia; Liangjie Wei (Earth-Science Reviews, 2024)

In situ growth of hydrophobic 3D porous Zn@Ag electrode in achieving excellent performance for eCO2RR - Shenglin Yan; Xinyu Zhang; Samah A. Mahyoub; Bo Zhang; Xiangbei Wan; Yanran Cui; Pengfei Xie; Qiong Wang; Zhenmin Cheng; Zhenglong Li (Chemical Engineering Journal, 2024)

Endocytic pathways and metabolic fate of colloidal bismuth subcitrate in human renal cells - Yang Yang; Mengfei Tan; Jinbin Cui; He Liu; Hezhang Meng; Xiaju Cheng; Yangyun Wang; Yong Wang; Leshuai W. Zhang (Chemico-Biological Interactions, 2024)

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Identification of shallow groundwater recharge and circulation in an intensive agricultural area of the Sanjiang Plain, China, based on hydrochemistry, isotopes and hydrogeological conditions - Zhihong Li; Xuxue Cheng; Lin Lv; Huqun Cui; Weipo Liu; Jiangtao Liu; Tingwen Wu (Hydrogeology Journal, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Safety performance evaluation of offshore high integrity pressure protection system using multiphase dynamic Bayesian network methodology - Yang Yu; Yuqing Liang; Shibo Wu; Baoping Cai; Yu Pan; Ruilong Gao; Siyuan Cheng; Yupeng Cui; Yuheng Yang; Hao Guo (Ocean Engineering, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Chitosan aided polyaluminium ferric silicate (PAFS) coagulant for treatment of wool scouring wastewater - Cheng Wang; Congzhong Shi; Fangling Shi; Yongming Cui; Jinfeng Wang; Shouwei Zhang; Jiankun Zhu; Qingtao Liu (Journal of Environmental Chemical Engineering, 2024)

Modeling biomass degradation and biological respiration in biomass storage piles: A lab-scale investigation - Xinke Chen; Mingshuo Cui; Lun Ma; Qingyan Fang; Cheng Zhang; Gang Chen; Chungen Yin (Fuel, 2024)

Enzymatic synthesis and sensory evaluation of the novel kokumi compound N-butyryl phenylalanine - Lei Cai; Yuqin Cheng; Yuqing Pan; Lu Wang; Xu Zhao; Wenxiang Gao; Pimiao Huang; Chun Cui (Food Chemistry, 2024)

Molecular simulation screening and sensory evaluation unearth a novel kokumi compound with bitter-masking effect: N-lauroyl-L-tryptophan - Lei Cai; Liyu Li; Xu Zhao; Lu Wang; Yuqin Cheng; Wenxiang Gao; Chun Cui (Food Chemistry, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

Synergistic effects of biochar and laccase on nitrogen conversation and degradations of two artificial sweeteners during the sewage sludge composting - Jishao Jiang; Huilin Cui; Zhuyu Tang; Shipeng Wang; Ke Cheng; Chunyan Zhang; Tonghuan Yu; Jinghua Lv; Fuqiang Yu; Dong Liu (Chemical Engineering Journal, 2024)

A robust 3D nanostructured composite polymer electrolyte with novel dual-ion channels toward solid-state sodium metal batteries - Yunlong Cui; Pengyu Zhang; Yuan Tian; Cheng Wang; Su Wang; Yan Zhang; Xixi Shi; Yue Ma; Dawei Song; Hongzhou Zhang; Kai Liu; Na Zhang; et al. (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

Mining Pressure Distribution Law and Disaster Prevention of Isolated Island Working Face Under the Condition of Hard “Umbrella Arch” - Chong Jia; Xingping Lai; Feng Cui; Haidong Xu; Suilin Zhang; Yuhang Li; Cheng Zong; Zhong Luo (Rock Mechanics and Rock Engineering, 2024)

Correction to: Metal transport proteins and transcription factor networks in plant responses to cadmium stress - Chaochao Liu; Lang Wen; Yijia Cui; Golam Jalal Ahammed; Yuan Cheng (Plant Cell Reports, 2024)

Evaluating the spatiotemporal land ecological changes in the Yangtze-to-Huaihe Water Diversion Project area - Beibei Guo; Wei Li; Xuemin Kong; Tingting Cheng; Tingting Sun; Yingxue Cui (Environmental Science and Pollution Research, 2024)

Occurrence, toxicity and removal of polystyrene microplastics and nanoplastics in human sperm - Ying Chen; Cheng Cheng; Wenqing Xu; Yanfan Cui; Yan Tian; Yulin Jiang; Yangyang Yuan; Ruirui Qian; Yujie Wang; Liping Zheng; Houyang Chen; Tao Luo (Environmental Chemistry Letters, 2024)

Progressive failure characteristics of coal under uniaxial compression: A comprehensive application of micro-ct and digital volume correlation - Yanbin Yu; Chuanwen Ni; Wenting Cui; Weimin Cheng; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Novel phenazine-based microporous organic network for selective and sensitive determination of trace sulfonamides in milk samples - Zhao-Jun Hu; Xiao-Lin Luan; Yuan-Yuan Cui; Cheng-Xiong Yang (Analytica Chimica Acta, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Induced production of defensive secondary metabolites from Aspergillus fumigatiaffinis by co-culture with Aspergillus alabamensis - Zhibo Hu; Haishan Cui; Qiang Wang; Cheng Li; Senhua Chen; Zhizeng Gao; Lan Liu; Bo Peng; Jing Li (Phytochemistry, 2024)

A hierarchical framework for finite-time cooperative depth control of heterogeneous multi-AUV system - Yougang Bian; Jinlong Cheng; Changkun Du; Manjiang Hu; Qingjia Cui; Rongjun Ding (Ocean Engineering, 2024)

Coastal bridges with a box-girder superstructure under the action of solitary waves: Study on the optimization of bearings, dynamic characteristics and failure mechanism - Minglin Chen; Bo Huang; Cheng Cui; Zechen Xue; Zhiying Yang; Yong Xiao; Bing Zhu (Ocean Engineering, 2024)

Prediction of DEDI index for meteorological drought with the VMD-CBiLSTM hybrid model - Tao Su; Dan Liu; Xingyuan Cui; Xianshen Dou; Bo Lei; Xu Cheng; Mengning Yuan; Renjie Chen (Journal of Hydrology, 2024)

Spatial and temporal changes of air quality in Shandong Province from 2016 to 2022 and model prediction - Xu Zhang; Xinrui Zhang; Huanhuan Yang; Xu Cheng; Yong Guan Zhu; Jun Ma; Dayong Cui; Zhibin Zhang (Journal of Hazardous Materials, 2024)

Characterization of differences in physicochemical properties, volatile organic compounds and non-volatile metabolites of prune wine by inoculation of different lactic acid bacteria during malolactic fermentation - Jianqiao Jiang; Yun Xie; Miao Cui; Xiaomei Ma; Ruonan Yin; Yiwen Chen; Yongkang Li; Yue Hu; Weidong Cheng; Feifei Gao (Food Chemistry, 2024)

Nanoscale characterization of Ediacaran microfossils from lower Doushantuo formation chert nodules - Shiqi Cheng; Lianjun Feng; Chaoqun Zhang; Linhao Cui; Wei Liu; Hao Qiu; Shi He; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2024)

Metal transport proteins and transcription factor networks in plant responses to cadmium stress - Chaochao Liu; Lang Wen; Yijia Cui; Golam Jalal Ahammed; Yuan Cheng (Plant Cell Reports, 2024)

Pharmacokinetics and safety of a new generic lurasidone: a phase I bioequivalence study in healthy Chinese subjects - Zhengzhi Liu; Jinling Xue; Qiaohuan Deng; Yanli Wang; Lixiu Zhang; Lang Liu; Nan Xiao; Tianying Chang; Yingzi Cui; Yang Cheng; Guangwen Liu; Wanhua Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

A review on design and analysis of floating bridges: Numerical simulations, model tests and field measurements - Chao Wang; Minghao Cui; Zhengshun Cheng; Torgeir Moan (Ocean Engineering, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

Emission and optical characteristics of brown carbon in size-segregated particles from three types of Chinese ships - Fengqin Yang; Fan Zhang; Zeyu Liu; Yingjun Chen; Yan Zhang; Can Wu; Yali Lei; Shijie Liu; Binyu Xiao; Xinyi Wan; Yubao Chen; Yong Han; et al. (Journal of Environmental Sciences, 2024)

Linking Taiwan to the Cathaysia Block during the Cenozoic: Evidence from Pb isotopes in detrital K-feldspar - Ce Wang; Liangjie Wei; Cheng-Shing Chiang; David A. Foster; Heqi Cui; Ming Su (Global and Planetary Change, 2024)

Immunoprotective efficacy evaluation of OmpTS subunit vaccine against Aeromonas hydrophila infection in Megalobrama amblycephala - Zehua Xu; Minying Zhang; Ting Zhang; Hujun Cui; Hongping Li; Xu Wang; Xiaoheng Zhao; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Zhujin Ding (Fish & Shellfish Immunology, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Metal-organic frameworks derived low-cost Cu-doped Co3O4 for efficient reduction of ultra-low nitrate concentrations to ammonia - Xiaorui Hu; Mingming Zhang; Cui Lai; Min Cheng; Fuhang Xu; Dengsheng Ma; Ling Li; Huchuan Yan; Hao Sun; Xing Fan; Biting Wang (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

Impact of the COVID-19 pandemic on daily travel: Findings from New South Wales, Australia - Bo Du; Cheng Zhang; Tianyang Qu; Qi Wang; Quan Spring Zhou; Tingru Cui; Pascal Perez; Thomas Astell-Burt (Travel Behaviour and Society, 2024)

Informal E-waste dismantling activities accelerated the releasing of liquid crystal monomers (LCMs) in Pakistan: Occurrence, distribution, and exposure assessment - Yanhui Ge; Jingren Cui; Lianying Zhang; Shaohan Zhang; Mujtaba Baqar; Zhipeng Cheng (Science of The Total Environment, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Removal of the organophosphorus scale inhibitor potassium hexamethylenediamine tetramethylphosphonate (HDTMPA·K6) from industrial wastewater using UV oxidation, flocculation, and the Fenton reaction - LiChao Zhang; Yawen Luo; Wensu Gao; Guiqiao Wang; Jinzhi Cui; Yaxin Lu; Xing Rong; Zhongfa Cheng; Canzhu Gao (Journal of Water Process Engineering, 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Mechanism analysis and performance evaluation of clean and efficient recovery of N-heptanol/N-hexanol from wastewater via extractive distillation with green mixed entrainer - Haiyang Cheng; Yangyang Wang; Lili Yang; Wenxuan Zhao; Yan Zhang; Guoxuan Li; Zhaoyou Zhu; Yinglong Wang; Peizhe Cui (Journal of Cleaner Production, 2024)

Effects of different thawing methods on physical and physicochemical properties of frozen dough and quality of corresponding steamed bread - Fan Zhang; Jinying Guo; Peiyao Li; Fen Zhao; Xue Yang; Qiaofen Cheng; J. Stephen Elmore; Ping Wang; Can Cui (Food Chemistry, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Engineering hyperthermophilic pullulanase to efficiently utilize corn starch for production of maltooligosaccharides and glucose - Ting Xie; Li Zhou.; Laichuang Han; Cuiping You; Zhongmei Liu; Wenjing Cui; Zhongyi Cheng; Junling Guo; Zhemin Zhou (Food Chemistry, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Enhanced medium-chain fatty acid production from sewage sludge by combined electro-fermentation and anaerobic fermentation - Xiaoyan Sun; Hui Chen; Ting Cui; Lei Zhao; Cheng Wang; Xuejun Zhu; Tao Yang; Yanan Yin (Bioresource Technology, 2024)

Effect of temperature step-changes and ramps on physiological and psychological responses of occupants in office buildings in summer - Angchen Jiang; Yong Cheng; Yuxin Wu; Haijiao Cui; Guojian Li; Hong Liu; Baizhan Li (Building and Environment, 2024)

Enhancing grain shape, thermotolerance, and alkaline tolerance via Gγ protein manipulation in rice - Na Xu; Yuchao Qiu; Xin Cui; Cheng Fei; Quan Xu (Theoretical and Applied Genetics, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Lnc-HIBADH-4 Regulates Autophagy-Lysosome Pathway in Amyotrophic Lateral Sclerosis by Targeting Cathepsin D - Jingxuan Huang; Yujiao Yu; Dejiang Pang; Chunyu Li; Qianqian Wei; Yangfan Cheng; Yiyuan Cui; Ruwei Ou; Huifang Shang (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is the most prevalent and lethal class of severe motor neuron diseases (MND) with no efficacious treatment. The pathogenic mechanisms underlying ALS remain unclear. Nearly 90% of patients exhibit sporadic onset (sALS). Therefore, elucidating the pathophysiology of ALS is imperative. Long non-coding RNA (lncRNA) is a large class of non-coding RNAs that regulate transcription, translation, and post-translational processes. LncRNAs contribute to the pathogenesis of diverse neurodegenerative disorders and hold promise as targets for interference in the realm of neurodegeneration. However, the mechanisms of which lncRNAs are involved in ALS have not been thoroughly investigated. We identified and validated a downregulated lncRNA, lnc-HIBADH-4, in ALS which correlated with disease severity and overall survival. Lnc-HIBADH-4 acted as a “molecular sponge” regulating lysosomal function through the lnc-HIBADH-4/miR-326/CTSD pathway, thereby impacting autophagy-lysosome dynamics and the levels of cell proliferation and apoptosis. Therefore, this study discovered and revealed the role of lnc-HIBADH-4 in the pathogenesis of ALS. With further research, lnc-HIBADH-4 is expected to provide a new biomarker in the diagnosis and treatment of ALS.

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Enhancing the health benefits of air quality improvement: a comparative study across diverse scenarios - Chuang Han; Chuanlong Cheng; Ying Liu; Qidi Fang; Chunyu Li; Feng Cui; Xiujun Li (Environmental Science and Pollution Research, 2024)

A novel histone deacetylase inhibitor Se-SAHA attenuates isoproterenol-induced heart failure via antioxidative stress and autophagy inhibition - Tianwei Cheng; Chang Liu; Yufei Wang; Guangru Li; Lifeng Feng; Shengzheng Zhang; Bing Qi; Jianlin Cui; Lihong Guo; Lei Cao; Yanming Wang; Zhi Qi; et al. (Toxicology and Applied Pharmacology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Comprehensive assessment of copper's effect on marine organisms under ocean acidification and warming in the 21st century - Liang Cui; Chen Cheng; Xiaoguang Li; Xiangyun Gao; Xubo Lv; Yan Wang; Hua Zhang; Kun Lei (Science of The Total Environment, 2024)

Enhanced reaction extraction distillation via multi-objective optimization and 4E analysis for sustainable recovery of organic compounds from wastewater - Yumeng Wang; Wenguang Zhu; Haiyang Cheng; Jianhui Zhong; Xin Li; Jianguang Qi; Shuai Wang; Zhaoyou Zhu; Yinglong Wang; Peizhe Cui (Process Safety and Environmental Protection, 2024)

Evaluation and determinants of metro users' regularity: Insights from transit one-card data - Xinwei Ma; Xiaolin Tian; Zejin Jin; Hongjun Cui; Yanjie Ji; Long Cheng (Journal of Transport Geography, 2024)

Efficient detection of geosmin and 2-methylisoborneol in natural/drinking water by UIO66-NH2 composite-derived porous carbon - Wei Liu; Ming Yang; Shuang Wang; Yan-Sai Bao; Yong-He Cui; Ling-Xu Meng; Liang-Cheng Li; Yang Wu; Yu-Yang Zhang (Journal of Environmental Chemical Engineering, 2024)

Amide and carboxyl dual-functionalized magnetic microporous organic networks for efficient extraction of cephalosporins - Xu-Hui Li; Yuan-Yuan Cui; Shi-Lei Ji; Abdukader Abdukayum; Cheng-Xiong Yang (Food Chemistry, 2024)

Dynamic changes of physicochemical parameters, antioxidant activity, organic acids, polyphenols, and volatile components in prune vinegar during fermentation - Ruonan Yin; Jianqiao Jiang; Xiaomei Ma; Yun Xie; Miao Cui; Yiwen Chen; Yongkang Li; Yue Hu; Weidong Cheng; Feifei Gao (Food Bioscience, 2024)

Unveiling the biointerfaces characteristics and removal pathways of Cr(Ⅵ) in Bacillus cereus FNXJ1-2-3 for the Cr(Ⅵ)-to-Cr(0) conversion - Zhaoxia Li; Entian Cui; Naipeng Gu; Weixing Ma; Qingyuan Guo; Xuan Li; Jianxiang Jin; Qun Wang; Cheng Ding (Environmental Research, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Seasonality and potential generation mechanisms of submesoscale processes in the northern Bay of Bengal - Yifei Zhou; Wei Duan; Haijin Cao; Guidi Zhou; Rong Cui; Xuhua Cheng (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Bright cyan emission from Eu-Doped borosilicate glasses by optimizing reduction of Eu3+ to Eu2+ in ambient atmosphere - Jiuzhi Cui; Yufeng Wen; Runchuan Chen; Xi Cheng; Meidong Yu; Jiandi Liu; Zuofu Hu; Jiajun He; Zhuohao Xiao; Xin-Yuan Sun (Chemical Engineering Journal, 2024)

Self-stablized monodispersing nano-MOFs for controlled enzyme delivery - Peiwei Gong; Huiying Cui; Cheng Li; Shaohua Song; Yuwen Gong; Junyao Li; Bairen Wang; Fangxin Liu; Dandan Wang; Zhe Liu (Chemical Engineering Journal, 2024)

Application of multiple strategies to enhance oleanolic acid biosynthesis by engineered Saccharomyces cerevisiae - Xu Cheng; Yaru Pang; Yali Ban; Shuai Cui; Tao Shu; Bo Lv; Chun Li (Bioresource Technology, 2024)

An improved multi-filter fusion indoor localization algorithm based on INS and UWB - Long Cheng; Chen Cui; Zhijian Zhao; Yuanyuan Shi (Earth Science Informatics, 2024)

Di-n-butyl phthalate induces toxicity in male fetal mouse testicular development by regulating the MAPK signaling pathway - Xinwei Wan; Xudong Cui; Xiang Wang; Mingyang Feng; Shinan Wei; Jia Yu; Sha Cheng; Heng Luo; Jianxin Hu (Toxicology and Applied Pharmacology, 2024)

Ecotoxicity and trophic transfer of metallic nanomaterials in aquatic ecosystems - Lanlan Zhang; Yifei Cui; Jiake Xu; Jingran Qian; Xiaoqing Yang; Xiaoni Chen; Cheng Zhang; Peng Gao (Science of The Total Environment, 2024)

Effects of remediation agents on rice and soil in toxic metal(loid)s contaminated paddy fields: A global meta-analysis - Meng Liu; Ruiqing Xu; Xuedan Cui; Daibing Hou; Pengjie Zhao; Yanzhao Cheng; Yujie Qi; Guilan Duan; Guodong Fan; Aijun Lin; Xiao Tan; Yong Xiao (Science of The Total Environment, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

Multi-performance reliability-based concept-detailed co-design of offshore structures using modified conjugate FR algorithm - Yupeng Cui; Yang Yu; Siyuan Cheng; Mingxiu Wei; Yu Pan; Zewei Dong (Ocean Engineering, 2024)

Elemental and Sr isotopic compositions of plagioclase as an indicator of lunar source-rock type: Insights from Chang'e 5 plagioclase fragments - Le Zhang; Ya-Nan Yang; Zhi-Ming Chen; Jintuan Wang; Cheng-Yuan Wang; Ze-Xian Cui; Yan-Qiang Zhang; Yi-Gang Xu (Icarus, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Highly efficient molybdenum nanostructures for solar thermophotovoltaic systems: One-step fabrication of absorber and design of selective emitter - Tao Cui; Yan Shen; Ao Cheng; Zhe Liu; Shi Jia; Shuai Tang; Lei Shao; Huanjun Chen; Shaozhi Deng (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Evolution rules of coal mesopore structure under the action of hydraulic coupling - Yanbin Yu; Ruoyu Mu; Weimin Cheng; Wenting Cui; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Optimization Analysis of the Arrangement of the Submerged Floating Tunnel Subjected to Waves - Wenbo Pan; Cheng Cui; Chun Chen; Mingxiao Xie; Qian Gu; Zhiwen Yang (Journal of Marine Science and Engineering, 2024)
The motion responses, mooring tensions, and submergence depth are the dominant factors for the arrangement of the Submerged Floating Tunnel (SFT) subjected to waves. Generally, the maximum values of motion responses, mooring tensions, and absolute submergence depth are mainly focused on. In the present study, experiments are implemented to measure the motion responses and mooring tensions of the SFT with different mooring patterns and submergence depths under waves with different characteristic wave heights and periods. In order to evaluate the arrangement of the SFT more effectively and comprehensively, besides the maximum values, several new characteristic parameters are introduced. Such parameters account for the motion responses in the frequency domain, the uniformity of the tension distribution, the length of time during which the cable reaches a relaxed condition during wave action, the KC number, the dimensionless period, the wave height, and the submergence depth. The results from the optimization analysis show the following: according to the characteristic values of motion responses and mooring tensions, the pattern of diagonal cables is better than that of diagonal cables + vertical cables; and within the range of the present experiments, there are optimal dimensionless parameters—the dimensionless submergence depth d0/LP ≥ 0.15, the KC number ≤ 0.8, or the dimensionless wave height Hs/d0 ≤ 0.10—for the condition of which the dynamic responses and mooring tensions vary slightly.

Study on Dynamic Evolution and Erosion Characteristics of Cavitation Clouds in Submerged Cavitating Water Jets - Yanyu Cui; Manjun Zhao; Qingmiao Ding; Bin Cheng (Journal of Marine Science and Engineering, 2024)
The dynamic evolution behavior of submerged water jet cavitation clouds was studied by combining experiments and simulation. The formation, development, shedding, and collapsing process of a void cloud was analyzed by high-speed camera technology, and the influence of jet pressure was studied. Cavitation water jet erosion experiments were carried out on AL6061 specimens with standard cylindrical nozzles, and the correlation between cavitation cloud evolution and material erosion was studied by surface analysis. The results showed that the evolution of a cavitation cloud has obvious periodicity, that one period is about 0.8 ms, and its action region can be divided according to the attenuation rate of the jet velocity of the nozzle axis. The attenuation rate of the jet velocity at the nozzle axis in the central jet action zone is less than or equal to 82.5%, in the mixed action zone greater than 82.5% and less than 96%, and in the cavitation action zone greater than or equal to 96%. The erosion damage characteristics in different regions of the mixed action zone are significantly different.

Pyrolysis of exhausted biochar sorbent: Fates of cadmium and generation of products - Xiaoqiang Cui; Yuxin Yang; Jiangtao Wang; Zhanjun Cheng; Xutong Wang; Kiran Yasmin Khan; Shiwei Xu; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

A novel BACG inverse reliability algorithm for efficient and robust reliability-based topology optimization of marine structures - Yupeng Cui; Baolei Zhang; Yang Yu; Siyuan Cheng; Mingxiu Wei; Zihang Jin; Lin Song (Ocean Engineering, 2024)

Evolution of the Neo-Tethys traced by Late Triassic to Early Cretaceous marine remnants in the eastern segment of the Yarlung-Tsangpo suture zone, southern Tibet - Zhihao He; Xin Li; Yalin Li; Atsushi Matsuoka; Hui Luo; Xiaohui Cui; Jianbo Cheng (Journal of Asian Earth Sciences, 2024)

Effects of geometric structures on the sub-Kelvin porous media heat exchanger - Xue-shuo Shang; Han Gong; Xiao-xin Zeng; Bing-cheng Wang; Huai-qing Cao; Wei Shao; Zheng Cui (International Journal of Refrigeration, 2024)

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

β-Cyclodextrin based Pickering emulsions for α-tocopherol delivery: Antioxidation stability and bioaccessibility - Caiyun Cheng; Chao Yuan; Bo Cui; Jianpeng Li; Guimei Liu (Food Chemistry, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Active metal-free CaO-based dual-function materials for integrated CO2 capture and reverse water–gas shift - Yuqi Zhou; Xiaoling Ma; Qogluk Yusanjan; Hongjie Cui; Zhenmin Cheng; Zhiming Zhou (Chemical Engineering Journal, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Prediction of transformation in the histopathological growth pattern of colorectal liver metastases after chemotherapy using CT-based radiomics - Shengcai Wei; Xinyi Gou; Yinli Zhang; Jingjing Cui; Xiaoming Liu; Nan Hong; Weiqi Sheng; Jin Cheng; Yi Wang (Clinical & Experimental Metastasis, 2024)

Improved Biocompatibility and Angiogenesis of the Bone Titanium Scaffold through ERK1/2 Signaling Mediated by an Attached Strontium Element - Bingkun Cheng; Qing Yong Chen; Xueqiang Zhang; Jiahuan He; Qingqing Cui; Chao Ma; Jianjun Jiao (Biological Trace Element Research, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Exogenous melatonin enhanced cadmium stress tolerance of cucumber seedlings (Cucumis sativus L.) - Xin Kang; Zi-Qi Pei; Ting-Ting Xu; Cui-Yun Dong; Xue Bai; Cheng Ma; Qiao Zhu; Cai-Hong Chai; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Performance of public drinking water purifiers in control of trihalomethanes, antibiotics and antibiotic resistance genes - Liangyu Zhang; Wenjie Cui; Hongyan Zhai; Shengzi Cheng; Wenling Wu (Chemosphere, 2024)

Suppression of neutrophil extracellular traps is responsible for the amelioration of chemotherapeutic intestinal injury by the natural compound PEITC - Mei Bai; Shuaifei Li; Cui Zhang; Ning An; Jie Wang; Jia Qin; Rumeng Jia; Wentao Liu; Jingcai Cheng; Xuefeng Wu; Qiang Xu (Toxicology and Applied Pharmacology, 2024)

Effects of extreme temperature events on deaths and its interaction with air pollution - Chuanlong Cheng; Ying Liu; Chuang Han; Qidi Fang; Feng Cui; Xiujun Li (Science of The Total Environment, 2024)

Efficient recovery of aluminum, lithium, iron and gallium from coal fly ash leachate via coextraction and stepwise stripping - Li Cui; Lijuan Feng; Hefeng Yuan; Huaigang Cheng; Fangqin Cheng (Resources, Conservation and Recycling, 2024)

ECM1 promotes migration and invasion in endometriosis - Chen Zhang; Hongyan Cheng; Xue Ye; Heng Cui; Yi Li; Honglan Zhu; Xiaohong Chang (Reproductive Biology, 2024)

Provenance and tectonic settings of the lower Permian siliciclastic rocks in central Inner Mongolia: Implications for the evolution of the Paleo-Asian Ocean - Xinyu Cui; Lizhi Shi; Xianchun Tang; Zhuozhuo Wang; Jinxi Wang; Lijun Cheng; Longming Li; Biao Wang; Xiaomeng Han; Kaijun Zhang (Marine and Petroleum Geology, 2024)

Quantitative identification of the co-exposure effects of e-waste pollutants on human oxidative stress by explainable machine learning - Luhan Yang; Tao Zhang; Yanxia Gao; Dairui Li; Rui Cui; Cheng Gu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2024)

Comparative evaluation of soil accumulation of light stabilizers from biodegradable mulching films versus conventional polyethylene ones - Ruiqi Fan; Bingru Li; Qi Liu; Qiuyun Liu; Jixiao Cui; Runhao Bai; Yang Wang; Robert Elias; Cheng Li; Wenqing He (Journal of Hazardous Materials, 2024)

Key technologies improvements promote the economic-environmental sustainability in wheat production of China - Xu Wang; Chenhui Cui; Mengyao Xu; Beijia Cheng; Minghao Zhuang (Journal of Cleaner Production, 2024)

Temperature variability revealed by lacustrine brGDGTs in northeastern China since the Last Glacial Maximum - Chengcheng Leng; Qiaoyu Cui; Yan Zhao; Can Zhang; Xiaoshuang Sun; Tianlong Yan; Cheng Zhao (Global and Planetary Change, 2024)

A multi-layer nanocased model to explain the U-shaped evolution of shale gas permeability at constant confining pressure - Wangxing Cheng; Guanglei Cui; Yuling Tan; Derek Elsworth; Chunguang Wang; Chengxiang Yang; Tianyu Chen; Chuanzhong Jiang (Fuel, 2024)

Microstructure evolution law and dissolution time effect of bituminous coal under acetic acid acidification: Based on Micro-CT image analysis - Yanbin Yu; Hao Xing; Weimin Cheng; Wenting Cui; Yongtao Chen (Fuel, 2024)

Effects of starch–fatty acid complexes with different fatty acid chain lengths and degrees of saturation on the rheological and 3D printing properties of corn starch - Yue Cheng; Wei Gao; Xuemin Kang; Jianfei Wang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Chemistry, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

A novel tool for tracing water sources of streamflow in a mixed land-use catchment - Zhi-Xiang Sun; Jun-Fang Cui; Jian-Hua Cheng; Xiang-Yu Tang (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

The long-term spatial and temporal distributions of polychlorinated naphthalene air concentrations in Fildes Peninsula, West Antarctica - Tariku Bekele Gebru; Qinghua Zhang; Cheng Dong; Yanfen Hao; Cui Li; Ruiqiang Yang; Yingming Li; Guibin Jiang (Journal of Hazardous Materials, 2024)

Efficient lithium recovery from electrolytic aluminum slag via an environmentally friendly process: Leaching behavior and mechanism - Li Cui; Weihong Wang; Xi Chao; Jianming Gao; Fangqin Cheng (Journal of Cleaner Production, 2024)

Molecular simulation study on carbon dioxide replacement in methane hydrate near the freezing point - Liwei Cheng; Yunfei Li; Jinlong Cui; Qi Wu; Bei Liu; Fulong Ning; Guangjin Chen (Gas Science and Engineering, 2024)

Ultrasonic-assisted extraction of flavonoids from peanut leave and stem using deep eutectic solvents and its molecular mechanism - Yan Cheng; Huanzhu Zhao; Li Cui; Hidayat Hussain; Liliya Nadolnik; Zhihao Zhang; Yan Zhao; Xiuheng Qin; Jinfan Li; Jeong Hill Park; Daijie Wang (Food Chemistry, 2024)

Effects of wheat germ polysaccharides prepared by ultra-high pressure on functional constipation and gut microbiota - Chunbo Guan; Yukun Zhang; Heqin Wang; Qiufeng Chen; Xiao Pang; Xinwen Cui; Yongqiang Cheng; Xiuqing Zhang (Food Bioscience, 2024)

Seismic performance of special-shaped hexagonal concrete filled steel tubes with inner diaphragm plates and shear studs - Bai-Xiang Wang; Ran Ding; Jian-Guo Nie; Cui-Kun Wang; Peng Liu; Cheng-Hua Wang (Engineering Structures, 2024)

Effect of long-term straw return on organic matter transformation by hydroxyl radical during paddy soil oxygenation - Yanqi Xiao; Wei Peng; Junhong Fu; Yaqi Ning; Hao-jie Cui; Dong Cheng; Na Zhang; Weijun Zhou; Wenjuan Liao (Chemical Engineering Journal, 2024)

MEIC-global-CO2: A new global CO2 emission inventory with highly-resolved source category and sub-country information - Ruochong Xu; Dan Tong; Qingyang Xiao; Xinying Qin; Cuihong Chen; Liu Yan; Jing Cheng; Can Cui; Hanwen Hu; Wenyu Liu; Xizhe Yan; Huaxuan Wang; et al. (Science China Earth Sciences, 2024)

Fitting levels of 6-benzylademine matching seasonal explants effectively stimulate adventitious shoot induction in Cyclocarya paliurus (Batal.) Iljinskaja - Yuan Cheng; Yichan Cui; Xulan Shang; Xiangxiang Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

PCB126 impairs human sperm functions by affecting post-translational modifications and mitochondrial functions - Yebin Yang; Guangquan Mei; Liu Yang; Tao Luo; Runwen Wu; Shenglin Peng; Zhen Peng; Jiajun Cui; Yimin Cheng (Chemosphere, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Chronological features of Heinrich Stadial 2 based on a high-resolution analysis of δ18O stalagmite records from China, and possible links to changes in Atlantic Meridional Overturning Circulation - Yingfang Cui; Hao Xu; Yijia Liang; Kan Zhao; Jianshun Chen; Yongjin Wang; Jiaqi Cong; Hai Cheng; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A novel DBD/VUV/PMS process for efficient sulfadiazine degradation in wastewater: Singlet oxygen-dominated nonradical oxidation - Jing Lou; Jiutao An; Xiangyou Wang; Meng Cheng; Yingjun Cui (Journal of Hazardous Materials, 2024)

Life cycle comprehensive performance assessment of the TiAlN coated tool based on surface treatment - Yuxin Cui; Guangming Zheng; Junfeng Zhang; Chengli Jing; Xiang Cheng; Xianhai Yang (Journal of Cleaner Production, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Mechanism of interaction between astaxanthin and soy protein fibrils: Effects on complexes structure, rheological properties and bioaccessibility - Ning Li; Yi-fan Cui; Yi-an Liu; Mengyue Zhang; Yi-cheng Wang; Jiahui Shi; Xibo Wang; Ning Xu; Qingshan Chen (Food Hydrocolloids, 2024)

Composite interpretability optimization ensemble learning inversion surrounding rock mechanical parameters and support optimization in soft rock tunnels - Jingqi Cui; Shunchuan Wu; Haiyong Cheng; Gai Kui; Haoran Zhang; Meili Hu; Pengbin He (Computers and Geotechnics, 2024)

AMPKα is active in autophagy of endothelial cells in arsenic-induced vascular endothelial dysfunction by regulating mTORC1/p70S6K/ULK1 - Ziqi Xu; Qiaoling Liu; Jinyu Li; Jingqiu Wang; Zhihan Yang; Juan Wang; Lin Gao; Jin Cheng; Jing He; Yishan Dong; Xiangnan Guo; Jing Cui; et al. (Chemico-Biological Interactions, 2024)

Electrochemical biosensing for E.coli detection based on triple helix DNA inhibition of CRISPR/Cas12a cleavage activity - Jiuying Cui; Qisheng Luo; Cheng Wei; Xiandong Deng; Hongqu Liang; Jihua Wei; Yuanxun Gong; Qianli Tang; Kai Zhang; Xianjiu Liao (Analytica Chimica Acta, 2024)

Changes in years of life lost and life expectancy by reducing air pollution - Ying Liu; Shuxia Yang; Chunyu Li; Qidi Fang; Chuang Han; Chuanlong Cheng; Yunxian Cao; Feng Cui; Xiujun Li (Air Quality, Atmosphere & Health, 2024)

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Economic, environmental, exergy (3E) evaluations of recovering n-propyl acetate and n-propanol from wastewater via distillation coupled pervaporation - Wenxin Wang; Haiyang Cheng; Qing Zhao; Yangyang Wang; Xin Li; Zhaoyou Zhu; Yinglong Wang; Fang Wang; Peizhe Cui (Process Safety and Environmental Protection, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Fabrication of zwitterionic magnetic microporous organic network for efficient extraction of fluoroquinolone antibiotics from meat samples - Xu-Hui Li; Yuan-Yuan Cui; Xun Wu; Abdukader Abdukayum; Cheng-Xiong Yang (Food Chemistry, 2023)

Formation of fluorescent substances and correlation with process flavor changes of dehydrated Maillard reaction intermediates of peanut protein hydrolysates - Wenyu Zhou; Cheng Huang; Yishun Yao; Tong Zhou; Heping Cui; Yunwei Niu; Foxin Zhang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2023)

Controlled release mechanism of thymol loaded into mesoporous silica nanoparticles for active packaging films - Yingjun Cui; Xiangyou Wang; Meng Cheng; Yanli Guo; Rongfei Zhang (Food Bioscience, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Bio-inspired flexible versatile textiles for excellent absorption-dominated electromagnetic interference shielding, thermal management, and strain sensing - Teng Chen; Jun Cai; Xiang Cheng; Shuoming Cui; Deyuan Zhang; De Gong (Chemical Engineering Journal, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Micropeptides: origins, identification, and potential role in metabolism-related diseases - Yirui Lu; Yutong Ran; Hong Li; Jiao Wen; Xiaodong Cui; Xiaoyun Zhang; Xiumei Guan; Min Cheng (Journal of Zhejiang University-SCIENCE B, 2023)

Synergistic effects of technology and native aptitude in the perspective of industrial transfer for sustainable development in emerging economies - Sehresh Hena; Sufyan Ullah Khan; Baoyu Cui; Shahrukh Khan; Deyuan Zhang; Zhen Cheng (Environment, Development and Sustainability, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Different responses of precipitation patterns to the East Asian summer monsoon weakening: The 7.2 and 8.2 ka events - Liangkang Pan; Jingyao Zhao; Yan Yang; Kexin Wang; Carlos Pérez-Mejías; Jiahui Cui; Xiyu Dong; Rui Zhang; Hai Cheng (Quaternary Science Reviews, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Research on motion control of the semi-submersible platform under the mooring line failure - Siyuan Cheng; Yang Yu; Penghui Zhang; Baolei Zhang; Yupeng Cui; Zhengxin Huang; Xiaoming Zhang; Jianxin Yu; Zhenglong Yang (Ocean Engineering, 2023)

Impact of inherent calcium in coal on the structure and performance of activated carbon in flue gas activation: The enhanced mechanism of calcite on the methylene blue adsorption - Jian Niu; Lin Luo; Jinglei Cui; Huirong Zhang; Yanxia Guo; Linbo Li; Fangqin Cheng (Journal of Cleaner Production, 2023)

Study on the relationship between primary structure/ spatial conformation and gel properties of pectins from different varieties - Jiefen Cui; Lin Zhang; Jirong Wang; Shaojie Zhao; Cheng Zhao; Dan Liu; Wenxiang Li; Jinkai Zheng (Food Hydrocolloids, 2023)

Occurrences of typical PPCPs during wastewater treatment and the composting of sewage sludge with micron-sized and nano-sized Fe3O4 - Jishao Jiang; Rui Hou; Huilin Cui; Dong Liu; Guangxuan Yan; Yujuan Fan; Ke Cheng; Zhiguo Cao (Environmental Pollution, 2023)

Janus membranes with simultaneous flux enhancement and fouling/wetting resistance prepared by a modified interfacial polymerization process for membrane distillation - Cheng Lei; Jinlong Han; Tengyu Cui; Weifeng Cao; Yinhua Wan; Haoli Zhou; Fei Shen (Desalination, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

The disruption of blood-brain barrier induced by long-term arsenic exposure is associated with the increase of MMP-9 and MMP-2: The characteristics are similar to those caused by senescence - Man Lv; Xinbo Ma; Kunyu Zhang; Meichen Zhang; Yi Ji; Lin Cheng; Xinhua Shao; Ziqiao Guan; Jia Cui; Yanhui Gao; Yang Liu; Yanmei Yang; et al. (Chemico-Biological Interactions, 2023)

Clinical characteristics and prognostic risk factors of candidemia in non-neutropenic patients: a retrospective cohort study - Fengqi Liu; Xueping Shao; Zhaohui Dong; Kankai Tang; Li Zhong; Wei Xu; Zhidong Chen; Cheng Zheng; Kai Zhang; Jiachang Cai; Hongwei Zhou; Wei Cui; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Prominent Impact of Diurnal Rainfall Variations on Evapotranspiration and Gross Primary Productivity in Forests over Low Latitudes - Mengmiao Yang; Jane Liu; Yong Wang; Jing M. Chen; Zeyu Cui; Zhanjie Zhang; Zhixiong Chen; Xugeng Cheng (Agricultural and Forest Meteorology, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Low-carbon economic dispatch of integrated energy systems that incorporate CCPP-P2G and PDR considering dynamic carbon trading price - Yang Cui; Yang Xu; Tao Huang; Yijian Wang; Dingran Cheng; Yuting Zhao (Journal of Cleaner Production, 2023)

Design and multiple performance evaluation of green energy saving process for ethyl acetate/ethanol/water azeotrope separation by extractive distillation based on mixed solvent - Haiyang Cheng; Jianhui Zhong; Yasen Dai; Yuyang Jiao; Zhaoyou Zhu; Peizhe Cui; Jianguang Qi; Yinglong Wang (Journal of Cleaner Production, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Process design and multi-objective optimization for separation of isopropyl acetate/isopropanol/water by extractive distillation using ionic liquid mixed solvents - Qing Zhao; Mengjin Zhou; Haiyang Cheng; Jiuxu Ruan; Yangyang Wang; Zhaoyou Zhu; Peizhe Cui; Yinglong Wang; Jingwei Yang (Fuel, 2023)

Xylan derived carbon dots composite ZIF-8 and its immobilized carbon fibers membrane for fluorescence selective detection Cu2+ in real samples - Yingying Zhang; Xiaoci Cui; Xin Wang; Xiuyuan Feng; Yankang Deng; Weixia Cheng; Ranhua Xiong; Chaobo Huang (Chemical Engineering Journal, 2023)

NaNO2 additive-assisted Li2O2 decomposition for highly efficient cathode prelithiation of lithium-ion batteries - Rang Xiao; Cong Kang; Yang Ren; Renlong Li; Jiyuan Jian; Binghan Cui; Geping Yin; Xinqun Cheng; Yulin Ma; Hua Huo; Pengjian Zuo; Guokang Han; et al. (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Tenofovir disoproxil fumarate mediates neuronal injury by inducing neurotoxicity - Xiaotian Yang; Juanmei Zhang; Yanhong Cheng; Mengmeng Cui; Zhixiong Jiang; Chunhui Fan; Jiaxing Chen; Lixia Qi; Hongliang Liu; Dengke Bao (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Nitrogen and sulfur co-doped carbon quantum dots as “on-off-on” fluorescence probes to detect Hg2+ and MnO4− and improving the photostability of Rhodamine B - Wensu Gao; Shurong Zhang; Guiqiao Wang; Jinzhi Cui; Yaxin Lu; Xing Rong; Yawen Luo; LiChao Zhang; Zhongfa Cheng; Canzhu Gao (Analytica Chimica Acta, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Rapid and efficient extraction of Zn from wasted Zn-rich paint residue by indirect bioleaching and successive production of high-purity ZnCO3/ZnO by precipitation - Lingkai Wen; Gongchu Shi; Yingqin Sun; Yanchao Cui; Shihao Zhang; Xiaohui Chen; Jian Cheng; Jia Wang; Baoping Xin (Journal of Environmental Management, 2023)

Hexachlorocyclohexane impairs human sperm motility by affecting lysine glutarylation and mitochondrial functions - Liu Yang; Guangquan Mei; Yebin Yang; Jiajun Cui; Shenglin Peng; Zhen Peng; Yimin Cheng (Food and Chemical Toxicology, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Towards the automated virtual trial assembly of large and complex steel members using terrestrial laser scanning and BIM - Jiepeng Liu; Na Cui; Guozhong Cheng; Dongsheng Li; Xiaoxiao Ma; Yue Liao (Engineering Structures, 2023)

Prediction of single pile response to lateral soil movement in model test - Congyu Lin; Qijian Liu; Tao Deng; Cheng Yue; Penglu Cui (Computers and Geotechnics, 2023)

Protective effect of Platycodon grandiflorus polysaccharide on apoptosis and mitochondrial damage induced by pseudorabies virus in PK-15 cells - Yuxiao Xing; Yukun Cui; Guanlong Xu; Changxi Qi; Meihua Zhang; Guodong Cheng; Yongxia Liu; Jianzhu Liu (Cell Biochemistry and Biophysics, 2023)

Accumulation behavior of heavy metals by Bidens pilosa L. from metallurgical slag: effects on plant physiology and absorption characteristics - Meng Wei; Zheng Sun; Bu-li Cui; Yang He; Zhi-cheng Dong; Ling-xiao Meng (Journal of Mountain Science, 2023)

A review of remote sensing estimation of crop water productivity: definition, methodology, scale, and evaluation - Minghan Cheng; Dameng Yin; Wenbin Wu; Ningbo Cui; Chenwei Nie; Lei Shi; Shuaibing Liu; Xun Yu; Yi Bai; Yadong Liu; Yuqin Zhu; Xiuliang Jin (International Journal of Remote Sensing, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Autonomous Navigation Decision-Making Method for a Smart Marine Surface Vessel Based on an Improved Soft Actor–Critic Algorithm - Zhewen Cui; Wei Guan; Xianku Zhang; Cheng Zhang (Journal of Marine Science and Engineering, 2023)
In this study, an intelligent hybrid algorithm based on deep-reinforcement learning (DRL) is proposed to achieve autonomous navigation and intelligent collision avoidance for a smart autonomous marine surface vessel (SMASV). First, the kinematic model of the SMASV is used, and clauses 13 to 17 of the Convention on the International Regulations for Preventing Collisions at Sea (COLREGs) are introduced. Then, the electronic chart is rasterized and used for path planning. Next, states, actions, and reward functions are designed, and collision avoidance strategies are formulated. In addition, a temperature factor and a constrained loss function are used to improve the soft actor–critic (SAC) algorithm. This improvement reduces the challenges of hyperparameter adjustment and improves sampling efficiency. By comparing the improved SAC algorithm with other deep-reinforcement learning (DRL) algorithms based on strategy learning, it is proved that the improved SAC algorithm converges faster than the other algorithms. During the experiment, some unknown obstacles are added to the simulation environment to verify the collision-avoidance ability of the trained SMASV. Moreover, eight sea areas are randomly selected to verify the generalization ability of the intelligent-navigation system. The results show that the proposed method can plan a path for the SMASV accurately and effectively, and the SMASV decision-making behavior in the collision-avoidance process conforms to the COLREGs in both unknown and dynamic environments.

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Schiff base cross-linked dialdehyde β-cyclodextrin/gelatin-carrageenan active packaging film for the application of carvacrol on ready-to-eat foods - Haiying Cui; Qun Cheng; Changzhu Li; Myat Noe Khin; Lin Lin (Food Hydrocolloids, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

RETRACTED: Multifunctional chondroitin sulfate based hydrogels for promoting infected diabetic wounds healing by chemo-photothermal antibacterial and cytokine modulation - Yuan Zhang; Wenjuan Chen; Wenjing Feng; Wenhong Fang; Xiao Han; Cui Cheng (Carbohydrate Polymers, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Fermentation broth of food waste: A sustainable electron donor for perchlorate biodegradation - Lijie Cheng; Ningbo Gao; Cui Quan (Waste Management, 2023)

Spatiotemporal characteristics of ozone and the formation sensitivity over the Fenwei Plain - H.H. Ren; Y. Cheng; F. Wu; Z.L. Gu; J.J. Cao; Y. Huang; Y.G. Xue; L. Cui; Y.W. Zhang; J.C. Chow; J.G. Watson; R.J. Zhang; et al. (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Mooring line failure diagnosis and motion control of semi-submersible platform based on the predictive model - Yang Yu; Siyuan Cheng; Yupeng Cui; Xiaoming Zhang; Penghui Zhang; Jianxing Yu (Ocean Engineering, 2023)

Novel bimetallic chalcogenide adsorbents for elemental mercury removal from flue gas: A review - Xin Yang; Chen Gong; Yu Guan; Jingyi Li; Fangqin Li; Cheng Peng; Jiang Wu; Tianhui Cui; Shang Xiang; Yuan Gao (Fuel, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Mass balance of the Antarctic Ice Sheet from 2013 to 2018 estimated using the input-output method with updated remote sensing products - Yuan Cheng; Gang Hai; Xiangbin Cui; Da Lv; Gang Qiao; Rongxing Li (Science China Earth Sciences, 2023)

Identification and characterization of the gene BraANS.A03 associated with purple leaf color in pak choi (Brassica rapa L. ssp. chinensis) - Chen Tan; Haidong Chen; Guoqiang Dai; Yi Liu; Wenjie Shen; Chenchen Wang; Duannv Liu; Sijia Liu; Shuqi Xu; Bo Zhu; Daozong Chen; Cheng Cui (Planta, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Inspired by game theory: Multi-signal output photoelectrochemical point-of-care immunoassay based on target-triggered organic electronic barriers - Xianlin Han; Shujin Lin; Cui Cheng; Xiao Han; Dianping Tang (Analytica Chimica Acta, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Inversion of reclaimed soil water content based on a combination of multi-attributes of ground penetrating radar signals - Qi Cheng; Shiwen Zhang; Xiaoyang Chen; Hongbiao Cui; Yunfei Xu; Shasha Xia; Ke Xia; Tao Zhou; Xu Zhou (Journal of Applied Geophysics, 2023)

Effects of different laying periods on airborne bacterial diversity and antibiotic resistance genes in layer hen houses - Huan Cui; Cheng Zhang; Kui Zhao; Juxiang Liu; Jie Pu; Yunyi Kong; Shishan Dong; Ligong Chen; Yanbin Zhao; Yanyan Chen; Zhaoliang Chen; Lei Zhang; et al. (International Journal of Hygiene and Environmental Health, 2023)

Glucosinolates or erucic acid, which one contributes more to volatile flavor of fragrant rapeseed oil? - Qiang Liang; Wei Xiong; Qi Zhou; Cheng Cui; Xia Xu; Ling Zhao; Pu Xuan; Yingzheng Yao (Food Chemistry, 2023)

Anti-oxidative and anti-inflammatory effects of different lutein isomers in Caco-2 cell model - Ning Cui; Cheng Yang; Xuemei Chen; Jian Zhang; Lianfu Zhang (Food Bioscience, 2023)

Numerical and experimental study of the mechanical behaviour for FRP-wrapped cement mortar-coal composite disc - Xudong Shi; Guorui Feng; Jinwen Bai; Shanyong Wang; Kai Wang; Boqiang Cui; Xinyu Yang; Cheng Song; Hongchao Zhao (Computers and Geotechnics, 2023)

Sodium alginate reinforced polyacrylamide/xanthan gum double network ionic hydrogels for stress sensing and self-powered wearable device applications - Tuo Li; Huige Wei; Yingying Zhang; Tong Wan; Dapeng Cui; Shixiang Zhao; Teng Zhang; Yanxiu Ji; Hassan Algadi; Zhanhu Guo; Liqiang Chu; Bowen Cheng (Carbohydrate Polymers, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Study on the spatio-temporal evolution and influencing factors of farmland abandonment on a county scale - Cheng Wang; Yue Su; Shan He; Yan Xie; Panpan Xia; Yanglin Cui (Environmental Science and Pollution Research, 2023)

The neuroprotective effects of peracetylated chitosan oligosaccharides against β-amyloid-induced cognitive deficits in rats - Cui Hao; Minmin Han; Wei Wang; Cheng Yang; Jigang Wang; Yunliang Guo; Tao Xu; Lijuan Zhang; Chunxia Li (Marine Life Science & Technology, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Transcriptomics and physiological analyses unveil the distinct mechanisms of ATP and glucose-6-phosphate utilization in Phaeodactylum tricornutum - Xiaohua Zhang; Shuang Cheng; Zhengquan Gao; Yulin Cui; Qingshou Yao; Jiayang Qin; Xiangyong Liu; Senjie Lin (Frontiers in Marine Science, 2023)
Phosphoesters are a dominant component of marine dissolved organic phosphorus (DOP) and an important source of the phosphorus nutrient for phytoplankton, but the molecular mechanisms of their utilization by phytoplankton are divergent and poorly understood. In this study, we used the model diatom Phaeodactylum tricornutum to investigate and compare the utilization mechanisms of two different phosphoesters, adenosine triphosphate (ATP) and glucose-6-phosphate (G6P). We found that ATP and G6P can both be efficiently used to support the growth of P. tricornutum . Cells grown on ATP or G6P showed lower pigment contents and photosynthetic rates but higher cellular lipids relative to those grown on NaH 2 PO 4 (DIP). Surprisingly, in neither the ATP nor the G6P group were significant increases in whole-cell alkaline phosphatase (AP) activity detected, suggesting that utilization of both DOPs was not reliant on extracellular AP. Yet, ATP-grown cultures released DIP into the medium (i.e., ATP hydrolyzed extracellularly) whereas G6P-grown cultures did not. Furthermore, transcriptomic and RT-qPCR results showed that the gene encoding 5’ nucleotidase (5NT) in the ATP group and PhoD in the G6P group was upregulated. These results indicated that different pathways are involved in the use of these two DOPs, with ATP being hydrolyzed extracellularly likely by 5NT (PHATRDRAFT_44177) to release DIP for uptake, and G6P being directly absorbed and hydrolyzed intracellularly likely by PhoD (PHATRDRAFT_45757). Nevertheless, P. tricornutum under ATP and G6P conditions showed more similar transcriptomic profiles to each other than either compared to DIP-grown cultures, indicating similar metabolic functions of these two DOPs. These findings demonstrate that despite the high similarity in transcriptomic response to ATP and G6P conditions, the utilization mechanisms of these phosphoesters in the same species can be totally different, and the lack of AP activity does not necessarily signal the absence of DIP deficiency or the absence of DOP utilization.

Experimental Study on Hydrodynamic Characteristics of a Submerged Floating Tunnel under Freak Waves (I: Time-Domain Study) - Wenbo Pan; Meng He; Cheng Cui (Journal of Marine Science and Engineering, 2023)
The dynamic response characteristics of a two-dimensional submerged floating tunnel (SFT) under random and freak waves were investigated in the present study. The results demonstrate that (1) the dynamic responses of the SFT under the freak wave are significantly larger than those under the largest wave in the wave train excluding the freak wave, particularly for the motion response. The maximum values of the motion responses induced by the freak wave were several times larger than those induced by the largest wave in the wave train excluding the freak wave, far exceeding the proportion of the corresponding wave height. (2) The freak wave parameter α1 has a significant effect on the amplification coefficients of surge, heave and pitch; all increase nonlinearly as α1 increases. Within α1 = 1.90~2.59, the amplification coefficients of the surge, heave and pitch vary in the ranges of 1.91~6.46, 1.53~3.87 and 1.73~5.32, respectively. (3) Amplification coefficients of tension increase almost linearly as α1 increases. Additionally, the amplification effect of the freak wave on the mooring tension is much smaller than that on motion responses. Within α1 = 1.90~2.59, the amplification coefficients of tension vary from 1.15 to 1.35. (4) Generalised amplification coefficients of motion responses increase as α1 increases and are all greater than 1.0, indicating that growth rates for motion responses under the freak wave exceed the growth rates for maximum wave height. Moreover, motion responses show a significantly nonlinear growth as maximum wave height increases. The generalised amplification coefficients of the mooring tension decrease as α1 increases, and are all less than 1.0, indicating that the dynamic amplification effect of the freak wave on the mooring tension is much smaller than that on motions. On the other hand, growth rates of the mooring tension under freak waves are smaller than the linear growth rate of the height of freak waves.

Experimental Study of the Hydrodynamic Characteristics of a Submerged Floating Tunnel under Freak Wave (II: Time-Frequency Domain Study) - Wenbo Pan; Cheng Cui; Meng He (Journal of Marine Science and Engineering, 2023)
A freak wave is a spike in a random wave series and hence the local characteristics in the time-domain are of key importance. When freak waves act on moored floating structures, the dynamic responses of the structures in the time and frequency domains change interdependently in a short period of time. It is difficult to comprehensively and accurately describe this physical process using a single-dimensional analysis method, such as time-domain statistical analysis or frequency-domain spectral analysis. The wavelet analysis method, which can simultaneously provide the time-domain and frequency-domain joint information of the physical process, is used to discuss the time-frequency joint variation characteristics of the dynamic responses of a two-dimensional submerged floating tunnel under a freak wave. The time-frequency characteristics of the dynamic responses induced by the freak wave and the differences from the action under random waves are investigated, with a particular emphasis on the ‘convex variation’ characteristics of the dynamic responses under a freak wave. The results show that: (1) The wavelet analysis method can effectively describe the basic characteristics of the dynamic responses of the SFT under a freak wave and clearly distinguish the differences in dynamic responses under freak and random waves. (2) Freak waves have dynamic amplification effects, which are related to the freak wave parameter α1, on a two-dimensional SFT. Following the action of freak waves on a two-dimensional SFT, significant energy concentration occurs in the time-frequency spectrum of the dynamic response in a certain time and frequency range. The degree of energy concentration increases nonlinearly with an increase in α1, and a certain high-frequency energy appears in the time-frequency spectrum of the motion response. The maximum values of the time-frequency spectra of the dynamic responses under a freak wave are much larger than those under a random wave with the identical wave spectrum. (3) Following the action of a freak wave on a two-dimensional SFT, the generalised energy spectra of surge, heave, pitch, and mooring tensions have convex peak values, which occur simultaneous with the occurrence of the freak wave, and the convex parts significantly increase as α1. (4) The time lengths of the influence of a freak wave on the dynamic responses exceeded the freak wave period. With an increase in α1, the time ranges of the large values of the time-frequency spectra of surge, heave, pitch, and mooring tensions increase nearly linearly.

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Anisotropic interlayer Dzyaloshinskii-Moriya interactions in synthetic ferromagnetic multilayers - Ruyi Chen; Feng Xu; Qirui Cui; Jinghua Liang; Yongjian Zhou; Ning Wang; Feng Pan; Fei Xue; Hongxin Yang; Cheng Song (Science Bulletin, 2023)

Thermodynamic analysis of a food waste plasma gasification-based multigeneration system with dehumidification and carbon capture - Jifu Zhang; Haiyang Cheng; Zaifeng Xu; Yaru Zhou; Kexin Yin; Xianlong Wang; Ying Gao; Chaoyue Sun; Yinglong Wang; Peizhe Cui (Journal of Cleaner Production, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Spatiotemporal Variation Air Quality Index Characteristics in China’s Major Cities During 2014–2020 - Jianhua Cheng; Fayuan Li; Lulu Liu; Haoyang Jiao; Lingzhou Cui (Water, Air, & Soil Pollution, 2023)

Advances in spring leaf phenology are mainly triggered by elevated temperature along the rural-urban gradient in Beijing, China - Yuebo Su; Xuming Wang; Cheng Gong; Li Chen; Bowen Cui; Binbin Huang; Xiaoke Wang (International Journal of Biometeorology, 2023)

Levels, source apportionment, and risk assessment of polycyclic aromatic hydrocarbons in vegetable bases of northwest China - Nuerla Ailijiang; Xi Cui; Anwar Mamat; Yusuyunjiang Mamitimin; Naifu Zhong; Wenhu Cheng; Nanxin Li; Qiongfang Zhang; Miao Pu (Environmental Geochemistry and Health, 2023)

Positive contribution of predatory bacterial community to multiple nutrient cycling and microbial network complexity in arsenic-contaminated soils - Wei Dai; Mingqing Liu; Ning Wang; Xianfeng Ye; Yang Liu; Dandan Yao; Lei Wang; Zhongli Cui; Peirui Yan; Chunxiao Cheng; Zhonglin Huang; Hui Wang (Applied Soil Ecology, 2023)

Spatial distribution of anemophilous pollen and its correlation with the Asian summer monsoon on the southeastern Tibetan Plateau - Zhiyong Zhang; Dongmei Cheng; Dajun Xie; Zetian Liu; Jian Ni; Aizhi Sun; Yiming Cui; Zhongxin Duan; Qiqi Li (Palynology, 2023)

Flavonoid accumulation modulates the responses of cassava tuberous roots to postharvest physiological deterioration - Feifei An; Mengjia Cui; Ting Chen; Cheng Cheng; Zhu Liu; Xiuqin Luo; Jingjing Xue; Yanqiong Tang; Jie Cai; Songbi Chen (Postharvest Biology and Technology, 2023)

Ab initio kinetics of OH-initiated reactions of 2-furfuryl alcohol - Lili Xing; Jintao Cui; Liuchao Lian; Jinglan Wang; Huanhuan Wang; Yunrui He; Shaowei Wang; Xuetao Wang; Liyou Xu; Zhanjun Cheng (Fuel, 2023)

Effects of recess ratio on combustion characteristics of LOX/methane swirl coaxial injectors - Pengjin Cao; Peng Cheng; Xiao Bai; Qinglian Li; Chengchao Cui (Fuel, 2023)

Effect of molecular structure changes during starch gelatinization on its rheological and 3D printing properties - Yue Cheng; Kexin Liang; Yifan Chen; Wei Gao; Xuemin Kang; Tianze Li; Bo Cui (Food Hydrocolloids, 2023)

Coupling effect of freeze–thaw cycles and multiaxial compression on concrete-filled steel tube (CFST): Insights from simplified meso-scale axisymmetric finite element model - Facheng Wang; Bo Li; Zhengqing Cheng; Tao Cui (Engineering Structures, 2023)

Microbiome - based agents can optimize composting of agricultural wastes by modifying microbial communities - Fengshuo Li; Hossein Ghanizadeh; Guangliang Cui; Jiayin Liu; Shuang Miao; Chang Liu; Wenwei Song; Xiuling Chen; Mozhen Cheng; Peiwen Wang; Yao Zhang; Aoxue Wang (Bioresource Technology, 2023)

Fine-mapping and candidate gene analysis of the Mcgy1 locus responsible for gynoecy in bitter gourd (Momordica spp.) - Jian Zhong; Junjie Cui; Jia Liu; Chunfeng Zhong; Fang Hu; Jichi Dong; Jiaowen Cheng; Kailin Hu (Theoretical and Applied Genetics, 2023)

Genetic and enzymatic characterization of two novel blaNDM-36, -37 variants in Escherichia coli strains - Wanshan Ma; Bo Zhu; Wen Wang; Qian Wang; Xiaodi Cui; Yujiao Wang; Xiutao Dong; Xiaofeng Li; Jianping Ma; Fang Cheng; Xiaohong Shi; Liang Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The widespread of different NDM variants in clinical Enterobacterales isolates poses a serious public health concern, which requires continuous monitoring. In this study, three E. coli strains carrying two novel bla NDM variants of bla NDM-36, -37 were identified from a patient with refractory urinary tract infection (UTI) in China. We conducted antimicrobial susceptibility testing (AST), enzyme kinetics analysis, conjugation experiment, whole-genome sequencing (WGS), and bioinformatics analysis to characterize the bla NDM-36, -37 enzymes and their carrying strains. The bla NDM-36, -37 harboring E. coli isolates belonged to ST227, O9:H10 serotype and exhibited intermediate or resistance to all β-lactams tested except aztreonam and aztreonam/avibactam. The genes of bla NDM-36, -37 were located on a conjugative IncHI2-type plasmid. NDM-37 differed from NDM-5 by a single amino acid substitution (His261Tyr). NDM-36 differed from NDM-37 by an additional missense mutation (Ala233Val). NDM-36 had increased hydrolytic activity toward ampicillin and cefotaxime relative to NDM-37 and NDM-5, while NDM-37 and NDM-36 had lower catalytic activity toward imipenem but higher activity against meropenem in comparison to NDM-5. This is the first report of co-occurrence of two novel bla NDM variants in E. coli isolated from the same patient. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of NDM enzymes.

Regional differences in gully network connectivity based on graph theory: a case study on the Loess Plateau, China - Jian-hua Cheng; Lan-hua Luo; Fa-yuan Li; Lu-lu Liu; Ling-zhou Cui (Journal of Mountain Science, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Decades of reforestation significantly change microbial necromass, glomalin, and their contributions to soil organic carbon - Mengling Zhang; Rongxiao Che; Zhibao Cheng; Hongkai Zhao; Chengwei Wu; Jinming Hu; Song Zhang; Dong Liu; Xiaoyong Cui; Yibo Wu (Agriculture, Ecosystems & Environment, 2023)

Local singularity and S–A methods for analyzing ore-producing anomalies in the Jianbiannongchang area of Heilongjiang, China - Zhonghai Zhao; Kai Qiao; Yiwen Liu; Xiaomeng Cui; Binbin Cheng; Shanshan Liang; Chenglu Li (Acta Geochimica, 2023)

Study on Bearing Capacity of Reinforced Composite Pipe Pile Group in Reclaimed Stratum under Vertical Load - Xiaohua Bao; Zilong Cheng; Jun Shen; Xiaodong Zhang; Xiangsheng Chen; Hongzhi Cui (Journal of Marine Science and Engineering, 2023)
A new stiffened composite pipe pile was developed for improving the foundation of reclaimed ground in ocean engineering. To study the bearing capacity of the stiffened composite pipe pile group, a combination of field test and finite element method was used. Firstly, field tests were performed on the proposed single stiffened composite pipe pile. The single stiffened composite pipe pile model was verified by comparing the numerical simulation results with the field test results. The load transfer mechanism from the stiffened core to the cemented soil and the surrounding soil was clarified. Further, a 3D finite element model of the stiffened composite pipe pile group was established based on the single stiffened composite pipe pile model. Finally, the bearing capacity of the pile group and the stress distribution of each pile were analysed and the influence of the pile spacing on the pile bearing capacity was discussed. The results showed that the axial stress of both the side and corner piles decreased rapidly with an increase in the pile spacing, and the stress-bearing ratio decreased. The stress-bearing ratio of the central pile increases with an increase in pile spacing. The smaller the pile spacing, the larger the load proportion of the composite pile group and the larger the foundation settlement. The optimal design scheme was a composite pile with a 500 mm stiffened core diameter, 700 mm outer cemented soil diameter, and a spacing between piles of four times the cemented soil diameter (2.8 m) considering the group pile bearing capacity and the economic benefits of the project. These results provide a reference for the design and construction of stiffened composite piles for ground improvement projects.

Retinoic acid-induced differentiation of porcine prospermatogonia in vitro - Xueni You; Tianjiao Li; Youjie Cui; Wei Liu; Zechao Cheng; Wenxian Zeng; Peng Wang; Yi Zheng (Theriogenology, 2023)

Experimental study on penetration characteristics of an open-ended pile under static and dynamic driving methods - Jingxue Lu; Hongfeng Guang; Lin Cui; Junwei Liu; Cheng Wang; Subramani Anandha Kumar (Soil Dynamics and Earthquake Engineering, 2023)

A molecular level understanding of antimony immobilization mechanism on goethite by the combination of X-ray absorption spectroscopy and density functional theory calculations - Qian Sun; Cun Liu; Tingting Fan; Hu Cheng; Peixin Cui; Xueyuan Gu; Lina Chen; Syed Tahir Ata-Ul-Karim; Dongmei Zhou; Yujun Wang (Science of The Total Environment, 2023)

Application of MXene-based materials in Fenton-like systems for organic wastewater treatment: A review - Chuanbin Wang; Jingya Ye; Lan Liang; Xiaoqiang Cui; Lingchao Kong; Ning Li; Zhanjun Cheng; Wenchao Peng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Quantitative study on release kinetics of thymol in food packaging films - Yingjun Cui; Rongfei Zhang; Liang Wang; Meng Cheng; Yanli Guo; Xiangyou Wang (Journal of Food Engineering, 2023)

Design of carboxymethyl chitosan-reinforced pH-responsive hydrogels for on-demand release of carvacrol and simulation of release kinetics - Meng Cheng; Yingjun Cui; Yanli Guo; Peixin Zhao; Juan Wang; Rongfei Zhang; Xiangyou Wang (Food Chemistry, 2023)

The structure-function relationships of pectins separated from three citrus parts: Flavedo, albedo, and pomace - Lin Zhang; Jiefen Cui; Shaojie Zhao; Dan Liu; Cheng Zhao; Jinkai Zheng (Food Hydrocolloids, 2023)

Improving the mechanical and water-resistance properties of pea protein-based edible film via wet-heating Maillard reaction: Insights into the simultaneous effect of heating and Maillard reaction - Jingjing Cheng; Jing Wang; Zhengze Li; Bingcan Chen; Leqi Cui (Food Packaging and Shelf Life, 2023)

Water-in-water emulsions stabilized by self-assembled chitosan colloidal particles - Wanying Cui; Chunmiao Xia; Sheng Xu; Xinke Ye; Yihao Wu; Shukai Cheng; Rongli Zhang; Cuige Zhang; Zongcheng Miao (Carbohydrate Polymers, 2023)

Transferring a new Fusarium head blight resistance locus FhbRc1 from Roegneria ciliaris into wheat by developing alien translocation lines - Rongrong Song; Yifan Cheng; Mingxing Wen; Xinying Song; Tong Wang; Mengshuang Xia; Haojie Sun; Menghao Cheng; Huimin Cui; Chunxia Yuan; Xiaoxue Liu; Zongkuan Wang; et al. (Theoretical and Applied Genetics, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

Application and research progress of infrared thermography in temperature measurement of livestock and poultry animals: A review - Zhenjiang Cai; Jialiang Cui; Hongbo Yuan; Man Cheng (Computers and Electronics in Agriculture, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Synthesis of crown ether-based microporous organic networks: A new type of efficient adsorbents for chlorophenols - Yi-Xuan Wang; Yan-Ping Bi; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2023)

Role of interfacial electron transfer reactions on sulfamethoxazole degradation by reduced nontronite activating H2O2 - Hao-Jie Cui; Yaqi Ning; Cong Wu; Wei Peng; Dong Cheng; Lichu Yin; Weijun Zhou; Wenjuan Liao (Journal of Environmental Sciences, 2023)

Enhancing cadmium removal efficiency through spinel ferrites modified biochar derived from agricultural waste straw - Ma Bai; Youzheng Chai; Anwei Chen; Jiayi Yuan; Cui Shang; Liang Peng; Cheng Peng (Journal of Environmental Chemical Engineering, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

CO2 methanation over the Ni-based catalysts supported on the hollow ZSM-5 zeolites: Effects of the hollow structure and alkaline treatment - Yan Cui; Bin Chen; Leilei Xu; Mindong Chen; Cai-e Wu; Jian Qiu; Ge Cheng; Ning Wang; Jingxin Xu; Xun Hu (Fuel, 2023)

Effect of SBA-15-CEO on properties of potato starch film modified by low-temperature plasma - Yanli Guo; Meng Cheng; Yingjun Cui; Rongfei Zhang; Zitong Zhao; Xiangyou Wang; Shuaiyu Guo (Food Bioscience, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Insights into reactive species generation and organics selective degradation in Fe-based heterogeneous Fenton-like systems: A critical review - Ling Li; Zhuo Yin; Min Cheng; Lei Qin; Shiyu Liu; Huan Yi; Mingming Zhang; Yukui Fu; Xiaofeng Yang; Xuerong Zhou; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Impacts of river discharge, coastal geomorphology, and regional sea level rise on tidal dynamics in Pearl River Estuary - Xia Li; Yanzi Cai; Zezheng Liu; Xiaobiao Mo; Li Zhang; Cheng Zhang; Baoshan Cui; Ze Ren (Frontiers in Marine Science, 2023)
Introduction Recently, accelerated sea-level rise (SLR) has raised major concerns on estuarine management and restoration because it modifies estuarine hydrodynamics, such as tidal inundation extent and amplitude, tidal current asymmetry, flood frequency, etc. Understanding underlying processes which regulate estuarine tidal dynamics is critical for mitigating potential impacts on the coastal population and development. Methods We selected the Pearl River Estuary (PRE), an estuary with a higher regional SLR compared to the global SLR as the study area. To identify the effects of regional SLR on tidal dynamics, we analyzed long-term records of four tidal variables from 19 gauge stations between 1952 and 2020, including annual highest tidal levels (AHTLs), annual lowest tidal levels (ALTLs), annual mean tidal ranges (AMTRs), and annual mean tidal levels (AMTLs). Results Results suggested that variability in tidal variables was site-specific. The AMTRs decreased gradually from offshore regions to the upper reaches of rivers with a maximum at the mouth of the estuary. In contrast, the magnitudes of the AHTLs, AMTLs, and ALTLs decreased when approaching the coastline. Distance to the coastline had the highest correlations with the AHTLs, ALTLs, and AMTLs, followed by river width and river depth. The local SLR was responsible for the temporal variability in AHTLs, ALTLs, and AMTLs at the estuarine mouth with correlation coefficients from 0.43 to 0.85 (P < 0.001) but showed low correlations with these three tidal variables at the upper reaches of rivers (P > 0.001). Instead, the tidal variables were highly correlated with river discharge at the upper reaches of rivers, especially for the AHTLs (correlation coefficient = 0.83, P < 0.0001). Conclusions Our study demonstrated that the tidal dynamics demonstrate significant spatial-temporal variability. Geomorphology, river discharge, and sea levels have jointly affected estuarine hydrodynamics.

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Optimal local skin temperatures for mean skin temperature estimation and thermal comfort prediction of seated person in thermally stratified environments - Yuxin Wu; Zixuan Zhang; Hong Liu; Haijiao Cui; Yong Cheng (Journal of Thermal Biology, 2023)

CO2 methanation over the Ni-based catalysts supported on nano-CeO2 with varied morphologies - Yufang Bian; Chunying Xu; Xueying Wen; Leilei Xu; Yan Cui; Shuhan Wang; Cai-e Wu; Jian Qiu; Ge Cheng; Mindong Chen (Fuel, 2023)

Fast and sensitive UHPLC-QqQ-MS/MS method for simultaneous determination of typical α,β-unsaturated aldehydes and malondialdehyde in various vegetable oils and oil-based foods - Lukai Ma; Yun Cui; Feng Wang; Huifan Liu; Weiwei Cheng; Lianxin Peng; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao (Food Chemistry, 2023)

Interfacial behavior of cyclodextrins at the oil-water interface of Pickering emulsion - Caiyun Cheng; Chao Yuan; Bo Cui; Lu Lu; Jianpeng Li; Haojie Sha (Food Hydrocolloids, 2023)

Experimental and analytical studies on flexural behavior of composite bridge decks with orthotropic steel deck and ultra-high-performance concrete (UHPC) slab under negative moment - Yizhi Bu; Mingzhe Li; Chuan Wei; Zhenyu Cheng; Chuang Cui; Yi Bao (Engineering Structures, 2023)

Integrating multiple redox-active sites and universal electrode-active features into covalent triazine frameworks for organic alkali metal-ion batteries - Juan Chu; Linqi Cheng; Lan Chen; Heng-guo Wang; Fengchao Cui; Guangshan Zhu (Chemical Engineering Journal, 2023)

Chemical looping partial oxidation (CLPO) of toluene on LaFeO3 perovskites for tunable syngas production - Yi Lv; Binhai Cheng; Hang Yang; Xiaomin Cui; Ming Zhao (Chemical Engineering Journal, 2023)

Insight into a strategy to improve charge carrier migration in lead-free bismuth-based halide perovskite for efficient selective oxidation of thioanisole under visible light - Zihao Cui; Yaqiang Wu; Shuhui Zhang; Hui Fu; Guoqiang Chen; Zaizhu Lou; Xiaolei Liu; Qianqian Zhang; Zeyan Wang; Zhaoke Zheng; Hefeng Cheng; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2023)

Amygdalin alleviated TGF-β-induced epithelial-mesenchymal transition in bronchial epithelial cells - An-nan Zhang; Nan Li; Zhuo-chang Chen; Ya-li Guo; Cui-jie Tian; Dong-jun Cheng; Xue-yi Tang; Xiao-yu Zhang (Chemico-Biological Interactions, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Pollution levels, sources and risk assessment of polycyclic aromatic hydrocarbons in farmland soil and crops near Urumqi Industrial Park, Xinjiang, China - Xi Cui; Nuerla Ailijiang; Yusuyunjiang Mamitimin; Naifu Zhong; Wenhu Cheng; Nanxin Li; Qiongfang Zhang; Miao Pu (Stochastic Environmental Research and Risk Assessment, 2023)

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Geomorphologic evolution of the shallow-buried abandoned Yellow River delta during the last 2000 years - Qing Wang; Lin Zeng; Chao Zhan; Xianbin Liu; Longsheng Wang; Shanshan Cheng; Buli Cui (Frontiers in Marine Science, 2022)
Different from the continuous development of many river deltas since the major Holocene transgression, the modern Yellow River delta (YRD) remained for nearly 1000 years (from 893 AD to 1855 AD) in an abandonment state, until after 1855 AD when it was buried after the Yellow River entered the sea via Lijin. In this study we used optically stimulated luminescence (OSL) dating and grain size and sedimentary facies analysis of four borehole cores, combined with an analysis of landform morphology, to reconstruct the history of the ancient abandoned YRD. The results indicate that after the delta was abandoned due to the reduced sediment supply by the Yellow River in 893 AD, a sandy coast developed under the influence of wave erosion, and offshore shell ridges were formed beyond the coastline. During the interval from the Medieval Warm Period (MWP) to the Little Ice Age (LIA), driven by climate change and storm surges, the shell ridges migrated laterally, widened and rose, while sediment accumulation in the landward-side interfluvial floodplains was relatively weak. This configuration subsequently constituted a coastal highland – plain depression system. After 1077 AD, this system, together with the abandoned delta, was eroded by the Daqing River estuary. After 1855 AD, the abandoned delta landform system was completely buried by Yellow River sediments, and the wave-controlled sandy coast was transformed to a tide-controlled silt-mud coast. We summarize these findings in the form of a geomorphic model of the evolution of the abandoned delta from the MWP to the LIA. Overall, our results highlight the geomorphic effects of the sediment-laden river delta and the response of the abandoned delta geomorphic system on the millennial timescale, and they provide a theoretical foundation for predicting the geomorphic evolution of a major river delta on different timescales, against the background of global change.

Dynamics of extracellular polymeric substances and soil organic carbon with mangrove zonation along a continuous tidal gradient - Dong-Xi Liu; Zhi-Mao Mai; Cui-Ci Sun; Yan-Wu Zhou; Hui-Huang Liao; You-Shao Wang; Hao Cheng (Frontiers in Marine Science, 2022)
The importance of mangroves in blue carbon storage has been widely reported. However, the potential contribution of microbial extracellular polymeric substances (EPS) to the carbon pool is still poorly understood in mangrove ecosystems. Thus, a natural mangrove reserve located in Gaoqiao was chosen to investigate the linkage between microbial EPS and sediment organic carbon. Sequential resin extraction, Fourier transform infrared spectroscopy (FTIR), and 16S high-throughput sequencing were employed to determine the variations in EPS and bacterial taxa in different mangrove communities. Both EPS and EPS-C increased significantly with mangrove zonation from seaward to landward, irrespective of the EPS subfractions (colloidal and bound EPS) and components (extracellular protein and polysaccharide). Moreover, both EPS and EPS-C were found to be positively correlated with soil organic carbon. The present data further showed that EPS-C accounted for 1.84~10.69% of TOC in surface sediments. Multiple functional groups (e.g., O-H, N-H, and C=O), which may provide ligands for particle adsorption and complexation, were identified by FTIR. Consistent with the ascend of EPS with mangrove zonation from seaward to landward, the highest transmittance intensity for all functional groups was consistently exhibited in EPS isolated from landward Rhizophoraceae forest. In addition, the present data also indicated an interesting positive linkage between EPS and the abundance of some specific bacterial taxa, such as Rhizobiales, Corynebacteriales, and Gaiellales. In summary, this study claims the importance of EPS in the carbon pool in mangrove ecosystems. The present study may provide a better understanding of the functions of mangroves in carbon stocks.

Anti-Seizure and Neuronal Protective Effects of Irisin in Kainic Acid-Induced Chronic Epilepsy Model with Spontaneous Seizures - Jie Yu; Yao Cheng; Yaru Cui; Yujie Zhai; Wenshen Zhang; Mengdi Zhang; Wenyu Xin; Jia Liang; Xiaohong Pan; Qiaoyun Wang; Hongliu Sun (Neuroscience Bulletin, 2022)

Hydrogen Sulfide Attenuates High-Fat Diet-Induced Obesity: Involvement of mTOR/IKK/NF-κB Signaling Pathway - Maofang Zhao; Yuan Cheng; Xiaoxuan Wang; Xiaoying Cui; Xiaojing Cheng; Qian Fu; Yilin Song; Peiquan Yu; Yi Liu; Yinghua Yu (Molecular Neurobiology, 2022)

What are the disease burden and its sensitivity analysis of workers exposing to Staphylococcus aureus bioaerosol during warm and cold periods in a wastewater treatment plant? - Jiaxin Ma; Dongzi An; Beibei Cui; Manli Liu; Hao Zhu; Ming Li; Xiaojun Ai; Wajid Ali; Cheng Yan (Environmental Science and Pollution Research, 2022)

Investigation of microplastic pollution on paddy fields in Xiangtan City, Southern China - Yudi Wang; Wenjie Cui; Zhenghua Duan; Li Qin; Haihong Zhang; Haodong Cheng; Lei Wang (Environmental Science and Pollution Research, 2022)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Progress in Intradermal and Transdermal Gene Therapy with Microneedles - Ting Zhu; Wenya Zhang; Pengju Jiang; Shuwen Zhou; Cheng Wang; Lin Qiu; Honglei Shi; Pengfei Cui; Jianhao Wang (Pharmaceutical Research, 2022)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Buffer effect of MgO on Na2SO3 to stabilize S(IV) for the enhancement in simultaneous absorption of NOx and SO2 from non-ferrous smelting gas - Wenjun Huang; Sichao Li; Hongbin Wang; Peng Cui; Haomiao Xu; Can Cheng; Zan Qu; Naiqiang Yan (Environmental Science and Pollution Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of coastal marsh conversion to shrimp aquaculture ponds on sediment nitrogen fixation - Cheng Liu; Niu Li; Xuexin Shao; Dengzhou Gao; Jiangbao Xia; Qian Cui; Dongjie Zhang (Frontiers in Marine Science, 2022)
As a common reclamation practice in global estuaries and coasts, conversion of natural wetlands to aquaculture ponds for food demand had significant effects on nitrogen (N) cycling processes. However, the response of sedimemt N fixation process on this conversion remains poorly understood. Here, slury incubation experiment combined with 15 N isotope tracing method and molecular analysis technique were used to investigate the influences of conversion of natural marshland to shrimp ponds on sediemt N fixation process. The results showed that conversion of natural marshland to shrimp ponds significantly promoted sediment N fixation rate. The increasing of sediment N fixation rate may be mainly attributed to the change of sediment EC, TOC and Fe 2+ /Fe 3+ rather than the change of N fixation gene abundance. In addition, there was no obvious difference in sediment N fixation rate between 5-year-old shrimp ponds and 18-year-old shrimp ponds, which may be ascribed to the increasing inhibiting effect of inorganic N concentration with reclamation time. Overall, our findings highlighted that conversion of natural wetlands to aquaculture ponds can affect the N budgets in estuarine and coastal regions by altering the sediment N fixation process.

Bamboo cellulose–derived activated carbon aerogel with controllable mesoporous structure as an effective adsorbent for tetracycline hydrochloride - Ce Cui; Mengyuan Yang; Jianyu Zhai; Wenhao Bai; Lanling Dai; Li Liu; Shan Jiang; Weijie Wang; Erhui Ren; Cheng Cheng; Ronghui Guo (Environmental Science and Pollution Research, 2022)

Recent advances in alleviating food allergenicity through fermentation - Xiaowen Pi; Yili Yang; Yuxue Sun; Qiang Cui; Yin Wan; Guiming Fu; Hongbing Chen; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Particle breakage mechanism and particle shape evolution of calcareous sand under impact loading - Xing Wang; Ying Wang; Cheng Liao; Jie Cui; Jian-Hua Shen; Xin-Zhi Wang; Chang-Qi Zhu (Bulletin of Engineering Geology and the Environment, 2022)

Nanoscale storage encryption: data storage in synthetic DNA using a cryptosystem with a neural network - Yue Teng; Shan Yang; Liyan Liu; Ruicun Liu; Yaofeng Chen; Jinyu Li; Qian Yang; Tuoyu Liu; Yujun Cui; Peng Cheng; Shengqi Wang (Science China Life Sciences, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Nitrogen Enrichment Reduces the Diversity of Bacteria and Alters Their Nutrient Strategies in Intertidal Zones - Yuan-Feng Xu; Xu-Meng Dong; Cheng Luo; Shuo-Nan Ma; Ji-Lin Xu; Yong-De Cui (Frontiers in Marine Science, 2022)
Intertidal ecosystems are affected by severe nitrogen (N) pollution as a result of anthropogenic activities, and it is unclear how this may affect intertidal microbial communities, which play critical roles in regulating biogeochemical cycles. To address this gap, we conducted a two-month mesocosm experiment using six targeted concentrations of total N. The findings indicated that N entering seawaters has direct negative effects on the bacterial diversity. Dose dependence was found for the effects of N on bacterial diversity in sediment: low N addition increased the bacterial diversity, but a reduction in bacterial diversity occurred when N exceeded a certain value (≥ 3 mg L−1). Additionally, N enrichment caused clear shifts in bacterial community composition with increases in the relative abundance of Balneola (organic-degrading), Phalacroma mitra (carbohydrate-fermenting), and Bacteroides (phosphorus (P)-solubilizing), and decreases in Leptolyngbya_PPC_6406 (N2-fixing). The increased abundance in P-solubilizing and organic-degrading bacteria and decrease in N-fixing bacteria, combined with the upregulated activity of alkaline phosphatase and downregulation of urease activity, implied that the bacterial assemblage tended to be more effective in P and carbon acquisition but reduced N acquisition. Further path analysis suggested that N had direct effects on bacteria and contributed 50%–100% to the variations in bacterial diversity, whereas environmental changes such as dissolved oxygen and pH played minor roles. Overall, bacteria occurring in sediment were likely more stress-resistant to high N exposure than those occurring in seawater, possibly due to the high buffering capacity of sediment and growth tolerances of bacteria in the sediment. These findings point to the vulnerability of microbes in water systems to increasing global N loading, and that N reduction is needed to combat the loss of microbial diversity.

Effects of nitrogen addition on the concentration and composition of soil-based dissolved organic matter in subtropical Pinus taiwanensis forests - Xiaochun Yuan; Juyan Cui; Kaimiao Lin; Cheng-Chung Liu; Jiacong Zhou; Qiufang Zhang; Quanxin Zeng; Lianzuan Wu; Yue Wu; Kongcan Mei; Huiying Lin; Huan Xie; et al. (Journal of Soils and Sediments, 2022)

Seasonal Variation of Catenary-Bead Dunes in the Yangtze River Estuary: Causes and Implications - Shuwei Zheng; Xinmeng Yuan; Suxian Yang; Heqin Cheng; Xingjie Guo; Yurong Cui; Enfeng Liu; Zijun Li (Journal of Marine Science and Engineering, 2022)
Low-angle lee-side slopes of dunes are commonly developed on the world’s riverbeds, and dune migration associated with sediment transport exert a major influence on riverine processes. However, the catenary-bead dune has been identified in the Yangtze River (YR) Estuary, featuring a higher lee-side angle. To date, the morphological variation and formation reasons of catenary-bead dunes in the YR Estuary remain uncharacterized. In this study, we used a multibeam echo system (MBES) to investigate the bedforms of the YR estuary during 2014–2015, as well as to discuss the seasonal variation of catenary-bead dunes. The results indicate that the catenary-bead dunes of the YR Estuary are characterized by growth during the flood season and extinction during the dry season. The lee-side angle is typically ~16.7°, which is larger than that of other dune types (3.7–8°) in the estuary; moreover, the catenary-bead dunes are higher than other dune types of the same length in the YR Estuary. The relationship between the dune height (H) and length (L) was found to be H = 0.1667L0.603 (R2 = 0.38), while the other dune types yielded the relationship of H = 0.0845L0.758 (R2 = 0.52). Strong runoff superimposing the ebb tide led to the development of catenary-bead dunes. Furthermore, the higher coarse sediment content (69.9–72%) and lower clay content (6.3–6.7%) of the riverbed sediment are favorable for their formation, while the higher curved crest-lines are favorable for the formation of the associated elliptical pits.

GAS5/METTL14/ESR1 genetic variants are related to the susceptibility of coronary heart disease - Yuxiao Sun; Zhaoyun Cheng; Mingxia Cui; Yan Chen; Ruigang Xie; Guoqing Lu; Chuanyu Gao (Functional & Integrative Genomics, 2022)

Functional characterization of chalcone isomerase gene HvCHI revealing its role in anthocyanin accumulation in Hosta ventricosa - Qin Shijie; Zhao Xue; Cui Baiqi; Cheng Jianlin; Liu Shuying; Liu Hongzhang (Brazilian Journal of Botany, 2022)

Inhibitory effect of Lactobacillus gasseri CCFM1201 on Gardnerella vaginalis in mice with bacterial vaginosis - Qiuxiang Zhang; Qiuhan Cheng; Shumao Cui; Jianxin Zhao; Wei Chen; Hao Zhang (Archives of Microbiology, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Modified Green–Ampt Model Considering Vegetation Root Effect and Redistribution Characteristics for Slope Stability Analysis - Shaohong Li; Peng Cui; Ping Cheng; Lizhou Wu (Water Resources Management, 2022)

Novel combination of bioleaching and persulfate for the removal of heavy metals from metallurgical industry sludge - Chen Chen; Huidong Li; Fengjiao Cui; Zhixia Wang; Xinxin Liu; Gang Jiang; Tianjia Cheng; Runying Bai; Lei Song (Environmental Science and Pollution Research, 2022)

Hydrogen-Rich Medium Regulates Cr(VI)-Induced ER Stress and Autophagy Signaling in DF-1 Cells - Kangping Liu; Yukun Cui; Hongyan Li; Changxi Qi; Guodong Cheng; Xin Gao; Zhuanglong Zhang; Yongxia Liu; Jianzhu Liu (Biological Trace Element Research, 2022)

Shear behaviour of reproduced rough and bolted marble joints using the 3D carving technique - Guangtan Cheng; Chuanxiao Liu; Jian Zhang; Ning Zhang; Guojian Cui (Arabian Journal of Geosciences, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Conspecific disturbance odors act as alarm cues to affect female mate choice in a treefrog - Ke Deng; Ya Zhou; Hao-Di Zhang; Qiao-Ling He; Bi-Cheng Zhu; Tong-Liang Wang; Ji-Chao Wang; Wouter Halfwerk; Jian-Guo Cui (Behavioral Ecology and Sociobiology, 2022)

Characteristics of Historical Underground Storage Sites of Capacitors Containing Polychlorinated Biphenyls - Yong Cui; Yuhang Ning; Guo Chen; Lei Zhang; Xin Wang; Weiguo Cheng; Haimeng Hou; Chong Zhang; Jian Wang (Water, Air, & Soil Pollution, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Influence of Functional Group Modification on the Toxicity of Nanoplastics - Haihong Zhang; Haodong Cheng; Yudi Wang; Zhenghua Duan; Wenjie Cui; Yansong Shi; Li Qin (Frontiers in Marine Science, 2022)
Nanoplastics (NPs) are ubiquitous in harvested organisms at various trophic levels, and more concerns on their diverse responses and wide species-dependent sensitivity are continuously increasing. However, systematic study on the toxic effects of NPs with different functional group modifications is still limited. In this review, we gathered and analyzed the toxic effects of NPs with different functional groups on microorganisms, plants, animals, and mammalian/human cells in vitro. The corresponding toxic mechanisms were also described. In general, most up-to-date relevant studies focus on amino (−NH 2 ) or carboxyl (−COOH)-modified polystyrene (PS) NPs, while research on other materials and functional groups is lacking. Positively charged PS-NH 2 NPs induced stronger toxicity than negatively charged PS-COOH. Plausible toxicity mechanisms mainly include membrane interaction and disruption, reactive oxygen species generation, and protein corona and eco-corona formations, and they were influenced by surface charges of NPs. The effects of NPs in the long-term exposure and in the real environment world also warrant further study.

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

DAL-1/4.1B promotes the uptake of exosomes in lung cancer cells via Heparan Sulfate Proteoglycan 2 (HSPG2) - Shuai Zhang; Min Guo; Tingting Guo; Mingyan Yang; Jiaqi Cheng; Chenyang Cui; Jie Kang; Jiajia Wang; Yuanru Nian; Wenjie Ma; Haibin Weng; Haibo Weng (Molecular and Cellular Biochemistry, 2022)

Impacts of pavement on the growth and biomass of young pine, ash and maple trees - Bowen Cui; Xuming Wang; Yuebo Su; Yuanyuan Chen; Weiwei Yu; Cheng Gong; Li Li; Abdur Rehim; Xiaoke Wang (Trees, 2021)

Endocrine pheromones couple fat rationing to dauer diapause through HNF4α nuclear receptors - Cheng Gao; Qi Li; Jialei Yu; Shiwei Li; Qingpo Cui; Xiao Hu; Lifeng Chen; Shaobing O. Zhang (Science China Life Sciences, 2021)

Efficiency of sulfamethoxazole removal from wastewater using aerobic granular sludge: influence of environmental factors - Di Cui; Zeyi Chen; Ximing Cheng; Guochen Zheng; Yuan Sun; Hongna Deng; Wenlan Li (Biodegradation, 2021)

A novel regQTL-SNP and the risk of lung cancer: a multi-dimensional study - Yuhui Yu; Liping Mao; Zhounan Cheng; Xiaoqi Zhu; Jiahua Cui; Xiaoyu Fu; Jingwen Cheng; Yan Zhou; Anni Qiu; Yang Dong; Xun Zhuang; Yihua Lu; et al. (Archives of Toxicology, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Paternal exposure to microcystin-LR induces fetal growth restriction partially through inhibiting cell proliferation and vascular development in placental labyrinth - Lan Gao; An-Qi Cui; Jing Wang; Jing Chen; Xiao-Yi Zhang; Zhi-Jing Lin; Yuan-Hua Chen; Cheng Zhang; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2021)

Comparative physiological and proteomic analyses of mangrove plant Kandelia obovata under cold stress - Jiao Fei; You-Shao Wang; Hao Cheng; Fu-Lin Sun; Cui-Ci Sun (Ecotoxicology, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

SETD3 Downregulation Mediates PTEN Upregulation-Induced Ischemic Neuronal Death Through Suppression of Actin Polymerization and Mitochondrial Function - Xiangyu Xu; Yu Cui; Congqin Li; Yuyang Wang; Jing Cheng; Songfeng Chen; Jiangdong Sun; Jinyang Ren; Xujin Yao; Jingchen Gao; Xiaohong Huang; Qi Wan; et al. (Molecular Neurobiology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Complex analysis of the personalized pharmacotherapy in the management of COVID-19 patients and suggestions for applications of predictive, preventive, and personalized medicine attitude - Lei-Yun Wang; Jia-Jia Cui; Qian-Ying OuYang; Yan Zhan; Yi-Min Wang; Xiang-Yang Xu; Lu-Lu Yu; Hui Yin; Yang Wang; Chen-Hui Luo; Cheng-Xian Guo; Ji-Ye Yin (EPMA Journal, 2021)
Aims Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide. Drug therapy is one of the major treatments, but contradictory results of clinical trials have been reported among different individuals. Furthermore, comprehensive analysis of personalized pharmacotherapy is still lacking. In this study, analyses were performed on 47 well-characterized COVID-19 drugs used in the personalized treatment of COVID-19. Methods Clinical trials with published results of drugs use for COVID-19 treatment were collected to evaluate drug efficacy. Drug-to-Drug Interactions (DDIs) were summarized and classified. Functional variations in actionable pharmacogenes were collected and systematically analysed. “Gene Score” and “Drug Score” were defined and calculated to systematically analyse ethnicity-based genetic differences, which are important for the safer use of COVID-19 drugs. Results Our results indicated that four antiviral agents (ritonavir, darunavir, daclatasvir and sofosbuvir) and three immune regulators (budesonide, colchicine and prednisone) as well as heparin and enalapril could generate the highest number of DDIs with common concomitantly utilized drugs. Eight drugs (ritonavir, daclatasvir, sofosbuvir, ribavirin, interferon alpha-2b, chloroquine, hydroxychloroquine (HCQ) and ceftriaxone had actionable pharmacogenomics (PGx) biomarkers among all ethnic groups. Fourteen drugs (ritonavir, daclatasvir, prednisone, dexamethasone, ribavirin, HCQ, ceftriaxone, zinc, interferon beta-1a, remdesivir, levofloxacin, lopinavir, human immunoglobulin G and losartan) showed significantly different pharmacogenomic characteristics in relation to the ethnic origin of the patient. Conclusion We recommend that particularly for patients with comorbidities to avoid serious DDIs, the predictive, preventive, and personalized medicine (PPPM, 3 PM) strategies have to be applied for COVID-19 treatment, and genetic tests should be performed for drugs with actionable pharmacogenes, especially in some ethnic groups with a higher frequency of functional variations, as our analysis showed. We also suggest that drugs associated with higher ethnic genetic differences should be given priority in future pharmacogenetic studies for COVID-19 management. To facilitate translation of our results into clinical practice, an approach conform with PPPM/3 PM principles was suggested. In summary, the proposed PPPM/3 PM attitude should be obligatory considered for the overall COVID-19 management.

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

A New Direct Shear Apparatus for Rock Joints Specialized in Cyclic Loading - Zhen Cui; Qian Sheng; Mao-chu Zhang; Jun-feng Cao; Xian-cheng Mei; Qing-zi Luo (Rock Mechanics and Rock Engineering, 2021)

First report of chick peach (Prunus persica L.) leaf spot disease caused by Didymella glomerata in China - Yiping Cui; Aitian Peng; Xiaobing Song; Baoping Cheng; Jinfeng Ling; Xia Chen (Journal of Plant Pathology, 2021)

Electricity end-use and construction activity are key leverage points for co-controlling greenhouse gases and local pollution in China - Li-Jing Liu; Qiao-Mei Liang; Felix Creutzig; Nan Cheng; Lan-Cui Liu (Climatic Change, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

Experimental investigation on dynamic mechanical characteristics and fracture mechanism of coal under repeated impact loads - Kai Wang; Guorui Feng; Tingye Qi; Jinwen Bai; Yujiang Zhang; Jun Guo; Cheng Song; Boqiang Cui (Arabian Journal of Geosciences, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Absorption and Aggregation Characteristics and Changes in the Reflectance Spectrum of an Arid Desert Plant under Gold, Copper, Zinc and Nickel Stress - Shichao Cui; Kefa Zhou; Rufu Ding; Jinlin Wang; Yinyi Cheng; Guo Jiang; Kai Ma (Natural Resources Research, 2021)

A Pyrene Fluorescent Probe for Rapid Detection of Ferric Ions - Guiqiao Wang; Xiaowei Liu; Shaokang Cai; Shurong Zhang; Jinzhi Cui; Canzhu Gao; Zhongfa Cheng (Journal of Fluorescence, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

Gas Flow Characteristics and Optimization of Gas Drainage Borehole Layout in Protective Coal Seam Mining: A Case Study from the Shaqu Coal Mine, Shanxi Province, China - Zhiheng Cheng; Hui Pan; Quanle Zou; Zhenhua Li; Liang Chen; Jialin Cao; Kun Zhang; Yongguo Cui (Natural Resources Research, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Spatial-Temporal Change of Phytoplankton Biomass in the East China Sea with MODIS Data - Yumei Wu; Haopeng Zhu; Xiaoyan Dang; Tianfei Cheng; Shenglong Yang; Lin Wang; Liangmin Huang; Xuesen Cui (Journal of Ocean University of China, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

KLF4 Exerts Sedative Effects in Pentobarbital-Treated Mice - Ziqian Cheng; Wei Yang; Bingjin Li; Ranji Cui (Journal of Molecular Neuroscience, 2021)

miR-9-5p facilitates hepatocellular carcinoma cell proliferation, migration and invasion by targeting ESR1 - Libing Wang; Mingxin Cui; Daming Cheng; Fengzhi Qu; Jingkun Yu; Yanbin Wei; Ling Cheng; Xiaotang Wu; Xiaogang Liu (Molecular and Cellular Biochemistry, 2021)

Characterization of Novel Bacteriophage AhyVDH1 and Its Lytic Activity Against Aeromonas hydrophila - Yahui Cheng; Dongye Gao; Yunsheng Xia; Ziyi Wang; Meng Bai; Kaijun Luo; Xiaolong Cui; Yongxia Wang; Shiying Zhang; Wei Xiao (Current Microbiology, 2021)

Progress and prospects of applied research on physical geography and the living environment in China over the past 70 years (1949–2019) - Fahu Chen; Shaohong Wu; Peng Cui; Yunlong Cai; Yili Zhang; Yunhe Yin; Guobin Liu; Zhu Ouyang; Wei Ma; Linsheng Yang; Duo Wu; Jiaqiang Lei; et al. (Journal of Geographical Sciences, 2021)

Identification of anthocyanin biosynthesis related microRNAs and total microRNAs in Lonicera edulis by high-throughput sequencing - Jie Cui; Zengle Gao; Binsheng Li; Junliang Li; Xinyan Li; Congyu Wang; Dayou Cheng; Cuihong Dai (Journal of Genetics, 2020)

Snapshot of Peptidomics of the Red Tide Forming Species Noctiluca scintillans - Shuwen Zhang; Cheng Li; Shunyan Cheung; Mingming Sun; Shuqun Song; Wang Guo; Cui Guo; Gongguo Wu; Hongbin Liu (Frontiers in Marine Science, 2020)

Ecological risk resonance of urbanization and its effect on geohazard disaster: the case of Freetown, Sierra Leone - Wen Jin; Yifei Cui; Shengnan Wu; Deqiang Cheng (Urban Ecosystems, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Correction to: Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Isolation and expression analysis of a CBF transcriptional factor gene from the mangrove Bruguiera gymnorrhiza - Ya-Lan Peng; You-Shao Wang; Jiao Fei; Hao Cheng; Cui-Ci Sun (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Comprehensive proppant settling model in hydraulic fractures of unconventional gas reservoir considering multifactorial influence - Chuanzhi Cui; Zhen Wang; Zhongwei Wu; Xiangzhi Cheng; Yinzhu Ye (Arabian Journal of Geosciences, 2020)

Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

Source characterization of nitrate in groundwater using hydrogeochemical and multivariate statistical analysis in the Muling-Xingkai Plain, Northeast China - Chen Su; Fenge Zhang; Xiaoshun Cui; Zhongshuang Cheng; Zhaoxian Zheng (Environmental Monitoring and Assessment, 2020)

DhLHY, a Circadian Expressed Gene of Doritaenopsis Hybrid, Promotes Floral Transition in Low Temperature, but Postpones Flowering in Overexpressed Transgenic Arabidopsis - Chi Zhang; Qian Cheng; Haiyan Li; Ping Luo; Yongyi Cui (Tropical Plant Biology, 2020)

Numerical Prediction of the Bridge Subsidence Induced by Longwall Mining: A Case Study of the Majiagou Bridge - Feng Cui; Yingchun Li; Xin Xu; Xiaofeng Cheng (Geotechnical and Geological Engineering, 2020)

Intelligent Marine Robotics Modelling, Simulation and Applications - Cheng Siong Chin; Rongxin Cui (Journal of Marine Science and Engineering, 2020)
Creating this inaugural Special Issue on Intelligent Marine Robotics Modelling, Simulation, and Applications is important due to the rapid technological advancement and the aim to reduce human involvement via artificial intelligence [...]

High-frequency direct shoot organogenesis from garlic (Allium sativum L.) inflorescence and clonal fidelity assessment in regenerants - Yan-Bin Wen; Xiao-Xue Liu; Hong-Jiu Liu; Cui-Nan Wu; Huan-Wen Meng; Zhi-Hui Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Fine mapping of restorer-of-fertility gene based on high-density genetic mapping and collinearity analysis in pepper (Capsicum annuum L.) - Jiaowen Cheng; Yijian Chen; Yafei Hu; Ziyan Zhou; Fang Hu; Jichi Dong; Weili Chen; Junjie Cui; Zhiming Wu; Kailin Hu (Theoretical and Applied Genetics, 2020)

Research on the influence of land use change to habitat of cranes in Shengjin Lake wetland - Lei Fang; Bin Dong; Cheng Wang; Fei Yang; Yanglin Cui; Wenrui Xu; Liang Peng; Yuting Wang; Haoran Li (Environmental Science and Pollution Research, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Composition and change in the microbiome of Diaphorina citri infected with Candidatus Liberibacter asiaticus in China - Xiao-bing Song; Ai-tian Peng; Jin-feng Ling; Yi-ping Cui; Bao-ping Cheng; Lian-hui Zhang (International Journal of Tropical Insect Science, 2019)

Fracturing fluid retention in shale gas reservoirs:mechanisms and functions - Lijun You; Yang Zhou; Yili Kang; Bin Yang; Zhongyu Cui; Qiuyang Cheng (Arabian Journal of Geosciences, 2019)

Two new polyketides isolated from a diethyl sulphate mutant of marine-derived Penicillium purpurogenum G59 - Chang-Jing Wu; Hua Qiao; Cheng-Bin Cui; Yu Yang; Rui Xu; Chun-Xiao Sun; De-Hai Li; Chang-Wei Li (Natural Product Research, 2019)

From Analysis of Ischemic Mouse Brain Proteome to Identification of Human Serum Clusterin as a Potential Biomarker for Severity of Acute Ischemic Stroke - Hailong Song; Hui Zhou; Zhe Qu; Jie Hou; Weilong Chen; Weiwu Cai; Qiong Cheng; Dennis Y. Chuang; Shanyan Chen; Shuwei Li; Jilong Li; Jianlin Cheng; et al. (Translational Stroke Research, 2019)

2,3,7,8-Tetrachlorodibenzo-p-dioxin-induced aryl hydrocarbon receptor activation enhanced the suppressive function of mesenchymal stem cells against splenocyte proliferation - Guorui Zhang; Xiaoming Li; Yi Cheng; Haiyang Yu; Wen Gu; Zhilei Cui; Xuejun Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Influence of Vitamin D Status and Mechanical Loading on the Morphometric and Mechanical Properties of the Mouse Tibia - Yong-Tao Lu; Zhen-Tao Cui; Han-Xing Zhu; Ru-Kun Ma; Cheng-Wei Wu (Journal of Medical and Biological Engineering, 2019)

The discovery and extraction of Chinese ink characters from the wood surfaces of the Huangchangticou tomb of Western Han Dynasty - Taixia Wu; Qian Cheng; Jiangfeng Wang; Shengkuan Cui; Shudong Wang (Archaeological and Anthropological Sciences, 2019)

CNOT3 contributes to cisplatin resistance in lung cancer through inhibiting RIPK3 expression - Lin Jing; Meng-En Zhai; Jian Cui; Xin-Yu Fan; Yuan-Yuan Cheng; Jian-Li Jiang; Zhi-Nan Chen (Apoptosis, 2019)

Preparation and DEA removal performance of iron-modified activated carbon - H. Li; F. Cui; F. Zhang; J. Cui; Q. Meng; J. Cheng (International Journal of Environmental Science and Technology, 2019)

Seabed deposition and erosion change and influence factors in the Yangshan Deepwater Port over the years - Shuhua Zuo; Hualiang Xie; Xiaoming Ying; Cheng Cui; Yuxin Huang; Huaiyuan Li; Mingxiao Xie (Acta Oceanologica Sinica, 2019)

Upregulation of MicroRNA miR-9 Is Associated with Microcephaly and Zika Virus Infection in Mice - Haijun Zhang; Yafei Chang; Longbin Zhang; Seung-Nam Kim; Gaizka Otaegi; Zhen Zhang; Yanzhen Nie; Taufif Mubarak; Cui Li; Cheng-Feng Qin; Zhiheng Xu; Tao Sun (Molecular Neurobiology, 2019)

The cost of rapid and haphazard urbanization: lessons learned from the Freetown landslide disaster - Yifei Cui; Deqiang Cheng; Clarence E. Choi; Wen Jin; Yu Lei; Jeffrey S. Kargel (Landslides, 2019)

Macrophyte identity shapes water column and sediment bacterial community - Yanran Dai; Juan Wu; Fei Zhong; Naxin Cui; Lingwei Kong; Wei Liang; Shuiping Cheng (Hydrobiologia, 2019)

Effect and threshold of PM2.5 on population mortality in a highly polluted area: a study on applicability of standards - Runze Ye; Liangliang Cui; Xiumiao Peng; Kunkun Yu; Fang Cheng; Yakun Zhu; Chongqi Jia (Environmental Science and Pollution Research, 2019)

Comprehensive prediction of coal seam thickness by using in-seam seismic surveys and Bayesian kriging - Mengbo Zhu; Jianyuan Cheng; Weixiong Cui; Hui Yue (Acta Geophysica, 2019)

Moso bamboo (Phyllostachys edulis) invasion effects on litter, soil and microbial PLFA characteristics depend on sites and invaded forests - Xishuai Liu; Evan Siemann; Cheng Cui; Yuanqiu Liu; Xiaomin Guo; Ling Zhang (Plant and Soil, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

A Novel Method for Agricultural Drought Risk Assessment - Wei Pei; Qiang Fu; Dong Liu; Tianxiao Li; Kun Cheng; Song Cui (Water Resources Management, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Differentiations of geographic distribution and subsistence strategies between Tibetan and other major ethnic groups are determined by the physical environment in Hehuang Valley - Xin Jia; Harry F. Lee; Mengchun Cui; Guoquan Cheng; Yang Zhao; Hong Ding; Ricci P. H. Yue; Huayu Lu (Science China Earth Sciences, 2019)

Erosion and transport mechanisms of mine waste along gullies - Xing-hua Zhu; Yi-fei Cui; Jian-bing Peng; Cheng Jiang; Wei-long Guo (Journal of Mountain Science, 2019)

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Relative trajectory-driven virtual dynamic occlusal adjustment for dental restorations - Sukun Tian; Ning Dai; Xiaosheng Cheng; Linlin Li; Yuchun Sun; Haihua Cui (Medical & Biological Engineering & Computing, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Characterization of miRNA160/164 and Their Targets Expression of Beet (Beta vulgaris) Seedlings Under the Salt Tolerance - Jie Cui; Zongyan Sun; Junliang Li; Dayou Cheng; Chengfei Luo; Cuihong Dai (Plant Molecular Biology Reporter, 2018)

Genetic characteristics of the P1 coding region of Coxsackievirus A16 associated with hand, foot, and mouth disease in China - Li Xu; Dawei Cui; Lei Wang; Jun Cheng; Changgui Sun; Lanjuan Li; Hongcui Cao (Molecular Biology Reports, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Ascidiaceibacter salegens gen. nov., sp. nov., isolated from an ascidian - Lei Chen; Shi-Cheng Wang; Cui-Hong Ma; Dong-Xu Zheng; Zong-Jun Du; Guang-Yu Wang (Antonie van Leeuwenhoek, 2018)

Multifractal Detrended Fluctuation Analysis of Regional Precipitation Sequences Based on the CEEMDAN-WPT - Dong Liu; Chen Cheng; Qiang Fu; Chunlei Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Imran Khan; Song Cui (Pure and Applied Geophysics, 2018)

Apparent permeability and representative size of shale: a numerical study on the effects of organic matter - Jiangfeng Cui; Long Cheng; Lei Li (Computational Geosciences, 2018)

Spatiotemporal analysis of the agricultural drought risk in Heilongjiang Province, China - Wei Pei; Qiang Fu; Dong Liu; Tian-xiao Li; Kun Cheng; Song Cui (Theoretical and Applied Climatology, 2018)

Preparation and Cr(VI) removal performance of corncob activated carbon - Hongyan Li; Pei Gao; Jianguo Cui; Feng Zhang; Fang Wang; Jici Cheng (Environmental Science and Pollution Research, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

The characteristics of the Mocoa compound disaster event, Colombia - Deqiang Cheng; Yifei Cui; Fenghuan Su; Yang Jia; Clarence Edward Choi (Landslides, 2018)

Review of CRISPR/Cas9 sgRNA Design Tools - Yingbo Cui; Jiaming Xu; Minxia Cheng; Xiangke Liao; Shaoliang Peng (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Cadmium exposure and early renal effects in the children and adults living in a tungsten-molybdenum mining areas of South China - Xiangfen Cui; Hongguang Cheng; Xuelian Liu; Elisa Giubilato; Andrea Critto; Haixu Sun; Lei Zhang (Environmental Science and Pollution Research, 2018)

Fate of antibiotic and metal resistance genes during two-phase anaerobic digestion of residue sludge revealed by metagenomic approach - Ying Wu; Erping Cui; Yiru Zuo; Weixiao Cheng; Hong Chen (Environmental Science and Pollution Research, 2018)

Experimental infection of Marmota monax with a novel hepatitis A virus - Jie-mei Yu; Li-li Li; Guang-cheng Xie; Cui-yuan Zhang; Yuan-yun Ao; Zhao-jun Duan (Archives of Virology, 2018)

Bacterial community structure and abundances of antibiotic resistance genes in heavy metals contaminated agricultural soil - Fengli Zhang; Xiaoxue Zhao; Qingbo Li; Jia Liu; Jizhe Ding; Huiying Wu; Zongsheng Zhao; Yue Ba; Xuemin Cheng; Liuxin Cui; Hongping Li; Jingyuan Zhu (Environmental Science and Pollution Research, 2018)

Development of Brassica oleracea-nigra monosomic alien addition lines: genotypic, cytological and morphological analyses - Chen Tan; Cheng Cui; Yi Xiang; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Numerical simulation of dynamic response around shield tunnel in the soft soil area - Cheng-Lin Zhang; Zhen-Dong Cui (Marine Georesources & Geotechnology, 2017)

Temporal–spatial variability of atmospheric and hydrological natural disasters during recent 500 years in Inner Mongolia, China - Yu Peng; Jingyi Song; Tiantian Cui; Xiang Cheng (Natural Hazards, 2017)

Influence of nitrogen loading and flooding on seedling emergence and recruitment from a seed bank in Chaohu Lake Basin, China - Naxin Cui; Juan Wu; Yanran Dai; Zhu Li; Shuiping Cheng (Environmental Science and Pollution Research, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

Projected Changes of Future Extreme Drought Events under Numerous Drought Indices in the Heilongjiang Province of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Qaisar Saddique; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Uzair Qamar; Song Cui; Chen Cheng (Water Resources Management, 2017)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

A preliminary study on ore-forming environments of Xianglushan-type iron deposit and the weathering mineralization of Emeishan basalt in Guizhou Province, China - Guofan Cheng; Youping Liu; Hansheng Long; Tao Cui; Ning Yu (Acta Geochimica, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Clinical feature and waveform in infantile nystagmus syndrome in children with FRMD7 gene mutations - Dayong Bai; Wei Shi; Zhan Qi; Wei Li; Aihua Wei; Yanhui Cui; Cheng Li; Li Li (Science China Life Sciences, 2017)

Effects of calcium at toxic concentrations of cadmium in plants - Danlian Huang; Xiaomin Gong; Yunguo Liu; Guangming Zeng; Cui Lai; Hassan Bashir; Lu Zhou; Dafei Wang; Piao Xu; Min Cheng; Jia Wan (Planta, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

Comparative Studies on the Toxicokinetics of Benzo[a]pyrene in Pinctada martensii and Perna viridis - Haihua Wang; Lili Cui; Huamin Cheng; Yu Zhang; Xiaoping Diao; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

A Novel, Multi-Target Natural Drug Candidate, Matrine, Improves Cognitive Deficits in Alzheimer’s Disease Transgenic Mice by Inhibiting Aβ Aggregation and Blocking the RAGE/Aβ Axis - Lili Cui; Yujie Cai; Wanwen Cheng; Gen Liu; Jianghao Zhao; Hao Cao; Hua Tao; Yan Wang; Mingkang Yin; Tingting Liu; Yu Liu; Pengru Huang; et al. (Molecular Neurobiology, 2017)

Dam-break risk analysis of the Attabad landslide dam in Pakistan and emergency countermeasures - Xiaoqing Chen; Peng Cui; Yong You; Zunlan Cheng; Asif Khan; Chengyin Ye; Shu Zhang (Landslides, 2017)

Evaluation of the land carrying capacity of major grain-producing areas and the identification of risk factors - Kun Cheng; Qiang Fu; Song Cui; Tian-xiao Li; Wei Pei; Dong Liu; Jun Meng (Natural Hazards, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

The morphology, ultrastructure, element distribution and motion behaviour in pollen of Ginkgo biloba L. - Yan Lu; Li Zhang; Fangmei Cheng; Jianguo Zhao; Jiawen Cui; Weixing Li; Li Wang; Biao Jin (Trees, 2016)

Synergistic Interactions Between Salt-tolerant Rhizobia and Arbuscular Mycorrhizal Fungi on Salinity Tolerance of Sesbania cannabina Plants - Cheng-Gang Ren; Yue-Jie Bai; Cun-Cui Kong; Bian Bian; Zhi-Hong Xie (Journal of Plant Growth Regulation, 2016)

Does Fluoride Affect Serum Testosterone and Androgen Binding Protein with Age-Specificity? A Population-Based Cross-Sectional Study in Chinese Male Farmers - Leizhen Duan; Jingyuan Zhu; Keyan Wang; Guoyu Zhou; Yuejin Yang; Liuxin Cui; Hui Huang; Xuemin Cheng; Yue Ba (Biological Trace Element Research, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans - Xiaoxiang Yang; Hui Cui; Jiasen Cheng; Jiatao Xie; Daohong Jiang; Tom Hsiang; Yanping Fu (Environmental Microbiology, 2016)
Summary Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

A disputed evidence on obesity: comparison of the effects of Rcan2−/− and Rps6kb1−/− mutations on growth and body weight in C57BL/6J mice - Jing Zhao; Shi-wei Li; Qian-qian Gong; Ling-cui Ding; Ye-cheng Jin; Jian Zhang; Jian-gang Gao; Xiao-yang Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Expression and functional analysis of two NhaD type antiporters from the halotolerant and alkaliphilic Halomonas sp. Y2 - Yanbing Cui; Bin Cheng; Yiwei Meng; Chunfang Li; Huijia Yin; Ping Xu; Chunyu Yang (Extremophiles, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Distinct subgenome stabilities in synthesized Brassica allohexaploids - Jiannan Zhou; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Roseomonas chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from activated sludge - Cui-Wei Chu; Qing Chen; Cheng-Hong Wang; Hong-Mei Wang; Zhong-Guan Sun; Qin He; Jian He; Jin-Gang Gu (Antonie van Leeuwenhoek, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Enhancing the water purification efficiency of a floating treatment wetland using a biofilm carrier - Lingling Zhang; Jing Zhao; Naxin Cui; Yanran Dai; Lingwei Kong; Juan Wu; Shuiping Cheng (Environmental Science and Pollution Research, 2016)

Occurrence and Partitioning of Antibiotics in the Water Column and Bottom Sediments from the Intertidal Zone in the Bohai Bay, China - Dengmiao Cheng; Yujia Xie; Yanjun Yu; Xinhui Liu; Shengnan Zhao; Baoshan Cui; Junhong Bai (Wetlands, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

High Sensitivity Bacillus thuringiensis Cry1Ac Protein Detections Using Fluorescein Diacetate Nanoparticles - Cui Liu; Zhen Zhou; Linling Zou; Yuan-Cheng Cao; Jun’An Liu; Yongjun Lin (Journal of Fluorescence, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Role of microRNA-195 in cardiomyocyte apoptosis induced by myocardial ischaemia–reperfusion injury - CHANG-KUI GAO; HUI LIU; CHENG-JI CUI; ZHAO-GUANG LIANG; HONG YAO; YE TIAN (Journal of Genetics, 2016)

Simultaneous refolding of denatured PsbS and reconstitution with LHCII into liposomes of thylakoid lipids - Cheng Liu; Zhimin Gao; Kun Liu; Ruixue Sun; Chunbo Cui; Alfred R. Holzwarth; Chunhong Yang (Photosynthesis Research, 2016)

Transplantation of Cerebral Dopamine Neurotrophic Factor Transducted BMSCs in Contusion Spinal Cord Injury of Rats: Promotion of Nerve Regeneration by Alleviating Neuroinflammation - Hua Zhao; Lei Cheng; Xinwen Du; Yong Hou; Yi Liu; Zhaoqiang Cui; Lin Nie (Molecular Neurobiology, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

RETRACTED ARTICLE: Effects of Common Polymorphisms in the MTHFR and ACE Genes on Diabetic Peripheral Neuropathy Progression: a Meta-Analysis - Shuai Wu; Yan Han; Qiang Hu; Xiao-Jie Zhang; Guang-Cheng Cui; Ze-Zhi Li; Yang-tai Guan (Molecular Neurobiology, 2015)

Acclimation of Hydrilla verticillata to sediment anoxia in vegetation restoration in eutrophic waters - Juan Wu; Yanran Dai; Shengyang Rui; Naxin Cui; Fei Zhong; Shuiping Cheng (Ecotoxicology, 2015)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

A review of soil cadmium contamination in China including a health risk assessment - Lin Wang; Xiangfen Cui; Hongguang Cheng; Fei Chen; Jiantong Wang; Xinyi Zhao; Chunye Lin; Xiao Pu (Environmental Science and Pollution Research, 2015)

Distribution and sources of the polycyclic aromatic hydrocarbons in the sediments of the Pearl River estuary, China - Jian-Dong Zhang; You-Shao Wang; Hao Cheng; Zhao-Yu Jiang; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Variation of phytoplankton community structure from the Pearl River estuary to South China Sea - Zhao-Yu Jiang; You-Shao Wang; Hao Cheng; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Ecophysiological differences between three mangrove seedlings (Kandelia obovata, Aegiceras corniculatum, and Avicennia marina) exposed to chilling stress - Ya-Lan Peng; You-Shao Wang; Jiao Fei; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Pb uptake and tolerance in the two selected mangroves with different root lignification and suberization - Hao Cheng; You-Shao Wang; Yong Liu; Zhi-Hong Ye; Mei-Lin Wu; Cui-Ci Sun (Ecotoxicology, 2015)

Spatial and vertical distribution of bacterial community in the northern South China Sea - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Aeration and fermentation strategies on nisin production - Liyan Jiang; Yan Liu; Guodong Yan; Yuxiao Cui; Qiyue Cheng; Zaixiao Zhang; Qingfan Meng; Lirong Teng; Xiaodong Ren (Biotechnology Letters, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Response of extracellular carboxylic and thiol ligands (oxalate, thiol compounds) to Pb2+ stress in Phanerochaete chrysosporium - Ningjie Li; Guangming Zeng; Danlian Huang; Chao Huang; Cui Lai; Zhen Wei; Piao Xu; Chen Zhang; Min Cheng; Ming Yan (Environmental Science and Pollution Research, 2015)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Diversity in the Toll-like receptor genes of the Tasmanian devil (Sarcophilus harrisii) - Jian Cui; Yuanyuan Cheng; Katherine Belov (Immunogenetics, 2015)

Effects of water quality of the basin caused by nitrogen loss from soil in drought - B. B. Huang; D. H. Yan; H. Wang; B. F. Cheng; X. H. Cui (Natural Hazards, 2015)

Seed banks and their implications of rivers with different trophic levels in Chaohu Lake Basin, China - Naxin Cui; Juan Wu; Fei Zhong; Lihua Yang; Dongfang Xiang; Shuiping Cheng; Qi Zhou (Environmental Science and Pollution Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Using enriched stable isotope technique to study Cu bioaccumulation and bioavailability in Corbicula fluminea from Taihu Lake, China - Wenhong Fan; Jinqian Ren; Chenguang Wu; Cheng Tan; Xiaolong Wang; Minming Cui; Kuang Wu; Xiaomin Li (Environmental Science and Pollution Research, 2014)

Protoplast fusion enhances lignocellulolytic enzyme activities in Trichoderma reesei - Yu-xiao Cui; Jia-jing Liu; Yan Liu; Qi-yue Cheng; Qun Yu; Xin Chen; Xiao-dong Ren (Biotechnology Letters, 2014)

Study on the estimation of groundwater withdrawals based on groundwater flow modeling and its application in the North China Plain - Jingli Shao; Yali Cui; Qichen Hao; Zhong Han; Tangpei Cheng (Journal of Earth Science, 2014)

Parallel simulation of groundwater flow in the North China Plain - Tangpei Cheng; Jingli Shao; Yali Cui; Zeyao Mo; Zhong Han; Ling Li (Journal of Earth Science, 2014)

Radon-induced demethylation of Cdk2 CpG island in the rat lung - Cheng Wu; Xin Xie; Fengmei Cui; Yang Jiao; Dandan Qi; Jihua Nie; Tom K. Hei; Qisheng Jiang; Qiu Chen; Jian Tong (Genes & Genomics, 2014)

Association of interleukin-23 receptor gene polymorphisms with risk of bladder cancer in Chinese - Tielong Tang; Hui Xue; Shu Cui; Zhiyong Gong; Zhonghai Fei; Shulin Cheng; Chunyan Gui (Familial Cancer, 2014)

Expression and localization of transcription factors SNAIL and SLUG in mouse ovaries and pre-implantation embryos - Cui Guo; Xiaoqian Meng; Jing Bai; Cheng Chen; Tao Liu; Shuzhen Liu; Cong Zhang; Wei-Ping Li (Cell and Tissue Research, 2014)

Erratum to: Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

A bioinformatics method for predicting long noncoding RNAs associated with vascular disease - JianWei Li; Cheng Gao; YuChen Wang; Wei Ma; Jian Tu; JunPei Wang; ZhenZhen Chen; Wei Kong; QingHua Cui (Science China Life Sciences, 2014)

Molecular cloning and characterization of NPR1 gene from Arachis hypogaea - Qi Wu; Xiu Zhen Wang; Yue Yi Tang; Hong Tao Yu; Yu Fei Ding; Chuan De Yang; Feng Gao Cui; Jian Cheng Zhang; Chuan Tang Wang (Molecular Biology Reports, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

3D-QSAR study using CoMFA and CoMSIA methods for a series of histone H3 phosphorylation inhibitors - Guo-Wu Rao; Cheng-Hai Hu; Jia-Bin Ni; Jian Wang; Cui Wang; Bing-Lan Wang (Medicinal Chemistry Research, 2014)

Activated macrophage-like synoviocytes are resistant to endoplasmic reticulum stress-induced apoptosis in antigen-induced arthritis - Li-Jie Feng; Tong-Cui Jiang; Cheng-Yue Zhou; Chang-Liang Yu; Yu-Jun Shen; Jun Li; Yu-Xian Shen (Inflammation Research, 2014)

Mouse organ coefficient and abnormal sperm rate analysis with exposure to tap water and source water in Nanjing reach of Yangtze River - Rongfei Zhang; Liujun Zhang; Dongsheng Jiang; Kai Zheng; Yibin Cui; Mei Li; Bing Wu; Shupei Cheng (Ecotoxicology, 2014)

Low Glucose Utilization and Neurodegenerative Changes Caused by Sodium Fluoride Exposure in Rat’s Developmental Brain - Chunyang Jiang; Shun Zhang; Hongliang Liu; Zhizhong Guan; Qiang Zeng; Cheng Zhang; Rongrong Lei; Tao Xia; Zhenglun Wang; Lu Yang; Yihu Chen; Xue Wu; et al. (NeuroMolecular Medicine, 2014)

Effect of BRAF V600E mutation on tumor response of anti-EGFR monoclonal antibodies for first-line metastatic colorectal cancer treatment: a meta-analysis of randomized studies - Dandan Cui; Dan Cao; Yu Yang; Meng Qiu; Ying Huang; Cheng Yi (Molecular Biology Reports, 2014)

Isolation and characterization of 57 novel polynucleotide microsatellites from yellow catfish (Pelteobagrus fulvidraco) genome for genetic analysis - Yun-Jing Shan; Cui-Yun Lu; Chao Li; Lei Cheng; Xiao-Wen Sun (Conservation Genetics Resources, 2014)

Development and characterization of new microsatellite markers for Amur sturgeon (Acipenser schrenckii) - Yang Liu; Chao Li; Lei Cheng; Cui-Yun Lu; Xiao-Wen Sun (Conservation Genetics Resources, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

Mechanisms of Anti-inflammatory Property of Conserved Dopamine Neurotrophic Factor: Inhibition of JNK Signaling in Lipopolysaccharide-Induced Microglia - Hua Zhao; Lei Cheng; Yi Liu; Wen Zhang; Sailendra Maharjan; Zhaoqiang Cui; Xingli Wang; Dongqi Tang; Lin Nie (Journal of Molecular Neuroscience, 2014)

Molecular phylogeny and morphology reveal a new species of Amyloporia (Basidiomycota) from China - Bao-Kai Cui; Yu-Cheng Dai (Antonie van Leeuwenhoek, 2013)

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

Development and characterization of four moderate multiplex microsatellite panels in crucian carp (Carassius auratus) - Lei Cheng; Yan Zhang; Cui-Yun Lu; Chao Li; Xiao-Wen Sun (Conservation Genetics Resources, 2013)

Changes in the Foxj1 expression of Schwann cells after sciatic nerve crush - Jianhua Cao; Xinghai Cheng; Zhengming Zhou; Huiqing Sun; Feng Zhou; Jing Zhao; Yonghua Liu; Gang Cui (Journal of Molecular Histology, 2013)

Microarray analysis of differentially expressed transcripts in porcine intestinal epithelial cells (IPEC-J2) infected with porcine sapelovirus as a model to study innate immune responses to enteric viruses - Daoliang Lan; Cheng Tang; Hua Yue; Huan Sun; Li Cui; Xiuguo Hua; Jian Li (Archives of Virology, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Prediction of the binding modes between macrolactin N and peptide deformylase from Staphylococcus aureus by molecular docking and molecular dynamics simulations - Jian Gao; Yuanhua Cheng; Wei Cui; Fushi Zhang; Huai Zhang; Yuguo Du; Mingjuan Ji (Medicinal Chemistry Research, 2013)

Oncolytic adenovirus co-expressing miRNA-34a and IL-24 induces superior antitumor activity in experimental tumor model - Wenjia Lou; Qing Chen; Leina Ma; Jia Liu; Zhi Yang; Junjie Shen; Youhong Cui; Xiu-wu Bian; Cheng Qian (Journal of Molecular Medicine, 2013)

An experimental and numerical study of the freak wave speed - Cheng Cui; Ningchuan Zhang; Haigui Kang; Yuxiu Yu (Acta Oceanologica Sinica, 2013)

Erratum to: Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Duu-Jong Lee; Aijie Wang (Environmental Science and Pollution Research, 2013)

Development of InDel markers for Brassica rapa based on whole-genome re-sequencing - Bo Liu; Yan Wang; Wen Zhai; Jie Deng; Hui Wang; Yang Cui; Feng Cheng; Xiaowu Wang; Jian Wu (Theoretical and Applied Genetics, 2013)

Grid interpolation algorithm based on nearest neighbor fast search - Hao Huang; Can Cui; Liang Cheng; Qiang Liu; Jiechen Wang (Earth Science Informatics, 2012)

Cerium Chloride Improves Protein and Carbohydrate Metabolism of Fifth-Instar Larvae of Bombyx mori Under Phoxim Toxicity - Bing Li; Yi Xie; Zhe Cheng; Jie Cheng; Rengping Hu; Xuezi Sang; Suxin Gui; Qingqing Sun; Xiaolan Gong; Yaling Cui; Weide Shen; Fashui Hong (Biological Trace Element Research, 2012)

Interacting Partners of AMPA-Type Glutamate Receptors - Juan Cheng; Jie Dong; Yaxuan Cui; Liecheng Wang; Bei Wu; Chen Zhang (Journal of Molecular Neuroscience, 2012)

Molecular characterization of a novel AP2 transcription factor ThWIND1-L from Thellungiella halophila - Cheng Zhou; Jiansheng Guo; Zhenhua Feng; Xianghuan Cui; Jian Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

The response of Mo-hydroxylases and abscisic acid to salinity in wheat genotypes with differing salt tolerances - Haixia Xu; Jinling Zhai; Yanli Liu; Xiyong Cheng; Zhihui Xia; Feng Chen; Dangqun Cui; Xingyu Jiang (Acta Physiologiae Plantarum, 2012)

3D-QSAR and molecular docking studies of hydroxamic acids as peptide deformylase inhibitors - Jian Gao; Yuanhua Cheng; Wei Cui; Quan Chen; Fushi Zhang; Yuguo Du; Mingjuan Ji (Medicinal Chemistry Research, 2012)

Effects of pyrene on antioxidant systems and lipid peroxidation level in mangrove plants, Bruguiera gymnorrhiza - Hui Song; You-Shao Wang; Cui-Ci Sun; Yu-Tu Wang; Ya-Lan Peng; Hao Cheng (Ecotoxicology, 2012)

Erratum to: A 90-day safety study of genetically modified rice expressing rhIGF-1 protein in C57BL/6J mice - Maoxue Tang; Tingting Xie; Wenke Cheng; Lili Qian; Shulin Yang; Daichang Yang; Wentao Cui; Kui Li (Transgenic Research, 2012)

Erratum to: The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zhao; Zhe Cheng; Jie Cheng; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

The Influence of Fluoride on the Expression of Inhibitors of Wnt/β-Catenin Signaling Pathway in Rat Skin Fibroblast Cells - Xiao-Li Liu; Chang-Cheng Li; Ke-Jian Liu; Cai-Yan Cui; Yu-Zeng Zhang; Yun Liu (Biological Trace Element Research, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Aijie Wang (Environmental Science and Pollution Research, 2012)

Effects of Added CeCl3 on Resistance of Fifth-Instar Larvae of Silkworm to Bombyx mori Nucleopolyhedrovirus Infection - Bing Li; Yi Xie; Zhe Cheng; Jie Cheng; Rengping Hu; Yaling Cui; Xiaolan Gong; Weide Shen; Fashui Hong (Biological Trace Element Research, 2012)

A 90-day safety study of genetically modified rice expressing rhIGF-1 protein in C57BL/6J rats - Maoxue Tang; Tingting Xie; Wenke Cheng; Lili Qian; Shulin Yang; Daichang Yang; Wentao Cui; Kui Li (Transgenic Research, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

Identification of single nucleotide polymorphisms and haplotypes associated with yield and yield components in soybean (Glycine max) landraces across multiple environments - Derong Hao; Hao Cheng; Zhitong Yin; Shiyou Cui; Dan Zhang; Hui Wang; Deyue Yu (Theoretical and Applied Genetics, 2012)

Genetic variation and population structure of swimming crab (Portunus trituberculatus) inferred from mitochondrial control region - Enmian Guo; Yuan Liu; Zhaoxia Cui; Xilian Li; Yongxu Cheng; Xugan Wu (Molecular Biology Reports, 2012)

Liver Injury and Its Molecular Mechanisms in Mice Caused by Exposure to Cerium Chloride - Haiquan Zhao; Jie Cheng; Jingwei Cai; Zhe Cheng; Yaling Cui; Guodong Gao; Renping Hu; Xiaolan Gong; Ling Wang; Fashui Hong (Archives of Environmental Contamination and Toxicology, 2012)

The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zha; Zhe Cheng; Jie Chen; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Thyroid disruption effects of environmental level perfluorooctane sulfonates (PFOS) in Xenopus laevis - Yan Cheng; Yuan Cui; Hui-ming Chen; Wen-ping Xie (Ecotoxicology, 2011)

Molecular characterization and NF-κB-regulated transcription of selenoprotein S from the Bama mini-pig - Ningbo Zhang; Wenqian Jing; Jiayue Cheng; Wentao Cui; Yulian Mu; Kui Li; Xingen Lei (Molecular Biology Reports, 2011)

Association of Dental Fluorosis with Polymorphisms of Estrogen Receptor Gene in Chinese Children - Yue Ba; Huizhen Zhang; Gang Wang; Shibao Wen; Yuejin Yang; Jingyuan Zhu; Lijun Ren; Rupu Yang; Cairong Zhu; Haixia Li; Xuemin Cheng; Liuxin Cui (Biological Trace Element Research, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Safety assessment of sFat-1 transgenic pigs by detecting their co-habitant microbe in intestinal tract - Maoxue Tang; Xinmin Zheng; Wenke Cheng; Erhui Jin; Hongxing Chen; Shulin Yang; Wentao Cui; Kui Li (Transgenic Research, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Three new species of Inonotus (Basidiomycota, Hymenochaetaceae) from China - Bao-Kai Cui; Ping Du; Yu-Cheng Dai (Mycological Progress, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

SSeCKS promote beta-amyloid-induced PC12 cells neurotoxicity by up-regulating tau phosphorylation in Alzheimer’s disease - Zhiming Cui; Tao Tao; Chun Cheng; Junling Yang; Qin Shen; Yuhong Ji; Xiaohong Li; Haiou Liu; Aiguo Shen; Xiang Lu (Molecular and Cellular Biochemistry, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Finger-vein image recognition combining modified Hausdorff distance with minutiae feature matching - Cheng-Bo Yu; Hua-Feng Qin; Yan-Zhe Cui; Xiao-Qian Hu (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Trichaptum (Basidiomycota, Hymenochaetales) from China with a description of three new species - Yu-Cheng Dai; Bao-Kai Cui; Hai-Sheng Yuan (Mycological Progress, 2009)

Effects of the Yangtze River source of drinking water on metabolites of Mus musculus - Yan Zhang; Dayong Zhao; Bing Wu; Fang Hu; Jie Kong; Xuxiang Zhang; Mei Li; Yibin Cui; Shupei Cheng (Ecotoxicology, 2009)

Extracellular proteomic analysis for degradation of PAHs in source of drinking water with fusant strains - Bing Wu; Xuxiang Zhang; Yan Zhang; Dayong Zhao; Yibin Cui; Shupei Cheng (Ecotoxicology, 2009)

Degradation of benzo(a)pyrene in Yangtze River source water with functional strains - Yan Zhang; Xuxiang Zhang; Bing Wu; Dayong Zhao; Mei Li; Yibin Cui; Tim Ford; Shupei Cheng (Ecotoxicology, 2009)

Toxicity of the Yangtze River source of drinking water on reproductive system of male mice (Mus musculus) - Dayong Zhao; Shupei Cheng; Bing Wu; Yan Zhang; Xuxiang Zhang; Weixin Li; Yibin Cui (Ecotoxicology, 2009)

Detection of quantitative trait loci for phosphorus deficiency tolerance at soybean seedling stage - Dan Zhang; Hao Cheng; Leiyue Geng; Guizhen Kan; Shiyou Cui; Qingchang Meng; Junyi Gai; Deyue Yu (Euphytica, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

On the genesis of granite pits on top of the Shigujian Peak of the Dayangshan Mountain in Jinyun County, Zhejiang Province - Cheng Zhu; Zhijiu Cui; Zhongxuan Li; Jie Gao; Lixin Wang; Xianglin Wu; Chaogui Zheng; Qingfan Shen; Xianzhang Zheng (Journal of Geographical Sciences, 2009)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Analysis of Cry1Ab toxin bioaccumulation in a food chain of Bt rice, an herbivore and a predator - Mao Chen; Gong-yin Ye; Zhi-cheng Liu; Qi Fang; Cui Hu; Yu-fa Peng; Anthony M. Shelton (Ecotoxicology, 2009)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

The roles of endogenous reactive oxygen species and nitric oxide in triptolide-induced apoptotic cell death in macrophages - Xiaofeng Bao; Jun Cui; Yuanyuan Wu; Xiaodong Han; Cheng Gao; Zichun Hua; Pingping Shen (Journal of Molecular Medicine, 2006)

A novel 2-aminophenol 1,6-dioxygenase involved in the degradation of p-chloronitrobenzene by Comamonas strain CNB-1: purification, properties, genetic cloning and expression in Escherichia coli - Jian-Feng Wu; Cui-Wei Sun; Cheng-Ying Jiang; Zhi-Pei Liu; Shuang-Jiang Liu (Archives of Microbiology, 2005)

Preparation and characterization of novel coenzyme Q10 nanoparticles engineered from microemulsion precursors - Cheng-Hsuan Hsu; Zhengrong Cui; Russell J. Mumper; Michael Jay (AAPS PharmSciTech, 2003)

Genetic diversity of alligator weed in China by RAPD analysis - Cheng-Yuan Xu; Wen-Ju Zhang; Cui-Zhang Fu; Bao-Rong Lu (Biodiversity and Conservation, 2003)

Inheritance and expression of the cry1Ab gene in Bt (Bacillus thuringiensis) transgenic rice - G. Wu; H. Cui; G. Ye; Y. Xia; R. Sardana; X. Cheng; Y. Li; I. Altosaar; Q. Shu (Theoretical and Applied Genetics, 2002)

Study of 1998 heavy rainfall over the Yangtze River Basin using TRMM data - Cheng Minghu; He Huizhong; Mao Dongyan; Qi Yanjun; Cui Zhehu; Zhou Fengxian (Advances in Atmospheric Sciences, 2001)